Efficient synthesis of ethyl levulinate from furfuryl alcohol using several biomass-based carbon - Kongde Li; Qikai Si; Guangyu Wu; Guijing Liu; Wei Jiang; Deyang Zhao; Ting Su; Hongwu Zhang; Zhenglong Yang; Christophe Len; Bin He (Biomass and Bioenergy, 2027)

Lactate-enhanced production of a cyclic β-1,2-glucan in Acetobacter pasteurianus - Yong Chen; Yihang Qi; Zhongya Zhou; Xin Liu; Yaping Sun; Ting Liu; Mengru Wu; Hui Li; Jing-yi Zhao; Zijun Xiao (Food Microbiology, 2027)

Drought weakens greenhouse gas sink of global wetlands - Longxin Qiao; Xinxin Wang; Hongyang Chen; Jihua Wu; Xiangming Xiao; Ming Nie; Rui-Ting Ju; Yuhan Zheng; Xi Zhang; Qiang He; Xutong Ru; Lijuan Cui; et al. (Environmental Impact Assessment Review, 2027)

Effect of iron homeostasis on modulating cold-associated ferroptosis related response and sterile inflammation in silver pomfret (Pampus argenteus) - Yunkang Wu; Yuanbo Li; Ting Chen; Wuqiang Xia; Denggui Chen; Xiang Chen; Yajun Wang; Xiaojun Yan; Jiabao Hu (Aquaculture, 2027)

Disinfection byproducts inhibit methane production and emissions in WWTP effluents and receiving rivers - Fanyan Yang; Dongqi Wang; Shu Chen; Jicheng Zhong; Xin Xu; Hechen Sun; Shengnan Wu; Yufang Li; Ting Liu; Ziqi Ren; Guanghui Zhao; Zhongjie Yu; et al. (Water Research, 2026)

Phosphorus-driven electronic modulation on CoP/Co@NC heterostructures for highly efficient and stable hydrogen production in NaBH4 hydrolysis - Kai Jia; Yuhui Qian; Suning Li; Fuying Wu; Guoqiang Liu; Beibei Xiao; Ting Bian; Petr Senin; Liuting Zhang (Fuel, 2026)

Machine learning-assisted quorum sensing molecules regulate growth progression and bioactivity of an oxygenic photobiofilm for non-aeration greywater purification - Beibei Wu; Libo Xia; Qian Li; Xiaocai Cui; Ting Ran; Yangrui Huang; Yun Zhou (Bioresource Technology, 2026)

Chemical constituents of Paratinospora sagittata and their chemotaxonomic significance - Wei Nie; Zhang-Juan Li; Ye-Ting Shi; Ming Hu; Xing-De Wu; Lin-Fen Ding (Biochemical Systematics and Ecology, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

Effects of two enzyme–microbe co-fermented feed formulations on growth performance, ruminal fermentation, serum metabolome, and gastrointestinal microbiota in mid-fattening simmental heifers - Keren Yang; Ting Liu; Hanfang Zeng; Zhenling Wu; Xuanwei Lv; Daiwei Li; Zhiwen Xu; Liming Wei; Dehai An; Shicheng Wang; Chen Zheng (Animal Feed Science and Technology, 2026)

Precise H2 supply enables quantitative control of on-demand deep nitrate removal while preserving denitrification completeness - Ge Yan; Zhen-Xiang Jiang; Jia-Le Wu; Ting Wang; Jun-Tong Hu; Li-Wen Qiu; Chen Zhou; Hongqiang Ren (Water Research, 2026)

XsiAMT1.1a was identified as a novel ammonium uptake functional gene and its overexpression combined with GA4 application significantly increased yield in Arabidopsis thaliana - Xiao Han; Zhao-Hua Gong; Jie Cao; Li-Na Ye; Yuan Cheng; Yu-Xuan Du; Ting-Ting Zhao; Hai-Long Wu; Chang Zhang (Plant Science, 2026)

Diverse bioactive metabolites from Callicarpa longifolia var. floccosa: terpenoids, polyketide, and callilongiflocin A as a potent anti-inflammatory diterpenoid targeting IL-17/TNF-α/MAPK signaling with anti-psoriatic activity - Ting Liu; Xiao-Lu Wu; Lian-Chun Li; Lan-Fang Tan; De-Sheng Ning; Yu-Xia Fu; Zheng-Hong Pan (Phytochemistry, 2026)

Elucidating 6PPD-Q-induced metabolic reprogramming and systemic injury via ultrasensitive breathomics - Jiawei Dong; Bo Yang; Qirun Li; Zhen Li; Haiyan Wu; Mo Zhang; Meng Wang; Ting Lan; Zhongbing Lu; Liwei Cui; Yinwei Luo; Yi Yi; et al. (Environmental Pollution, 2026)

Impact behavior of seawater sea-sand concrete beams enhanced with high corrosion resistant bars under marine environments: Experimental study and lifetime prediction - Kai Qian; Shi-hao Wu; Bing Liu; Ting Huang; Yang Ming; Zhi Li (Engineering Structures, 2026)

Novel D-A1-A2-π-A self-assembled monolayer in suppressing the Voc deficit of the wide-bandgap perovskite solar cells - Dong-Tai Wu; Yu Hsuan Lin; Yi-Chen Lin; Hsin Li; Yu-Chen Liang; Yu-Tong Hung; Yi-Sheng Lin; Wei-Jia Qiu; Shi-Chun Liu; Yuan Jay Chang; Chieh-Ting Lin (Chemical Engineering Journal, 2026)

A crystallinity-switch strategy for in-situ encapsulating Pd nanoclusters toward selective conversion of CO2 - Zhao-Cheng Shi; Jing Li; Xue-Feng Zhang; Ming-Ming Wu; Zhonggao Zhou; Meng-Tian Zhang; Chun-Ting He (Chemical Engineering Journal, 2026)

In situ formation of chemically integrated and mechanically interlocked interphases enables robust epoxy-copper adhesion - Ting Xin; Zeyu Zheng; Zuo Li; Yue Wu; Yang Liu; Binbin Zhou; Jibao Lu; Xiaoliang Zeng; Fan Yang; Gang Li; Rong Sun; Pengli Zhu (Chemical Engineering Journal, 2026)

CAMERA: A programmable CRISPR-gated logic system for high-fidelity assessment of Mycobacterium tuberculosis - Jiu Pu; Dan Bai; Yaoyi Zhang; Yiqi Zhang; Li Zhang; Yu He; You Wu; Na Yin; Zhe He; Shun Yao; Ting Xu; Yongchang Wu; et al. (Chemical Engineering Journal, 2026)

Microclimate controls on Collembola communities along an elevational gradient in subtropical forests - Yueying Li; Ting-Wen Chen; Meixiang Gao; Zhijing Xie; Mingxin Zheng; Xiaofei Yu; Donghui Wu; Jian Zhang (Applied Soil Ecology, 2026)

An ER-targeted electronic-switched cascade probe for synchronous dual-channel imaging of H2S and HClO during liver fibrosis - Jiaxue Yang; Yi Le; Na Wang; Beibei Wu; Yuyang Song; Ting Wang; Birong Yang; Fan Zhou; Li Liu (Analytica Chimica Acta, 2026)

Reshaping geochemical fate of gold-mining-derived arsenic in Jiehe River sediments from molecular to field scales via an innovative iron-based mineralization strategy - Weichen Luo; Ting Li; Yujun Zhou; Baoting Ding; Xin Du; Xuan Liu; Yongpeng Zhang; Zhaodi Wu; Jianru Liang; Shuqing Li; Jun Chen; Lixiang Zhou (Water Research, 2026)

Formation of post-traumatic and non-traumatic knee joint contracture: Role of macrophage polarization in joint capsule and skeletal muscle - Feng Wang; Fan Bai; Ting Zhou; He Liu; Ding-Jiang Wu; Yun Zhou; Wen Li (Tissue and Cell, 2026)

DAMPs and PAMPs driven macrophage activation in kidney injury - Jia-hui Li; Zhu-jun Wu; Wan-ting Li; Chun-yin Lv; Li Wang; Rui-zhi Tan (Tissue and Cell, 2026)

Quercetin alleviates Streptococcus agalactiae-induced mastitis in mice by inhibiting the NF-κB/NLRP3 signaling pathway and ferroptosis - Yaying Jia; Qi Sun; Ting Wu; Yueqing Xie; Hongsen Yu; Mingzhen Jiang; Xuhai Li; Zhengtao Yang; Ershun Zhou; Jingjing Wang (Research in Veterinary Science, 2026)

Corrigendum to 'Magnetic and mineralogical evidence for mid- to late Holocene monsoon variability in sediments from Yuehu Lagoon, eastern China' [Palaeogeogr. Palaeoclimatol. Palaeoecol. 698 (2026) 113910] - Menghan Li; Kuang He; Zhaoxia Jiang; Junjie Wu; Ting Hao; Wenhui Li; Xiaohui Zhao; Hanlin Hao; Yuewei Hu; Haonan Song; Fenghui Li; Sanzhong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Benzene-modified carbon nitride with enhanced π–π adsorption for efficient lignin C–C bond photocleavage - Yunyi Wang; Ru Yang; Xiang Li; Haiping Wang; Ting Wu; Guigan Fang (Journal of Environmental Chemical Engineering, 2026)

Synergistic activation in phosphogypsum multi-solid-waste cementitious systems: Ternary versus quaternary pathways - Yongquan Chen; Chen Wang; Zhonghu Wu; Ting Lu; Hanhua Yi; Cuicui Li; Shenglun Chen (Journal of Environmental Chemical Engineering, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Recent advances in the optical sensing of endocrine disrupting chemicals (EDCs) based on noble metal nanoparticles - Meng-ting Li; Jian Zhu; Guo-jun Weng; Jun-wu Zhao; Jian-jun Li (Journal of Environmental Chemical Engineering, 2026)

Synthesis and valorization of corn silk-derived carbon dots for antimicrobial fruit preservation - Yong-Ping Wen; Meng-Ting Wu; Kwang-Pyo Kim; Meng-Yi Chen; Jia-Hui Liu; Ya-Ping Li; An-Guo Wu; Xiang Li; Song-Zhi Xie; Die Gao; Jian-Ming Wu; Xiao-Gang Zhou (International Journal of Food Microbiology, 2026)

A novel perspective on the aging of raw Pu-erh tea: a comprehensive evaluation of the impact of different storage containers on flavor quality - Di Tian; Ting Wu; Linna Ma; Xiaohui Zhou; Chenyang Ma; Ning Chen; Haiyan Yi; Yapeng Liu; Yali Li; Yong-Quan Xu; Hongjie Zhou; Xiujuan Deng (Food Research International, 2026)

SNX8 interacts with THOC7 to negatively regulate IFN 1 response via the TBK1-IRF3 signaling axis in teleost fish - Miao-miao Li; Chu-xin Wu; Ji-huan Hu; Ting-ting Yu; Ze-yin Jiang; Hong-ying Zhang; Xun-hang Li; Cheng-yu Hu (Fish & Shellfish Immunology, 2026)

A bioinspired flavin-based catalytic construct enabling intracellular NAD+/NADH redox regulation for mitigating skin aging - Jiani Xiang; Qian Ling; Li Yan; Ying Xia; Peizhen Lou; Zhen-Gang Wang; Ting Li; Huiling Wu (Chemical Engineering Journal, 2026)

Interfacial electronic coupling in Bi2O3/COF heterostructures for high-performance supercapacitors - Rui Zhang; Hong-xia Gao; Yu-ting Zhao; Li Li; Yan Lv; Xue-yan Wu; Jixi Guo; Rui Xue (Chemical Engineering Journal, 2026)

Solvent-resistant, alkali-recoverable, self-healing, shape-memory and conductive dynamic polymers from multicomponent bio-based monomers for self-sensing soft actuators - Shiyu Du; Zhijian Li; Ting Gan; Zhou Bai; Yuan Li; Yonglong Chen; Cuizhu Wang; Guodong Liu; Haiwei Wu; Hongwei Zhou; Hanbin Liu (Chemical Engineering Journal, 2026)

Long-term continuous agricultural activities can significantly increase the soil carbon storage in the reclaimed wetlands of estuarine coastal islands - Hechen Sun; Ting Liu; Chenyang Wu; Dongqi Wang; Yizhe Li; Shengnan Wu; Fanyan Yang; Yufang Li; Xin Xu; Ziqi Ren; Huanguang Deng; Zhenlou Chen (CATENA, 2026)

Spatiotemporal scaling of gully erosion susceptibility: Integrating seasonal dynamics across regional and watershed contexts - Yanyan Xu; Yanru Wen; Seyed Hamidreza Sadeghi; Tong Zhou; Jing Yang; Ting-yong Li; Bingxue Zhu; Wenbin Wu (CATENA, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Dibutyl phthalate exposure induced hepatotoxicity via VDAC2 mediated mitochondria-dependent ferroptosis - Zixu Li; Jialing Zhang; Haodong Wang; Hanfei Xu; Yao Chen; Weiwei Feng; Ting Zhao; Liuqing Yang; Guanghua Mao; Xiangyang Wu (Aquatic Toxicology, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Thermal mechanisms driving Neoarchean ultrahigh-temperature metamorphism in a sagduction regime: numerical constraints from the North China Craton - Ying Li; Ting Yang; Chenying Yu; Qihang Wu; Changqing Yin; Jiahui Qian; Xiao Wang; Chuan Huang; Jian Zhang (Precambrian Research, 2026)

Multi-proxy evidence for the initiation of Yellow River integration through Sanmen Gorge at ∼1.8 Ma: Insights from borehole YJ-1 in the Yuncheng Basin, Fenwei Graben - Ting Huang; Zhenhong Li; Xiaopeng Dong; Shiyu Zhang; Yan Guan; Yong Lei; Zhonghai Wu; Zongxiu Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Magnetic and mineralogical evidence for mid- to late Holocene monsoon variability in sediments from Yuehu Lagoon, eastern China - Menghan Li; Kuang He; Zhaoxia Jiang; Junjie Wu; Ting Hao; Wenhui Li; Xiaohui Zhao; Hanlin Hao; Yuewei Hu; Haonan Song; Fenghui Li; Sanzhong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Systematic cadmium isotope fractionation between the organic and mineral fractions of soils - Jiawen Zhou; Tingting Mu; Ting Gao; Rebekah E.T. Moore; Mark Rehkämper; Yufang Sun; Zhen Zeng; Xinyang Li; Shijin Guo; Tong Zhou; Longhua Wu; Yongming Luo (Journal of Hazardous Materials, 2026)

Regenerable “Two-in-One” molecularly imprinted nanozymes colorimetric sensor array combined with deep learning enables selective removing and visual discriminate of tetracycline antibiotics - Yudan Wang; Yupeng Li; Gaoyuan Zuo; Ting Li; Yating Chen; Ting Wu; Xinrui Chen; Yiyang Ma; Meihong Li; Weimin Yang; Guiping Qin; Xinrong Guo; et al. (Journal of Hazardous Materials, 2026)

Milk vetch activates low-grade phosphate rock for phosphorus supply and cadmium mitigation in paddy fields - Jiancheng Xie; Danna Chang; Xinyan Li; Ting Liang; Xiaofen Chen; Jia Liu; Changxu Xu; Rongyan Bu; Hui Wang; Ji Wu; Songjuan Gao; Weidong Cao (Journal of Hazardous Materials, 2026)

Interfacial electron redistribution stabilizes Cu-centered redox cycling for efficient Fenton-like catalysis - Xiao-Ying Li; Ruo-Lan Xu; Ren Zhu; Ting-Yu Zhang; Wen-Rui Wang; Wu-Jun Liu; Hong Jiang (Journal of Cleaner Production, 2026)

Preparation of K2CO3-activated biochar from peanut shell and Chlorella for enhanced carbamazepine adsorption: Performance, mechanism, and reusability - Zhenzhen Li; Jiayu Wu; Ting Cheng; Liling Zhou; Yujia Yang (Journal of Environmental Management, 2026)

Submicron-scale mineral weathering and organo-mineral association in the rhizosphere of iron ore tailings - Zhen Li; Songlin Wu; Ting-Shan Chan; Cheng-Wei Kao; Jian Wang; Gordon Southam; Longbin Huang (Geochimica et Cosmochimica Acta, 2026)

Glucose glycosylation enhances the functional properties of grass carp scale gelatin-derived TIPs via gut microbiota and metabolite regulation - Zi-Zi Hu; Ting-Ting Wu; Xin Li; Chun-Yan Peng; Su-Su Ye; Xiao-Mei Sha; Zong-Cai Tu (Food Research International, 2026)

“Lotus leaf meets nacre”: a dual biomimetic approach to creating highly humidity-stable films with exceptional barrier properties for food packaging - Ningkang Deng; Jinsong Zeng; Pengfei Li; Junzhang Wu; Jianqiao Su; Zhiqiang Gong; Yuan Peng; Ting Yao; Jinpeng Li; Daxian Cao; Bin Wang; Jun Xu; et al. (Food Chemistry, 2026)

UEV1A attenuates MDA5-mediated antiviral immune response by reducing its ubiquitination and aggregation - Jiaxin Wang; Rongyao Sun; Ting Li; Houcheng Liang; Huan He; Jun Xiao; Hui Wu; Yong'an Zhang; Hao Feng (Fish & Shellfish Immunology, 2026)

Manganese doping redirects As-P competition on ferric/aluminum oxides: Mechanistic insights and adsorbent selection strategy - Xuan Sun; Furong Zhang; Kun Wu; Ting Liu; Jiangbo Li; Jiayuan Feng (Chemical Engineering Journal, 2026)

Molybdenum-functionalized thiolated chitosan repurposes aqueous V(V) as an in situ PMS activator for simultaneous organic degradation and vanadium recovery - Yating Wu; Ting Xiang; Lei Zhang; Ping Gao; Lei Li; Chensi Shen; Fang Li; Juan Zhou (Chemical Engineering Journal, 2026)

Redox-sensitive genetic circuits enhance microbial stress tolerance to complex inhibitors in lignocellulose biorefinery - Wen-Tao Wang; Qi Feng; Ting-Ting Li; Muhammad Aamer Mehmood; Hui Zhu; Ning Wang; Yi Ma; Chen-Guang Liu; Feng-Wu Bai (Chemical Engineering Journal, 2026)

Materials-centric protein corona design in polyurethanes for pro-regenerative immune modulation and soft tissue repair - Jingjing Lin; Mingtao Luo; Haonan Qi; Xue Wu; Junhong Li; Yuan Feng; Zhen Li; Feng Luo; Jiehua Li; Hong Tan; Ting Lan; Yanchao Wang (Chemical Engineering Journal, 2026)

Multifunctional oxidized arabinogalactan/N-methylacrylamide chitosan-based elastic gel designed by dual crosslinking for sensing and energy harvesting applications - Hongzhuang Zhang; Zhulan Liu; Ren'ai Li; Ting Wu; Yunfeng Cao; Guigan Fang (Carbohydrate Polymers, 2026)

Comprehensive Transcriptomics and Biochemical Analysis Provide New Insights into the Light Intensity Regulation Growth and Medicinal Quality of Dendrobium nobile - Ting Li; Haolin Liu; Yijun Fan; Hui Wang; Linlong Xu; Siyu He; Jie Ma; Junlan Wu; Chunhong Mou; Meng Zhao; Li Chen; Xuyang Liu; et al. (Journal of Plant Growth Regulation, 2026)

Multi-omics, machine learning, and molecular simulation identify CD44 as a candidate target in endocrine-disrupting chemical–associated thyroid cancer progression - Yifan Hu; Keshu Liu; Ting Chen; Zhizhen He; Shuang Li; Wu Hu; Qiuyang Fu; Xiong Chen (Molecular Diversity, 2026)

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

An Elastoplastic Strain Increment Ratio Method for Identifying the Crack Initiation and Damage Thresholds of Hard Rocks Under True Triaxial Stress - Jian-Zhi Zhang; Hai-Tao Wang; Jia-Yue Chen; Ting Zhang; Li-Yuan Wang; Xue-Zhen Wu; Jian-Cai Su (Rock Mechanics and Rock Engineering, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

In situ generation of NKG2D CAR T/NK cells via a tumor-targeted lipoplex for enhancing cancer immunotherapy - Xiaoxuan Xu; Wenzhe Yi; Xiangshi Sun; Zhiwen Zhao; Jialin Duan; Ting Wu; Xiaoting Shan; Jie Li; Dangge Wang; Yaping Li (Science Bulletin, 2026)

Anaerobic digestion of oily food waste controlled by mixing intensity under high-lipid loading: Emphasis on the effect of height-to-diameter ratio on process performance, lipid conversion and microbial community - Li-Jie Wu; Yu-Chao Duan; Zi-Wen Hao; Ting Xi; Fan Yang; Zhi-Feng Qin (Process Safety and Environmental Protection, 2026)

Weight-optimized fusion of satellite precipitation over the Qinghai-Tibet Plateau: Comparison of machine learning approaches - Li Zhou; Chun Zhou; Zhongshun Gu; Yinan Guo; Ting Chen; Xiaojun Guo; Juan Du; Jiajia Yue; Keying Liu; Lingling Wu; Jingyuan Xue (Journal of Hydrology, 2026)

Mechanistic insights into KOH-regulated biochar derived from waste Myriophyllum aquaticum biomass for 1O2-mediated degradation of 2,4,6-trichlorophenol - Guangya Zhou; Dong Zhang; Zhengzheng Lou; Miaomiao Zhao; Dihua Wu; Suling Zhang; Ying Pan; Ting Lü; Hongting Zhao; Jun Lin; Li Lu; Ming Zhang (Journal of Environmental Management, 2026)

Was the magma redox of the West Kunlun Paleo-Tethys modulated by surface environmental conditions of the Late Paleozoic Ice Age? - Zong-Yong Yang; Jing-Jing Zhu; Ruizhong Hu; Xian-Wu Bi; Li-Chuan Pan; Xing-Chun Zhang; Ju-Ting Deng; Yao-Wen Zhang; Qian Liu; Yi-Xin Li (Global and Planetary Change, 2026)

From solvent-tailored carbon dots to a practical sensor array: fingerprint discrimination and quantification of azo dyes in beverages - Zhi-Min Zhi; Zong-Mei Huang; Cong-Ting Wu; Jing Li; Yanting Song; Lu-Shuang Li (Food Chemistry, 2026)

Maternal Bifidobacterium bifidum BD-1 supplementation during late gestation modulates offspring gut microbiota succession and responses to DSS-induced acute colitis in a delivery-mode-dependent manner - Chenrui Peng; Chang Lu; Xiaoting Li; Lunpu Zhang; Yao Zeng; Xiaona Wu; Ting Wu; Fang He; Xi Shen (Food Bioscience, 2026)

Ternary ZnO@ZIF@COF core-shell-shell heterostructures: Energy-band cascade and layered signal amplification for biogenic amine detection - Junxi Cheng; Ting Li; Chang Liu; Yichen Gong; Xuanjun Wang; Miaomiao Liu; Yueguang Li; Hewei Yang; Zihan Qin; Zhengyang Cheng; Liyuan Cai; Qihua Sun; et al. (Chemical Engineering Journal, 2026)

Interfacial electronic reconstruction and near-zero hydrogen adsorption energy in Ru-modulated Ni2P/CoP nanowire arrays for on-demand chemical hydrogen evolution - Zichuan Lu; Fuying Wu; Kai Jia; Suning Li; Beibei Xiao; Ting Bian; Petr Senin; Liuting Zhang (Chemical Engineering Journal, 2026)

Gas-liquid two-phase flow pattern identification based on HHT and SVM-assisted optical carrier microwave interferometry - Songlin Li; Ting Xue; Yan Wu (Chemical Engineering Journal, 2026)

Decoding immunotherapy resistance in multiple myeloma: genetic insights and approaches to counter resistance - Huan Li; Qi Xia; Mei Yu; Ying Lv; Jialing Xiao; Xiaoxin Guo; Kai Dong; Yu Zhou; Ling Zhong; Ting Wang; Weijia Wu; Chengzi Gan; et al. (Science China Life Sciences, 2026)

MECP2T203M mutation disrupts neurogenesis in human cerebral organoids by altering chromatin dynamics and transcriptional regulation - Zhihong Song; Qian Zhu; Rui Yang; Huihui Jiang; Ying Li; Liping Chen; Ting Wang; Yan Wu; Yan Liu; Haitao Wu (Science China Life Sciences, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Plant growth stage drives the differentiation of microbial assemblage across plant niches - Li Shao; Jiajun Li; Ting Lu; Tangfu Xiao; Aiwen Wu; Xiuping Li; Jinmei Deng; Enzong Xiao (Applied Soil Ecology, 2026)

Reduced irrigation and phosphorus redistribution optimizes common vetch–mediated soil metabolic and microbial shifts suppress potato late blight - Ting Che; Shan Sun; Yilei Zhou; Chenxi Wu; Tingting Sun; Kangji Gao; Feng Hu; Huixin Li; Huijuan Zhang; Peiyi Zhao; Li Xu (Agriculture, Ecosystems & Environment, 2026)

Integrated Transcriptomic and Proteomic Analysis Reveals the Immune Response of Largemouth Bass ( Micropterus salmoides ) to Aeromonas hydrophila Infection - Fuyan Chen; Shuiping Wen; Xuehai He; Aiying Lei; Ting Huang; Yushan Wu; Honglian Tan; Youyong Liang; Xiaohua Lu; Meizhen Su; Jianbin Li; Xianhua Ouyang (Journal of Fish Diseases, 2026)
Largemouth bass ( Micropterus salmoides ) is an economically important freshwater fish species in China that is frequently affected by disease outbreaks caused by Aeromonas hydrophila . This study employed an integrated transcriptomic and proteomic approach to investigate the response of the liver in largemouth bass at 72 h post‐infection with A. hydrophila via intraperitoneal injection. We identified differentially expressed genes (DEGs; 2136 upregulated and 200 downregulated) and differentially expressed proteins (DEPs; 1683 upregulated and 1817 downregulated). Functional enrichment analysis indicated that the upregulated DEGs/DEPs were significantly involved in immune and inflammatory responses, encompassing pathways, such as TNF signalling, NF‐kappa B signalling, complement and coagulation cascades and B cell receptor signalling, while the downregulated DEGs/DEPs were primarily associated with metabolic processes, especially lipid metabolism. Integrated transcriptomic and proteomic analysis identified 420 correlated DEG/DEP pairs, among which 154 were consistently upregulated and 19 consistently downregulated. The upregulation of eight key immune‐related DEG/DEPs, including complement components (C1q, C7b, C1r‐A), MYD88 and BCL10, was verified by RT‐qPCR. Collectively, these findings provide valuable insights into the molecular basis of immune defence against A. hydrophila in largemouth bass and identify potential immune‐related biomarkers that may be useful in the development of effective prevention and control strategies.

The maternal gut microbiota influences myocardial maturation and diastolic function of offspring in mice - Shanshan Li; Yiqiong Zhang; Yang Li; Yuyang Lei; Hao Wu; Peining Liu; Wen Xi; Xiaozhen Zhuo; Pu Huang; Ting Yang; Ting Bai; Juanli Li; et al. (Science China Life Sciences, 2026)

A Rhodamine-Mannan Fluorescent Probe Targeting M2 Macrophages for Polarization Imaging - Lei Wen; Yuan Li; Ting Wu; Yue Yu; Yong Wu; Yue Wang; Deguo Wang (Journal of Fluorescence, 2026)

Tumorigenesis of well-differentiated and dedifferentiated liposarcoma: 12q amplicon architecture, oncogenic cargo, and evolutionary progression - Aobo Zhuang; Xiao Zhou; Chengfei Xu; YangJu Chen; Xueling Wang; Runchun Li; Jiajing Hu; Yinxue Cheng; Yunyan Wan; Ting Wu; Wengang Li (Cancer and Metastasis Reviews, 2026)

Impact and evaluation of different temporal compositing strategies on the accuracy of tea plantation remote sensing mapping - Deng Zhi-Yong; Wu Guo-Hui; Liu Xiao-Jing; Yang Ya-Jie; Luo Jian; Zhang Hai-Yao; Du Xin-Lu; Li Ting; Wang Shan (International Journal of Remote Sensing, 2026)

Four new phenylpropanoid glucosides from Artemisia annua L - Qi-guo Wu; Ye-qing Hu; Ting Hu; Chang-li Hu; Xue-qing Chen; Gui-xin Chou (Natural Product Research, 2026)

Biomechanical Evaluation of Zygomatic Implants: Intrasinus vs. Parasinus Surgical Approaches - Yu-Ling Wu; Aaron Yu-Jen Wu; Jui-Ting Hsu; Heng-Li Huang (Journal of Medical and Biological Engineering, 2026)

The microRNA-transcription factor-mRNA regulatory pathways involved in protein homeostasis and amino acid and lipid metabolism in the pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang (Aquaculture, 2026)

Drivers of the temporal and spatial variation in gully growth rates in Northeast China - Yanru Wen; Jingyue Li; Zhufeng Wang; Karl Auerswald; Peter Fiener; Wim Cornelis; Peng Qi; Ting-yong Li; Xinhua Peng; Liming Ye; Wenbin Wu; Ming Jiang; et al. (Science Bulletin, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Novel insights into the legacy effects of NBPT on fungal interactions and pathogenic fungal reduction in agricultural soils - Tikun Guan; Jilin Lei; Huangwei Liu; Jiarui Li; Ting Yang; Qi Wang; Han Wu; Meng Wang; Weizheng Shu; Rui Liu (Journal of Environmental Sciences, 2026)

First-trimester profiling of maternal plasma metals and vitamins in relation to gestational hypertension - Ting Wu; Tao Li; Xuan-Ping Wang; Yi-Cong Meng; Yan-Ting Wu; He-Feng Huang (Environmental Research, 2026)

A surface-engineered mycelial biofilm incorporating a self-cascading nanozyme for mycotoxin degradation in edible oils - Xue-ming Cao; Xue-ting Zhu; Yang-yang Geng; Ruo-mu Xia; Jin-min Zhang; Li-na Wu (Chemical Engineering Journal, 2026)

Mitophagy activation for jawbone radiation injury therapy via angiogenesis/osteogenesis-active nanozymes - Tianxiao Wang; Weihua Shao; Ting Zhou; Yuchao Li; Ran Qin; Ziyu Chen; Jikang Cao; Xinyu Hu; Jingxuan Cang; Chang Sun; Yuli Wang; Huijun Jiang; et al. (Science China Life Sciences, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Biochar-mediated microbial community and functional shifts regulate soil organic carbon fractions, enhancing carbon accumulation and stabilization in a subtropical plantation soil - Ting Li; Hongzhi Yang; Yuxin Tan; Mengzhu Jiang; Dechao Wu; Xiaoyong Chen; Wensheng Liu; Yelin Zeng; Kuan Peng; Yonghong Wang; Chan Chen; Guangjun Wang; et al. (Applied Soil Ecology, 2026)

Multitrophic predators shape and stabilize soil microbiome networks at a regional scale - Nan Jiang; Chunhui Liu; Huiping Ma; Yue Hu; Shi Cheng; Qijun Wu; Gen Li; Huixin Li; Ting Liu (Applied Soil Ecology, 2026)

Optimized Nitrogen Reduction Enhances Biomass Accumulation and Nitrogen Uptake of Maize–Soybean Intercropping Systems by Modulating Root Morphological Plasticity and Rhizosphere Enzymatic Activities - Ting Li; Jiao Wu; Liang He; Le Kang; Rina Wu; Yun Xiang; Jianmin Li (Journal of Soil Science and Plant Nutrition, 2026)

Pharmacological effect of rhCC16 on COPD: anti-senescence via the PI3K-AKT-mTOR pathway - Rui Gao; Shuo Wu; Chu-lin Zhang; Chao-feng Liu; Ting Li; Min Guo; Zhao-yang Chen; Hai-long Wang; Min Pang (Molecular and Cellular Biochemistry, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Dysregulated KIF2A correlates with p53 expression pattern in breast cancer - Yun Hao; Si-Qin Ma; Ting Xu; Jia-Qi Wu; Rong Ma; Ya-Wen Wang; Jian-Li Wang (Molecular and Cellular Biochemistry, 2026)

Research on the Highly Efficient and Low-Dose Improvement of Alcohol-Induced Liver Injury by High-Selenium-Content Modified Lycium barbarum Polysaccharides - Shuangzhe Mao; Xin Zhang; Lulu Wei; Han Zhang; Abo Li; Mengmeng Sun; Jiao Feng; Ting Ren; Yiting Huang; Xiaoying Liu; Zhifeng Zhang; Zhihui Zhao; et al. (Biological Trace Element Research, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mangrove species act as potential biofilters for legacy organochlorine pesticides: evidence from tissue-specific accumulation in the Zhangjiang Estuary - Nemin Luo; Ting Fang; Yingying Qian; Lei Wang; Wenhui Lin; Rongrong Song; Guoxin Li; Fengrun Wu; Xiaoqing Chen; Mingyuan Lin; Yan Lin (Marine Environmental Research, 2026)

Phosphorus-modified biochar for heavy metal passivation and soil improvement: from preparation to mechanistic understanding - Ting Ma; Yingying Wu; Haibo Li (Journal of Environmental Chemical Engineering, 2026)

Natural peptides from Vigna radiata protein hydrolysates suppress protein glycation via radical scavenging and targeted interactions - Shengru Yang; Yinchen Hou; Yanan Yuan; Wenwen Li; Ting Wu; Zhen Wang; Jian Zou; Xiaoyun Xu (Food Chemistry, 2026)

Comprehensive insights into AphA-induced physiological alterations and molecular pathways in Vibrio alginolyticus - Yanni Zhao; Zi Wang; Xuan Wu; Hua Li; Ningning Zhou; Meiru Yan; Ting Shao; Xuefeng Chen; Huan Liu (Food Bioscience, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Dibutyl phthalate exposure-induced AhR activation drives ferroptosis and HMGB1/TLR4-mediated inflammatory liver injury via NRF2–HO-1 signaling - Zixu Li; Muge Xu; Yahan Zhang; Yao Chen; Weiwei Feng; Ting Zhao; Liuqing Yang; Guanghua Mao; Xiangyang Wu (Environmental Pollution, 2026)

Integrating hybrid life cycle assessment to quantify carbon footprint in mariculture: Overcoming truncation errors and unveiling macroeconomic drivers - Ting Jiang; Kangni Wu; Yuanchao Hu; Guobao Song; Weiwei Sun; Gengyuan Liu; Zhaoyuan Yu; Ling Cao; Shaobin Li (Environmental Impact Assessment Review, 2026)

Directed synthesis, characterization and rheological properties of an ultrahigh molecular weight acetylated-gellan gum - Yue Ming; Zhuangzhuang Shi; Weilong Wang; Jue Li; Yiting Lin; Wei Sha; Guoqiang Li; Mengmeng Wu; Ting Ma (Carbohydrate Polymers, 2026)

Coupled influence of Western Pacific moisture anomalies and mid-tropospheric humidity on October precipitation in Yunnan Province Southwest China - Wen-Jun Sun; Zhen-Peng Tao; Zi-Yang Zhang; Tian-Qing Lan; Taohui Li; Peng Zi; Jian Zhang; Yao Wu; Ming-Qiang Liang; Chao-Jun Chen; Yuan-Yuan Mu; Jun-Yun Li; et al. (Atmospheric Research, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

ICE1 plays a vital role in the development of pollen grains through regulating tapetum degradation and nutrient mobilization in Arabidopsis thaliana - Fa-Li Chang; Jer-Lun Kuo; Meng-Ting Wu; Ching-Hsing Liang; Shiang-Jiuun Chen; Chien-Chih Yang (Plant Molecular Biology, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Advances and Perspectives in Atmospheric Environment Modeling in China - Zifa Wang; Xinwei Li; Meng Gao; Baozhu Ge; Xiao Tang; Xueshun Chen; Qizhong Wu; Lin Wu; Zhe Wang; Ting Yang; Xiaole Pan; Huansheng Chen; et al. (Advances in Atmospheric Sciences, 2026)

A comprehensive functional landscape of PRV replication and pathogenesis revealed by genome-wide transposon mutagenesis - Wanwan Yan; Keyue Ruan; Lingchao Chen; Songnan Li; Ting Liu; Wu Tong; Fei Gao; Lingxue Yu; Ning Kong; Guangzhi Tong; Hao Zheng (Veterinary Microbiology, 2026)

Giardia duodenalis cysts induce bovine neutrophil extracellular trap formation - Yifei Li; Hongsen Yu; Tianyu Li; Xuhai Li; Ting Wu; Xiangyu Yan; Qixi Li; Chenhan Bu; Qi Sun; Jingjing Wang; Ershun Zhou; Zhengtao Yang (Veterinary Parasitology, 2026)

Menopause status and modifiable risk factors for early menopause in China: a nationwide cross-sectional study on geographical disparities - Ting Guo; Xinyi Wu; Peihao Liu; Zifeng Cao; Keyan Xu; Li Yang; Guangmei Huang; Qianqian Ma; Xiaomin Yang; Xin Gao; Yehuan Yang; Yilin Yang; et al. (Science Bulletin, 2026)

First macrofossil record of Selaginellites from the Jurassic of northwestern China - Zhi-Hui Song; Zhuo-Er Wang; Huai Wang; Xu Li; Jing-Yu Wu; Su-Ting Ding (Review of Palaeobotany and Palynology, 2026)

Hydroclimatic heterogeneity in Southwest China revealed from trace elements of a Medieval-to-modern stalagmite - Chen-Yi Wang; Jun-Yun Li; Chao-Jun Chen; Jian Zhang; Yao Wu; Ting-Yong Li (Quaternary International, 2026)

Biocontrol of tobacco bacterial wilt by Bacillus velezensis Y19: insights into chemotaxis, competition and antagonism - Yajie Hu; Xiaolan Yang; Huiping Wu; Qunling Li; Guangxiong Xiao; Feng Wu; Feng Li; Zihua He; Xiaoxing Lin; Ting Ding (Physiological and Molecular Plant Pathology, 2026)

Cavitation flow in a self-excited oscillation nozzle under curved surface constraints - Lianan Wang; Shidong Fan; Wei Wu; Xiuneng Li; Ting Xiong; Zuyuan Liu; Fan Chen; Zhenlong Fang (Ocean Engineering, 2026)

Hydroxyapatite nanowires enhanced biochar hybrid aerogel for superior Ni(II) adsorption - Ting Wang; Haiyan Wu; Yili Wang; Yuansong Wei; Dunqiu Wang; Haixiang Li; Yufeng Xu; Libing Zheng (Journal of Cleaner Production, 2026)

Solid waste dumping differentially impacts soil prokaryotic, fungal, and viral communities: Insights from metagenomics - Rongzhou Jin; Can Chen; Jingru Zhang; Yanying Li; Ye Wu; Feifan Wang; Zhipeng Chen; Ting Huang; Qijie Cheng; Xinlin Yu; Pu Jia (Journal of Environmental Sciences, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Perfluorooctane sulfonate (PFOS) induces Caspase-8-mediated pyroptosis via GSDMD and GSDME to drive retinal disease: Evidence from epidemiological and experimental studies - Lu-Yin Wu; Li-Xia Liang; Jia-Xin Zhou; Yun-Ting Zhang; Zeeshan Mohammed; Muhammad Amjad; Yang Zhou; Zhi Wang; Guang-Hui Dong; Wen-Wen Bao (Environmental Pollution, 2026)

Efficient fabrication of PLA/PBAT/ZnO films with inverted-pyramid Micro/nanostructures for robust anti-wet pack and antimicrobial protection - Yu Du; Rong Zhou; Kai Mu; Congyuan Zhang; Changjun Guo; Jiabao Lu; Zihao Li; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2026)

Review of materials for solid oxide electrolysis cells in high-temperature ammonia synthesis - Qingshan Li; Yangfan Sun; Wei Wu; Ting Pan; Yuanna Sun; Siew Hwa Chan (Chemical Engineering Journal, 2026)

Elucidating the synergistic SO2 tolerance mechanism in Cu-doped BiFeO3 electrocatalysts for sustainable nitrate reduction - Yuxiang Li; Yaao Li; Qian Yang; Ting An; Xiao Cui; Liuyun Lai; Yaoxin Wu; Chenxia Yang; Dalei Chang; Aiqun Kong; Denghao Wang; Jiajun Wang; et al. (Chemical Engineering Journal, 2026)

Fabrication of egg white peptides/konjac glucomannan co-assembly stabilized high internal phase Pickering emulsions: Application for co-delivery of vitamin D3 and riboflavin - Shanglin Li; Leiyi Zhang; Yulun Wu; Jiale Guo; Chengbo Yang; Kun Chen; Yajuan Li; Longjiang Tian; Jingbo Liu; Ting Zhang; Zhiyang Du (Carbohydrate Polymers, 2026)

Genetic basis of pedicellate spikelet masculinization in maize revealed by an advanced maize–teosinte population - Ruifan Bao; Xueying Wang; Junle Wu; Ting Liang; Xiya Hu; Pengxu Meng; Hang Mi; Peng Li; Sijia Yang; Zhiqin Liu; Siyu Lei; Jinyu Yang; et al. (Planta, 2026)

Extracellular vesicle-derived CDCP1 promotes chemoresistance and macrophage polarization in breast cancer - Yibing Liu; Li Ma; Ting Zhu; Di Wu; Yonglei Liu (Human Cell, 2026)

Quantifying contributions of climate and rice phenological changes to SOC dynamics based on the integration of biogeochemical model and machine learning algorithm - Ting Wu; Zhiqiang Li; Xiuli Qian; Xuecai Bi; Jingyi Chen; Sirui Wang; Shihe Xing; Liming Zhang (Computers and Electronics in Agriculture, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Comparative assessment of reproductive and intergenerational toxicity of perfluorooctanoic acid and hexafluoropropylene oxide trimer acid in zebrafish (Danio rerio) - Shenggan Wu; Xuehua An; Ting Xu; Dou Wang; Zhenlan Xu; Yuanxiang Jin; Xinquan Wang; Yun Li; Yanhua Wang (Journal of Hazardous Materials, 2026)

Substrate-dependent function transition of lignin peroxidase during acclimated composting: From lignin degradation to humic acid synthesis - Ting Feng; Xiaolei Ding; Ting Li; Chunhao Zhang; Junqiu Wu (Journal of Environmental Chemical Engineering, 2026)

Crystal phase-dependent ZrO2 for fluoride adsorption in hydrochloric acid - Qian Wu; Xin Huang; Shiyu Sun; Yan Li; Fengzhen Liu; Xin Chen; Na Wang; Ting Wang; Zijian Zhou; Bin Lu; Hongxun Hao (Journal of Environmental Chemical Engineering, 2026)

Efficient nitrate and ammonium removal by psychrotolerant strain Pseudomonas yamanorum EH-G3 under acidic conditions - Qifeng Wu; Ruoyu Li; Ting Zou; Mei Li; Jianguo Zou; Tengxia He (Journal of Environmental Chemical Engineering, 2026)

Acclimation-enhanced ofloxacin biodegradation by Tetradesmus obliquus: Unveiling physiological and transcriptomic adaptation mechanisms - Wei Gao; Junzhuang Wu; Ting Guan; Imran Ali; Guoxin Tang; Yujiao Yue; Wei Li (Journal of Environmental Management, 2026)

Spatiotemporal distribution of legacy and alternative per- and Polyfluoroalkyl substances (PFASs) in major rivers of the Pearl river delta - Ting Wu; Yonglong Lu; Pei Wang; Cong Wang; Haojie Lei; Yanjun Liu; Kongming Li; Zhenjun Zhang (Journal of Environmental Sciences, 2026)

Sibakazin: a novel black fly derived non-classical kazal protease inhibitor, targeting antiplatelet (P2Y12/GPVI) pathways without perturbing coagulation - Zhuorui Li; Yanmei He; Yan Shen; Miao He; Ting Lin; Jiayi Yang; Lixian Mu; Jing Wu; Hailong Yang (Insect Biochemistry and Molecular Biology, 2026)

Relationship between sulfur compounds and Baijiu flavor: composition, flavor characteristics, and modulation - Ting Li; Ying Lang; Yangyang Huo; Xuanjing Ren; Tianyi Cao; Yao Long; Botian Wu; Mingquan Huang; Baoguo Sun; Jihong Wu; Hehe Li (Food Chemistry, 2026)

A study on the association between early-pregnancy hair metal levels and gestational diabetes mellitus - Feng Tang; Jun Guo; Li-An-Sheng Wu; Xiao-Yuan Fan; Han-Wen Zhang; Noora Kartiosuo; Boris Novakovic; Ting-Li Han; Hua Zhang; Yin-Yin Xia; Philip Baker; Richard Saffery (Environmental Pollution, 2026)

Engineering compartmentalized utilization of glycerol with glucose for high-level chondroitin production in Corynebacterium glutamicum - Zhuangzhuang Shi; Yue Ming; Jue Li; Yiting Lin; Weilong Wang; Wei Sha; Guoqiang Li; Mengmeng Wu; Ting Ma (Carbohydrate Polymers, 2026)

Contrasting effects of tree leaf litter on species interactions during early- and late-stage decomposition of litter mixtures in a boreal peatland: a 6-year experiment - Rui Li; Ting Wu; Sihan Guo; Zhenyang Liu; Rong Mao (Plant and Soil, 2026)

The transcription factor BRN2 confers cadmium tolerance by regulating SAM1 expression in Arabidopsis - Su Li; Jing Huang; Jia Qi Li; Chuan Jin Shan; Ren Fang Shen; Da Li Zeng; Jin Chen; Xian Jiao Guan; Xiao Fang Zhu; Ting Wu Liu; Yong Gang Xu (Plant Science, 2026)

Quorum sensing-driven biofilm cathode of Shewanella oneidensis for enhanced uranium adsorption: Elucidating the role of exogenous AHLs and validation in actual uranium-contaminated groundwater - Jing Sun; Hong Shu; Xiaoyan Wu; Tingting Liu; Guangyue Li; Zhao Cui; Ting Li; Xiaowei Zhou; Zhongran Dai; Qian Li (Journal of Hazardous Materials, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Potent dual-function of marine peptide N6NH2 and its D-enantiomer to combat MDR A. veronii infection in tilapia (GIFT, Oreochromis niloticus) - Ting Li; Na Yang; Da Teng; Ruoyu Mao; Ya Hao; Huihui Han; Yankang Wu; Xiumin Wang; Jianhua Wang (Fish & Shellfish Immunology, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Dual waste-derived 3D solar evaporator with vertically aligned channels for efficient solar-driven desalination, wastewater purification, and thermoelectricity generation - Xin Wang; Yicheng Wang; Xiao Sun; Xiaowen Cui; Tinghui Wu; Ting Wang; Yiran Luo; Yongqi Yang; Mengzhu Liu; Yongpeng Wang; Zhe Chen; Jing Li (Desalination, 2026)

Silica-reinforced tannin-carbon black/sodium alginate hydrogel on melamine foam for mechanically robust and salt-resistant solar interfacial evaporation - Yuqian Zhang; Chengping Li; Ziyi Wang; Zijian Li; Liang Wang; Kuzmin Anton; Xingqiao Wu; Ting Bian (Desalination, 2026)

Phosphorus-potassium fertilizer exposure induces oxidative stress and riboflavin metabolism disruption in juvenile turbot (Scophthalmus maximus) - Ying Tao; Xin Li; Lele Wu; Ting Qi; Xinlu Yue; Xian Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Imiquimod-induced colitis: A novel ROS/ERK-driven model of intestinal inflammation and barrier dysfunction - Kuang-Ting Liu; Shu-Hao Chang; Kuan-Chen Wu; Zheng-Yi Li; Mao-Chia Chang; Yen-Chu Huang; Mu-Chi Chung; Shih-Chung Wang; Yi-Ju Chen; Jeng-Jer Shieh (Chemico-Biological Interactions, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Understanding the role of C5a/C5aR1-mediated complement activation pathway in tumor progression and therapy resistance - Lemei Zheng; Jianxia Wei; Mengna Li; Changning Xue; Qingqing Wei; Zubing Wu; Xiaolong Li; Ting Zeng; Huizhen Xin; Wei Xiong; Hongyu Deng; Ming Zhou (Science China Life Sciences, 2026)

Three Decades in Review: The Evolution of Rockfall Impact Testing Apparatuses - Zhong-Min Ji; Huan-Huan Zhang; Haris Saroglou; Pavlos Asteriou; Ting-Hui Wang; Dong-Po Wang; Fa-Quan Wu; Zhen-Hua Li (Rock Mechanics and Rock Engineering, 2026)

Early predicting brain metastases of EGFR positive lung adenocarcinoma patients by CT radiomics - Xinliu He; Chao Guan; Ting Chen; Houde Wu; Liuchao Su; Mingfang Zhao; Li Guo (Physical and Engineering Sciences in Medicine, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Sedimentological and diagenetic effects on hydraulic flow units of ramp carbonates: Khasib Formation, Mesopotamian Basin, Iraq - Ting Wu; Zhongrong Mi; Ahsan Mohammed Saeed; Jianhua Qu; Hui Liu; Ahmed Saeb Rasheed; Xinguo Duan; Haiyue Li; Quanzhen Li (Carbonates and Evaporites, 2026)

Biodegradable microplastics as mediators of iron‑carbon decoupling: Enhanced soil carbon mineralization in wetland - Xinyi Huang; Yuan Pan; Xiansheng Zhang; Teng Li; Ting Wu; Shanqing Tang; Yunze Wang; Junhao Chen; Juanjuan Huang; Zhifeng Liu (Applied Soil Ecology, 2026)

Soil phosphorus dynamics during cropland reforestation - Wenchao Wu; Rongxiao Che; Song Zhang; Yunlong He; Benjamin L. Turner; Dong Liu; Fang Wang; Ting Li; Anquan Xia; Zejin Zhang; Tong Li; Guangbing Xu; et al. (Agriculture, Ecosystems & Environment, 2026)

Integrated Multi-Endpoint Analysis of Soluble Copper(II) Chloride–Induced Oxidative Stress, Mitochondrial Dysfunction, and Genotoxicity in RAW264.7 Macrophages - Ping-Kun Tsai; Sheng-Wen Wu; Yen-Ju Lee; Yu-Ting Chang; Shiuan-Shinn Lee; Yung-Chuan Ho; Li-Chiu Yang; Yu-Hsiang Kuan (Biological Trace Element Research, 2026)

Transgenerational Effects of Elevated Temperature on Life History and Lambda-Cyhalothrin Sensitivity in Cydia Pomonella - Kang-Wu Zheng; Zi-Han Wei; Zi-Nan Xia; Bo-Kun Wang; Ping Gao; Yu-Ting Li; Xue-Qing Yang (Neotropical Entomology, 2026)

Ochratoxin A induces intestinal barrier impairment and concurrent hepatorenal toxicity in broiler chicks via modulation of autophagy, ferroptosis, and the intestinal microbiota - Qixi Li; Ting Wu; Yueqing Xie; Mingzhen Jiang; Xuhai Li; Hongsen Yu; Ershun Zhou; Zhengtao Yang; Jingjing Wang (Research in Veterinary Science, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

Drospirenone inhibits neurobehavioral activity in zebrafish larvae by modulating NMDA receptors - Manci Chen; Ting Yu; Xiaoxuan Wang; Wei Wu; Qing Wan; Juan Liu; Ke Li; Jiang Yue; Jinlei Xi; Zheqiong Yang (Journal of Hazardous Materials, 2026)

Microplastics affect PAH sorption and migration in soil: Insights from experiments and backpropagation neural network modeling - Linghui Wang; Li Lu; Ting Li; Qingtao Wu; Yong Lai; Yi Shen; Jiali Shentu; Shengqi Qi; Min Zhu; Yuyang Long; Dongsheng Shen; Chao Chen (Journal of Environmental Chemical Engineering, 2026)

Socioeconomic inequality in flood exposure and compound urban flood risk: A multistage assessment across 30,000 towns in China - Zhen He; Jinghao Hei; Zhiqiang Wu; Otthein Herzog; Lan Li; Ting Yang; Xiang Li (Journal of Environmental Management, 2026)

Infrared spectroscopy combined with deep learning to describe the textural properties of cooked rice from raw materials: revealing spectral variations and internal correlations during processing - Rui Tang; Ting Yu; Zi Li; Junru Wu; Xiaoming Zheng; Leiqing Pan; Yang Chen; Kun Duan; Hui Dong; Weijie Lan (Food Control, 2026)

Performance and mechanism of engineered oxygen-vacancy CuCo-spinel nanorods for activating peroxymonosulfate toward contaminant remediation - Yuan Pan; Xiansheng Zhang; Xinyi Huang; Teng Li; Yunze Wang; Ruilin Cao; Jin Zeng; Ting Wu; Shaobo Liu; Zhifeng Liu (Chemical Engineering Journal, 2026)

Bio-inspired hyaluronic acid enhanced dual-network hydrogel electrolyte unlocks dendrite-free Zn deposition and exceptional cycling stability in flexible zinc ion batteries - Runhai Wu; Ran Wang; Shaopei Yang; Baiting Li; Shimeng Guo; Hongxiao Wang; Ting Wan; Baoyan Wang; Kefeng Xie; Pengcheng Du (Chemical Engineering Journal, 2026)

Structural characteristics and bioactivities of an exopolysaccharide from mycelial fermentation of a medicinal fungus Cs-HK1 - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2026)

Icariside II sensitizes osteosarcoma to doxorubicin through the lincROR/Wnt/β-catenin signaling regulatory axis - Shu-ting Zhou; Zhi-peng Li; Yong-xin Mai; Yu-Yan Wang; Feng-xiang Pang; Jin-fang Zhang; Xian-lin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Coupled polyphosphate storage and DOP mobilization along estuarine gradients in the Pearl River Estuary - Xian-Yang Zhang; Feng-Xian Han; Jian-Ting Li; Jia-Xue Wu; Song-Hui Lu; Lin-Jian Ou (Marine Pollution Bulletin, 2026)

Wenzhouxiangella psychrophila sp. nov., Wenzhouxiangella indolica sp. nov., and Halotectona sediminis gen. nov., sp.nov., three novel taxa with ability of IAA production from saline lake sediment - Qing-Yu Xu; Tayyiba Habib; Lei Gao; Dildar Wu; Xin-Yao Li; Thi-Nhan Khieu; Yue-Heng Chen; Yao Zhang; Yong-Hong Liu; Ting-Ting She; Bao-Zhu Fang; Wen-Jun Li (Systematic and Applied Microbiology, 2026)

Mechanistic insights into gas capture and diffusion during the CO2 separation of mixed matrix membranes using ZIF materials as nanofillers - Han-chong Liu; Hong-li Chen; Li-guang Wu; Ting Wang; Hua-li Chen; Cheng Hu (Process Safety and Environmental Protection, 2026)

Dynamic changes in epidermal wax composition and quality of three goji berry varieties during postharvest storage - Ben Niu; Zihao Zong; Yifan Ding; Huizhi Chen; Weijie Wu; Maratab Ali; Mohamed A. Farag; Xiangjun Fang; Ting Huang; Chaoyi Shen; Li-shu Wang; Ruiling Liu; et al. (Postharvest Biology and Technology, 2026)

Toxicity evaluation of fosthiazate to Bombyx mori Linnaeus (Lepidoptera: Bombycidae): A new perspective from the chirality - Yuepeng Qiu; Jiyan Hu; Yao Feng; Yan Ma; Chang Li; Yazhu Liu; Yonghong Lai; Changcai Wu; Ruilong Sun; Ting Tang; Lianshan Li; Fengsong Liu (Pesticide Biochemistry and Physiology, 2026)

Expanded species diversity of fungi in metalliferous mine tailings ponds and their potential ecological roles revealed by PacBio sequencing - Yanying Li; Ting Huang; Weihang Zeng; Rongzhou Jin; Ye Wu; Zhipeng Chen; Qijie Cheng; Xinlin Yu; Xiao-lin Luo; Guan-xiong Wu; Jia-wei Li; Pu Jia; et al. (Journal of Hazardous Materials, 2026)

Water loss and return flows matter for water stress mitigation in China - Dan Wang; Reetik Kumar Sahu; Taher Kahil; Ting Tang; Wei Zhang; Weili Ye; Guangxue Wu; Zhuo Chen; Huimei Li; Junxia Wang; Haoyuan Feng; Yuli Shan; et al. (Journal of Cleaner Production, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Plant colonization facilitates organic matter humification, iron mineral transformation, and microbial community restructuring in coal gangue remediation - Junsheng Guo; Zhen Li; Yirui Shi; Tingrui Zhang; Yuanfang Huang; Jianying Shang; Ting-shan Chan; Songlin Wu; Yunjia Liu (Environmental Research, 2026)

Glaucocalyxin A Promotes Spinal Cord Repair By Nrf2/HO-1 Pathway Activation to Suppress AIM2 Inflammasome Formation - Ze Li; Jiajing Ye; Zhiyu Fang; Xinyu Wu; Fang Tang; Ting Jiang; Yuhang Gong; Yuxuan Bao; Binbin Zheng; Huaxing Hong; Zhenghua Hong (Molecular Neurobiology, 2026)

Mosloflavone induces pancreatic α cells transdifferentiation into β cells through PDX1 - Lanxin Deng; Ting Deng; Yu Deng; Tongyu Zhang; Jiacheng Guo; Xin Wang; Xinyun Wu; Mingyu Li (Journal of Natural Medicines, 2026)

Enrichment of anthropogenic organic matter and acetoclastic pathway dominates ebullition CH4 production in urban river - Shengnan Wu; Dongqi Wang; Hongmei Ma; Yufang Li; Guanghui Zhao; Hechen Sun; Fanyan Yang; Xin Xu; Ting Liu; Ziqi Ren; Shu Chen; Chenyang Wu; et al. (Water Research, 2025)

S-nitrosylation of thaumatin-like protein in Ziziphus jujuba and its roles in chilling stress and pathogen stress responses - Yizhou Gao; Ting Guo; Lingling Liu; Li Li; Zhengbao Wu; Yunhong Jiang; Zhaojun Ban; Zhen Yang (Postharvest Biology and Technology, 2025)

Advancements in urban water management and ecological restoration technologies: Frameworks, challenges, and emerging trends - Sitong Zou; Yucong Zheng; Mawuli Dzakpasu; Qian Li; Ting Cao; Liping Zhao; Tianfu Wu; Dongfu Zhang; Yunze Chai; Rong Chen (Journal of Water Process Engineering, 2025)

Metallurgical organic pollutants assisted source apportionment of mobile heavy metals on artisanal non-ferrous metal processing contamination - Li-Rong Liu; Junyao Yan; Lei Xiang; Ting Liu; Ye Xiao; Wen-Shen Liu; Wen-Jun Wu; Ping Li; Miaoyue Zhang; Yuan-Qing Chao; Ye-Tao Tang; Rong-Liang Qiu (Journal of Hazardous Materials, 2025)

Microbial mechanisms of biochar reducing methane emission in a rice-crayfish integrated system - Linjie Ma; Chengxin Zhang; Baoli Qin; Ting Yang; Rong Xu; Lingyu Zhu; Guangming Han; Leiming Wu; Siyu Li; Jianhua Bi; Shouhong Wang; Jiahong Zhang; et al. (Journal of Environmental Management, 2025)

Machine learning unveils the impact of anthropogenic emission changes on urban PM2.5 and O3: A case study in Wuhu - Hongling Xu; Zhirong Ruan; Hua Fang; Qina Jia; Feng Li; Jun Li; Ming Ye; Ting Wu (Journal of Environmental Sciences, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

E-sensing coupled metabolomics unravels flavor-texture synergy in citric acid-thermally processed pink Auricularia cornea - Lei Ye; Ting Wu; Li Chen; Zhengzhu Huang; Xuezhen Yang; Yu Huang; Qing Tian; Bo Zhang; Yuntao Liu; Xiaolin Li (Food Chemistry, 2025)

Bioactive pterostilbene encapsulated in zein via an in-situ co-precipitation strategy for efficient antimicrobial and fruit preservative - Chunli Fang; Zhinan Fu; Nan Wei; Jia Wei; Shuying Li; Ting Feng; Zicheng Tan; Junyou Wang; Bin Wu; Xuhong Guo (Food Hydrocolloids, 2025)

Efficient lithium extraction from salt lakes brine via regulating the electric double-layer interface of high-loading film electrodes with CMC Li - Yawen Gao; Luxiang Ma; Xin Zeng; Zhixiang Li; Ting Li; Chunxi Hai; Tiandong Chen; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Xiaowang Wu; et al. (Desalination, 2025)

The catalyst derived from MoS2 with Fe/Cu dual-active-sites for peroxymonosulfate activation in antibiotic degradation: The role of Fe and Cu co-doping strategy - Wangbo Wang; Rui Yang; Tao Li; Ting Wu; Qiyu Shi; Yizhou Feng; Zhihua Li; Ying Gao; Weihuang Zhu (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

Distribution characteristics and pollution evaluation of heavy metals in surface sediments in China’s largest freshwater lake - Xiaolong Zhang; Xiaofeng Li; Weiqiang Dai; Weihao Zhang; Xiangwen Zhang; Daishe Wu; Shan Huang; Ting Huang (Stochastic Environmental Research and Risk Assessment, 2025)

SOX11-mediated CBLN2 Upregulation Contributes to Neuropathic Pain through NF-κB-Driven Neuroinflammation in Dorsal Root Ganglia of Mice - Ling-Jie Ma; Tian Wang; Ting Xie; Lin-Peng Zhu; Zuo-Hao Yao; Meng-Na Li; Bao-Tong Yuan; Xiao-Bo Wu; Yong-Jing Gao; Yi-Bin Qin (Neuroscience Bulletin, 2025)
Neuropathic pain, a debilitating condition caused by dysfunction of the somatosensory nervous system, remains difficult to treat due to limited understanding of its molecular mechanisms. Bioinformatics analysis identified cerebellin 2 (CBLN2) as highly enriched in human and murine proprioceptive and nociceptive neurons. We found that CBLN2 expression is persistently upregulated in dorsal root ganglia (DRG) following spinal nerve ligation (SNL) in mice. In addition, transcription factor SOX11 binds to 12 cis -regulatory elements within the Cbln2 promoter to enhance its transcription. SNL also induced SOX11 upregulation, with SOX11 and CBLN2 co-localized in nociceptive neurons. The siRNA-mediated knockdown of Sox11 or Cbln2 attenuated SNL-induced mechanical allodynia and thermal hyperalgesia. High-throughput sequencing of DRG following intrathecal injection of CBLN2 revealed widespread gene expression changes, including upregulation of numerous NF-κB downstream targets. Consistently, CBLN2 activated NF-κB signaling, and inhibition with pyrrolidine dithiocarbamate reduced CBLN2-induced pain hypersensitivity, proinflammatory cytokines and chemokines production, and neuronal hyperexcitability. Together, these findings identified the SOX11/CBLN2/NF-κB axis as a critical mediator of neuropathic pain and a promising target for therapeutic intervention.

Correction: LncRNA PCAT6 promotes proliferation, migration, invasion, and epithelial-mesenchymal transition of lung adenocarcinoma cell by targeting miR-545-3p - Chuyi Yang; Hongyu Huang; Yongpeng Li; Ting Zhuo; Lu Zhu; Chenyang Luo; Yanbin Wu; Shouming Qin (Molecular Biology Reports, 2025)

Aquaporins: a novel perspective in the treatment of lung diseases - Mengyuan Wu; Zhiming Miao; Fuxian Liu; Sichao Dai; Yangyang Li; Ting Zhou; Qihong Zhuo; Huanhuan Zhang; Zhangbo Song; Haiyi Nie; Wenxing Yong; Liying Zhang; et al. (Inflammation Research, 2025)

Retraction Note: Carnosic acid nanocluster-based framework combined with PD-1 inhibitors impeded tumorigenesis and enhanced immunotherapy in hepatocellular carcinoma - Wenhua Wu; Yaping Li; Xiaokang Wu; Junrong Liang; Weiming You; Xinyuan He; Qinhui Feng; Ting Li; Xiaoli Jia (Functional & Integrative Genomics, 2025)

Gene expression of long non-coding RNAs and messenger RNAs in Varroa destructor mites exposed to essential oil of camphor leaves - Siyi Shen; Meng Li; Tongyu Dong; Kai Xu; Lili Wu; Kang Wang; Defang Niu; Qingsheng Niu; Ting Ji; Zhi Wang; Zheguang Lin (Experimental and Applied Acarology, 2025)

Logging intensity and biome type mediate the effects of forest logging on soil greenhouse gas emissions - Chenjun Du; Xing Wu; Hao Shi; Bojie Fu; Ting Li; Yihe Lü; Lingfan Wan; Shuang Zhang; Binbin Huang; Yibin Shi (Agriculture, Ecosystems & Environment, 2025)

AKR1B1 is Required for Maintaining Acute Leukemia Cell Survival by Epigenetic Silencing of Tumor Suppressor Genes - Jingyu Chen; Lu Xu; Wangshi Li; Meiling Sun; Yao Chen; Ting Qiu; Yue Wu; Xingzhi Lv; Fukai Liu; Huitao Fan (Biochemical Genetics, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Neuroprotective Effects of Glucosamine in Huntington’s Disease Through NLRP3 Inflammasome Inhibition - Lichieh Julie Chu; Yi-ting Hsu; Yu Aoh; Chih-Yuan Cheng; Hui-Hsuan Wang; Ming-Tse Wu; Hao-Hsuan Li; Xiu-Yuan Lai; Kuo-Feng Hua; Chiung-Mei Chen; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2025)

Social-ecological memories as references for biodiversity restoration and conservation action in coastal community - Chia-Hsuan Hsu; Yu-Wen Wu; Jiefeng Kang; Hung-Kai Chiu; Mei-Ching Li; Wei-Ting Chen (Marine Pollution Bulletin, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Plasma-activated water: A novel approach to modulating main pectin, hemicellulose and cellulose metabolism in goji berry cell walls - Kai-Ping Cong; Ting-Ting Li; Cai-E. Wu; Gong-Jian Fan; Dan-Dan Zhou; Xiao-Jing Li; An-Di Suo (Postharvest Biology and Technology, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Self-sustained Bio-Fenton system driven by Shewanella oneidensis for efficient degradation of persistent organic pollutants under oxygen-limited conditions - Yang-Yang Fan; Xuan Yao; Zhi-Yong Li; Xin-Yu Yang; Ming-Juan Zou; Zi-Yi Zhang; Kun Wu; Ting Huang; Ya-Ning Sun; Xiang Xiao (Journal of Hazardous Materials, 2025)

Co-fermentation of non-Saccharomyces yeasts and Lactiplantibacillus plantarum for modifying physicochemical properties to alleviate stickiness and caking issues of jujube powder - Zijian Gong; Kangxue Chen; Wenbin Rong; Caiyun Wu; Ting Zhang; Qiaomei Li; Hongjie Lei (Food Research International, 2025)

Characterization of vB_SaRS_FS19–1, a newly isolated broad-host-range and virulent bacteriophage infecting Staphylococcus aureus and its application in foods - Xinyan Yao; Chaoxiang Jia; Ting Qin; Dai Peng; Linlin Huang; Yi Liu; Saiyu Zhang; Yingqian Han; Yanbin Yang; Heping Li; Hua Wu; Guoyu Yang; et al. (Food Chemistry, 2025)

Bifunctional metal-organic framework Nanozymes with flexibly tunable valence states for dual-mode detection of organophosphorus pesticides - Mai Luo; Yao Peng; Jihai Cai; Tiantian Jiang; Sheng Gong; Shiyao Hua; Ting Wang; Sijia Wu; Shuangpeng Wang; Jinchao Wei; Peng Li (Food Chemistry, 2025)

Engineered Plasmonic multi-hot spots on magnetic Nanospheres for quantitative detection of pesticide residues on food surfaces via SERS tagging analysis - Ming-Jie Wan; Yu-Ting Wu; Yan-Hui Wang; Xiao-Hang Wu; En-Ming You; An Wang; Sheng-Hong Liu; Jin-Chao Chen; Yue-Jiao Zhang; Shangzhong Jin; Fan-Li Zhang (Food Chemistry, 2025)

Synergistic adsorption and photocatalytic degradation of tetracycline by a functionalized Fe3O4/CuWO4/biochar Z-scheme composite - Dechao Wu; Mengzhu Jiang; Ting Li; Kuan Peng; Yonghong Wang; Yaohui Wu; Yelin Zeng (Environmental Research, 2025)

Hydrogel-based bimodal sensor array via modular assembly with decoupled strain–temperature sensing and high sensitivity - Fei Wang; Xiaojing Wu; Wenao Liao; Ting Li; Yidan Hu; Yan Zhu; Chang Lu; Junwei Feng; Xilin Liu (Chemical Engineering Journal, 2025)

Surface soft patch-mediated supramolecular co-assembly of lysozyme/konjac glucomannan with optimized antimicrobial performance - Shanglin Li; Yulun Wu; Yajuan Li; Longjiang Tian; Ting Zhang; Jingbo Liu; Zhiyang Du (Carbohydrate Polymers, 2025)

Microbial processes suppress antimony release during stibnite weathering under suboxic condition - Ting Lu; Li Shao; Aiwen Wu; Zengping Ning; Tangfu Xiao; Enzong Xiao (Chemical Geology, 2025)

Intercropping sunflower with amaranth to remediate cadmium-contaminated agricultural land: performance and mechanism - Zhuo-hui Wu; Feifan Wang; Mai Ye; Jingru Zhang; Zhiyi Li; Yunrong Xi; Rongzhou Jin; Yanying Li; Zhipeng Chen; Ye Wu; Ting Huang; Qijie Cheng; et al. (Plant and Soil, 2025)

Differences in temporal patterns of bacterial community assembly between soybean rhizosphere and endosphere - Ting Jin; Shuanghui Wang; Yong Wu; Junyao Deng; Xuanjing Li; Yao Liu; Jianli Zhang; Wuxuan Li; Gehong Wei; Peng Shi (Applied Soil Ecology, 2025)

Effects of Lactobacillus plantarum Ep-M17 on growth performance, immune response, and intestinal flora of the Plecoglossus altivelis (Ayu) - Yang Du; Ting Wu; Wenlong Xu; Xiaoman Hu; Le Li; Jiong Chen (Animal Feed Science and Technology, 2025)

Tree species identification based on convolutional neural network and feature fusion - Jihui Wu; Ting Zhong; Guanli Li; Yubin Lan; Wanjie Xiong (Computers and Electronics in Agriculture, 2025)

TACC3 facilitates chondrocyte differentiation by attenuating abnormally activated FGFR3 signaling in achondroplasia − An in vitro study - Xiang Li; Long Bao; Xiaoyan Wang; Haiying Wu; Ting Chen; Rongrong Xie; Hui Sun; Dandan Zhang; Lili Wang; Linqi Chen (Tissue and Cell, 2025)

Dynamic integrated optimization of batching and routing in narrow-aisle order picking systems with congestion consideration - Yanghua Pan; Shanshan Li; Ting Qu; Liqiang Ding; Naiqi Wu; George Q. Huang (Swarm and Evolutionary Computation, 2025)

Metal bioaccumulation and lipid response in aquatic ecosystem: Evidence of machine learning from Chaohu Lake, China - Qi Lu; Zhi Yuan; Wei Chang; Shen-dong Xu; Lan-lan Wu; Gang Liu; Li-yan Yang; Si-ting Liu; Meng-xue Gao; Yi-fan Hu; Xu-dong Zhang; Huan Zhou; et al. (Journal of Hazardous Materials, 2025)

Highly efficient stabilization of arsenic in the contaminated sediments of Jiehe River by schwertmannite to inhibit arsenic release into overlying water - Weichen Luo; Ting Li; Yan Dong; Yujun Zhou; Zhaodi Wu; Xuan Liu; Jiahao Ni; Jingang Xu; Dejin Zhang; Mingjiang Zhang; Di Fang; Lixiang Zhou (Journal of Hazardous Materials, 2025)

Linking short-term ozone exposure to mental health in Chinese adults: Lung function as a mediator beyond respiratory impairment - Junqi Li; Hongtao Niu; Wei Li; Jiarun Mi; Sinan Wu; Teng Wang; Ke Huang; Tianjia Guan; Ting Yang; Chen Wang (Journal of Hazardous Materials, 2025)

Ambient ozone exposure and acute blood oxygen desaturation: Role of airflow limitation - Jiarun Mi; Hongtao Niu; Wei Li; Junqi Li; Xueyan Han; Sinan Wu; Teng Wang; Ke Huang; Tianjia Guan; Ting Yang; Chen Wang (Journal of Hazardous Materials, 2025)

Phosphate perils in marine aquaculture: Systematic toxicity assessment in turbot juveniles in cultivation - Lele Wu; Xin Li; Jiale Zhou; Ting Qi; Yaolin Li; Xiefa Song; Zongcheng Song; Xian Li (Journal of Environmental Sciences, 2025)

A brief review of performance optimization and mechanism investigation of Co-based catalysts for hydrogen production from NaBH4 hydrolysis - Yuhui Qian; Fuying Wu; Zhenghao Deng; Ting Bian; Hu Zhao; Petr Senin; Hong Li; Liuting Zhang (Fuel, 2025)

Black carp STAT2 enhances IRF3-mediated antiviral signaling by regulating its ubiquitination and improving its nuclear translocation - Yiru Huang; Xinyu Wang; Jinyi Li; Ting Li; Xiaoyu Liu; Ji Liu; Jun Xiao; Hui Wu; Yong'an Zhang; Hao Feng (Fish & Shellfish Immunology, 2025)

Graft−growth of Cobalt−based Prussian blue analogs on bamboo for indoor formaldehyde removal - Yi Zhu; Honghui Yan; Ruiqi Xin; Yuding Zhu; Miaomiao Zheng; Xiangxing Wu; Yiting Zhang; Ting Wang; Meiling Chen; Song Li; Jeonghun Kim; Wenkai Zhu (Environmental Research, 2025)

Spider-cavity structured Ag/PDA@NiCuO/CF evaporator with bilateral siphon-driven channels for enhanced solar desalination - Zijian Li; Long Cheng; Ziyi Wang; Mengya Chen; Liang Wang; Kuzmin Anton; Xingqiao Wu; Ting Bian (Chemical Engineering Journal, 2025)

Hydrogel-transformable sucralfate microspheres restored gut epithelial wound and reshaped microbiota in colitis via autophagy - Dingwei Li; Bingjie Tong; Shenyuan Ouyang; Yumo Chen; Jie Wang; Bingyu Ding; Wenzhi Wu; Ting Ouyang; Kaili Mao; Helin Xu (Chemical Engineering Journal, 2025)

Emission of marine microbes via sea spray aerosol generation: Enrichment, influencing factors and the potential role in marine carbon cycle - Linyao Wu; Ting Liu; Yingyi Zhang; Yuhan Shen; Yinxi Yao; Zhaokang Ruan; Yee Jun Tham; Wei Song; Shan Huang; Jun Li; Senchao Lai (Atmospheric Environment, 2025)

Unveiling the drivers of ozone pollution rebound at an urban site in the Yangtze River Delta since 2020 - Hua Fang; Hongling Xu; Ting Wu; Qina Jia; Jun Li; Zhirong Ruan; Feng Li; Yang Li; Yuanling Shi; Xinming Wang (Atmospheric Research, 2025)

SHAPAttention: A novel approach to enhance model performance and interpretability in agricultural spectral data analysis - Ting Wu; Longhui Zhu; Lei Li; Leian Liu; Weidong Bai; Li Lin; Ling Yang (Computers and Electronics in Agriculture, 2025)

ChpR-displaying bacteria for bioremediation of chlorpyrifos and TCP: A whole-cell biosorbent approach - Yan Guo; Can Wu; Shun-yu Hu; Yu-xuan Xie; Wan-yan Wu; Bo-xin Li; Yu-ting Chen; Chang-ye Hui (Water Research, 2025)

Machine learning and network toxicology reveal arsenic as a key driver of non-carcinogenic health risks from heavy metal residues in Chinese medicinal plants - Guangying Du; Yuanju Zhang; Ting Zou; Chang Liu; Yingyue Hou; Jing Li; Feifei Deng; Jiayi An; Li Feng; Bangna Wu; Lingdan Huang; Ying Zhou (Science of The Total Environment, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Upstream moisture sources and circulation patterns controls Asian monsoon hydroclimate over the past 20,000 years - Jian Zhang; Ming-Qiang Liang; Jun-Yun Li; Yao Wu; Yan-Xia Xue; Wen-Jun Sun; Xiang-Zhuo Liu; Jin-Ke Chen; Chao-Jun Chen; Ting-Yong Li (Quaternary Science Reviews, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Biodiversity and nitrogen metabolism in the plastisphere impacted by urban nitrogen loading from a coastal mega-city - Ziqiu Lin; Shimei Pang; Yunchao Wu; Ting Xu; Ying-Li Zhou; Hao Li; Chuanlun Zhang; Pei-Yuan Qian; Si Zhang (Journal of Hazardous Materials, 2025)

Impact evaluation of coastal protection forest program on carbon sequestration change in East China - Hanle Xu; Ting Zhou; Shunbin Yao; Qigang Xu; Guozhi Li; Wu Yang (Journal of Environmental Management, 2025)

Egg white peptides suppress ghrelin secretion from the stomach by activating the mTOR signaling pathway in rats - Tianliang Wu; Wei Wang; Nan Hai; Ting Cai; Yiju Li; Zhi Feng; Haixi You; Zhipeng Yu; Jingbo Liu; Xuebo Liu; Long Ding (Food Research International, 2025)

Evolving trends in nanozyme-based SERS systems for food contaminant monitoring: A review - Tianle Wu; Yifei Mao; Ting Wang; Lingxuan Ma; Jiliang Cao; Beibei Xie; Jinchao Wei; Peng Li (Food Chemistry, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Quantitative assessment of heat tolerance in new rice varieties through field survey during natural extreme heat events - Ting Sun; Tianhui Miao; Jianan Hu; Haoyang Zhou; Minglu Li; Jiayi Zhang; Yuanyuan Pan; Ran Bi; Shenghao Ye; Menglei Wei; Zeyu Wu; Guoqiang Li; et al. (European Journal of Agronomy, 2025)

Dinotefuran exposure induces immunotoxicity in zebrafish embryos - Yunshuo Cheng; Yacan Gong; Dan Li; Weiwei Feng; Yao Chen; Ting Zhao; Liuqing Yang; Guanghua Mao; Xiangyang Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Synergistic degradation mechanism of roxithromycin by the combination of TiO2/graphene oxide/polypropylene fiber photocatalytic network and microalgae - Wei Gao; Xiangjie Pan; Junzhuang Wu; Ting Guan; Feng Cai; Jiangang Han; Yanwen Zhou; Jian Qiu; Wei Li (Chemical Engineering Journal, 2025)

Varied solvent-solvent interactions in hybrid-based electrolytes boost sodium ion transport kinetics at low temperature - Xianyan Qiao; Ruoyang Wang; Jiaqi Li; Ting Chen; Zhuangzhi Li; Fuqiren Guo; Ruixiang Wang; Yanxiao Chen; Zhenguo Wu; Xiaodong Guo (Chemical Engineering Journal, 2025)

Glycosylated protein-related microenvironmental features in breast cancer are associated with patient prognosis - Xiaoxiao Zhong; Jiaxuan Han; Huan Li; Xiangyu Shen; Bowen Yu; Ting Chen; Haobing Li; Jun Li; Jin Pang; Liyuan Qian; Wei Wu; Xiaoliang Tong; et al. (Mammalian Genome, 2025)

Reactive oxygen species and reactive nitrogen species are double-edged swords in Salmonella infection - Yue Song; Ting Ni; Yifei Zhao; Zichun Sang; Qiwen Wang; Xingyu Xia; Chang Liu; Wenlu Zhang; Shasha Li; Bo Deng; Pengfei Wu; Junfeng Tan; et al. (Archives of Microbiology, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

Engineering Patatin for enhanced lipase activity and long-chain fatty acid specificity via rational design - Ting Nie; Xue Bai; Zikang Liao; Runsha Chen; Qianyu Le; Yong Zhang; Xiaodan Liu; Xiaoying Bian; Shuhong Wu; Jinhong Wu; Xianghong Li (Food Chemistry, 2025)

Continuous reduction in socio-ecological system vulnerability on the Qinghai–Tibet Plateau from 2000 to 2050 under an intermediate protection scenario - Zhengyuan Zhao; Bojie Fu; Yihe Lü; Ting Li; Yuelu Wang; Haoyue Wang; Binbin Huang; Xing Wu (Environmental Impact Assessment Review, 2025)

Prim-O-glucosylcimifugin-loaded nanodrug hydrogel alleviates periodontitis and colitis via modulating macrophage polarization and microbiota balance - Chengye Ding; Xinjia Cai; He Zhang; Yixin Ma; Liyuan Chen; Xiaolan Wu; Min Yu; Chang Li; Hangbo Liu; Shiying Zhang; Xinmeng Shi; Ting Zhang; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Preparation and characterization of microcapsules using an acid-tolerant sanxan gum combined with sodium alginate/chitosan and their application in Lactobacillus plantarum delivery - Yue Ming; Zhuangzhuang Shi; Yufei Zhao; Jue Li; Wei Sha; Weilong Wang; Guoqiang Li; Mengmeng Wu; Ting Ma (Carbohydrate Polymers, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Mapping QTLs for adult-plant resistance to yellow rust in a hard winter wheat population Heyne × Lakin - Chunlian Li; Xiao-Ting Xu; Yibo Zhang; Shengjie Liu; Jianhui Wu; Dejun Han; Robert Bowden; John Fellers; Guihua Bai (Theoretical and Applied Genetics, 2025)

High-quality reference genome and population analysis of allotetraploid Elymus sibiricus provide insight into genome origin and environmental adaptations to the Qinghai-Tibetan Plateau - Xinrui Li; Changbing Zhang; Lili Wang; Gai Huang; Daxu Li; Changmian Ji; Zujun Yang; Minghong You; Lijun Yan; Lili Chen; Wenlong Gou; Xiong Lei; et al. (Science China Life Sciences, 2025)

Evolution of sexual dimorphism in nonhuman primates - Yuan-Ting Guo; Yijun Yang; Bolun Zhang; Hao Wu; Lei Wang; Baoguo Li; Christopher Opie; Xiao-Guang Qi (Science China Life Sciences, 2025)

Impact of ectomycorrhizal symbiosis on root system architecture and nutrient absorption in Chinese chestnut and pecan seedlings - Ting Chen; Cancan Zhu; Shucheng Li; Yan Xia; Jian Huang; Wu Wang; Chunlan Lian; Yu Chen; Yuqiang Zhao; Shijie Zhang (Plant and Soil, 2025)

Genome-wide identification of C1-1i-ZFP genes and functional analysis of ZFP6a gene from Platanus × acerifolia - Yangyang Li; Huanhuan Ji; Jinghong Wu; Gehui Shi; Ting Peng; Manzhu Bao; Jiaqi Zhang (Plant Cell Reports, 2025)

TISCalling: leveraging machine learning to identify translational initiation sites in plants and viruses - Ming-Ren Yen; Ya-Ru Li; Chia-Yi Cheng; Ting-Ying Wu; Ming-Jung Liu (Plant Molecular Biology, 2025)

Six Weeks of Moderate-Intensity Treadmill Exercise Improves Intestinal Barrier and Intestinal Inflammation in Parkinson’s Disease Mice - Ting Li; Sheng-Yang Zhou; Wei Quan; Yu Zhou; Jian Wu; Li-Ping Zhao; Chen-Meng Qiao; Wei-Jiang Zhao; Chun Cui; Yan-Qin Shen (Molecular Neurobiology, 2025)

Holocene seismically induced soft-sediment deformation structures in the Qingshuihe Basin, northeastern Tibetan Plateau - Ting Huang; Zhenhong Li; Xiaopeng Dong; Zhonghai Wu; Linlin Kou; Fang Wu (Sedimentary Geology, 2025)

Risk prioritization and experimental validation of per- and polyfluoroalkyl substances (PFAS) in Chaohu Lake: Based on nontarget and target analyses - Wei Chang; Shen-Dong Xu; Ting Liu; Lan-Lan Wu; Si-Ting Liu; Gang Liu; Jian Sun; Ye-Xin Luo; Lei Gao; Hao Li; Qi Lu; Zhi Yuan; et al. (Journal of Hazardous Materials, 2025)

Effects of pore structures of carbon paper on water management capability of a proton exchange membrane fuel cell - Yu-Ting Liu; Guo-Bao Huang; Xiao-Fang Zhang; Ting-Ting Yao; Li-Xia Cheng; Hong Zhu; Gang-Ping Wu (Fuel, 2025)

Novel insights into DBP-induced zebrafish liver inflammatory damage: Ferroptosis activating the HMGB1-TLR4-NF-κB signaling pathway - Zixu Li; Yacan Gong; Emmanuel Sunday Okeke; Dan Li; Yao Chen; Weiwei Feng; Ting Zhao; Liuqing Yang; Guanghua Mao; Xiangyang Wu (Environmental Pollution, 2025)

Collagen targeting BMSCs-derived extracellular vesicles coupled with decellularized tendon scaffold for anterior cruciate ligament reconstruction - Jie Wang; Jing Cui; Liang-Ju Ning; Yan-Jing Zhang; Fei Xing; Lei-Lei Zhao; Hui-Min Liu; Xuan Li; Min Zhu; Jing-Cong Luo; Zhou Xiang; Ting-Wu Qin (Chemical Engineering Journal, 2025)

Effects of Maternal Trace Elements Exposure in Early Pregnancy on Maternal Thyroid Hormones and Birth Outcomes - Ting Wu; Tao Li; Chen Zhang; Yan-Hui Hao; Si-Wei Zhang; Xuan-Ping Wang; Yi-Cong Meng; Yan-Ting Wu; He-Feng Huang (Biological Trace Element Research, 2025)

The substrate configuration influences pollutant removal in constructed wetlands: From the aspects of submerged status of substrate and carbon-felt distribution - Xiang-Zheng Li; Tong Wang; Ting Yang; Xue Li; Lin-Wei Wu; Lin-Lan Zhuang; Jian Zhang (Water Research, 2025)

As(III) removal from drinking water using FMCTO@Fe3O4 in the adsorption-magnetic separation-sand filtration equipment: Trade-off between As removal efficiency and adsorbent utilization rate - Xue Bai; Yuyang Xiao; Kun Wu; Ting Liu; Zhihua Li (Water Research, 2025)

Hydrological changes in the East Asian monsoon region around 4.2 ka precisely reconstructed from multi-proxy stalagmites - Chao-Jun Chen; Yao Wu; Jun-Yun Li; Hai-Wei Zhang; Hai Cheng; Chuan-Chou Shen; You-Feng Ning; Dao-Xian Yuan; R. Lawrence Edwards; Jian Zhang; Ting-Yong Li (Quaternary Science Reviews, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

Efficient fabrication of hunting trap-inspired degradable film with enhancing antimicrobial activity and reducing fomite transmission - Yu Du; Kai Mu; Xiaolong Li; Cheng Li; Chao Ding; Pingxu Chen; Ting Wu; Heng Xie; Jinping Qu (Journal of Hazardous Materials, 2025)

Comparative mechanisms of PDS-activated antibiotic remediation in groundwater via controlled-release materials with different mesoporous catalysts - Ting Wang; Jing-le Chen; Rui Huang; Hua-li Chen; Cheng Hu; Gang Chen; Kou-ping Chen; Ji-chun Wu (Journal of Environmental Management, 2025)

Advanced materials for CO2 capture and storage: A comprehensive review of current progress and future prospects - Jun Wang; Linjin Li; Guangfei Qu; Minhua Cheng; Yuanchuan Ren; Ping Lu; Ting Zhang; Yaoze Wang; Fenghui Wu (Journal of Environmental Chemical Engineering, 2025)

Correlation of volatile organic chemical exposure with uric acid metabolism among US population: A cross-sectional study from NHANES program - Yiyi Wang; Zichao Jiang; Jing Lei; Ziliang Tan; Yijie Wu; Yihe Hu; Junxiao Yang; Mingqing Li; Ting Lei; Long Hua (Journal of Environmental Sciences, 2025)

Flower like ZnO hybrid mediated visible light harvesting film with upgraded photodynamic antibacterial capacity for effective food preservation - Qingqing Li; Xinjie Yang; Zhiyi Wu; Longdong Qin; Linpin Luo; Liang Zhang; Ting Du; Bingzhi Li; Yiyue Ma; Yuanyuan Cheng; Wenxin Zhu; Wentao Zhang; et al. (Food Chemistry, 2025)

The morphologies, physicochemical properties and sustained-release features of short amylose/WPI modified by DBD plasma-rutin nanocomplex - Xiaojing Li; Ting Xu; Gongjian Fan; Caie Wu (Food Chemistry, 2025)

Nitrogen‑phosphorus responses and Vis/NIR prediction in fresh tea leaves - Qing Luo; Ting Tang; Yuxin Duan; Junlin Li; Caijin Ling; Ting Gao; Weibin Wu (Food Chemistry, 2025)

Detoxification of high solid-to-liquid ratio sugarcane bagasse hydrolysate using hydrophobic deep eutectic solvents for efficient cellulosic ethanol production - Yinan Hu; Chenxi Shi; Biying Li; Quanyuan Qiu; Jiuhang Song; Ting Wu; Lei Hu; Xiaoqing Lin (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Performance and mechanism of lead and cadmium stabilization in soil via two types of phosphorus-enriched biochars - Yingying Wu; Haibo Li; Ting Ma; Xinyi Gao; Yicheng Wu; Tianle Zhang (Biocatalysis and Agricultural Biotechnology, 2025)

Light intensity is a crucial factor that regulates growth, physiological traits, antioxidant defense, and metabolite acquisition in Dendrobium denneanum - Hui Wang; Siyu He; Yijun Fan; Ting Li; Linlong Xu; Jie Ma; Junlan Wu; Haolin Liu; XuYang Liu; ChunHong Mou; Meng Zhao; Li Chen; et al. (Physiology and Molecular Biology of Plants, 2025)

Impacts of water conservation, wastewater treatment, and reuse on water quantity and quality stress mitigation in China - Dan Wang; Zhuo Chen; Reetik Kumar Sahu; Taher Kahil; Ting Tang; Yuli Shan; Wei Zhang; Weili Ye; Guangxue Wu; Huimei Li; Klaus Hubacek (Journal of Industrial Ecology, 2025)
Wastewater treatment plays a crucial role in removing pollutants. Water conservation and reuse of wastewater help to reduce freshwater use and to alleviate water stress. However, the extent to which water conservation, wastewater treatment, and reuse can contribute to water stress mitigation is not clear. This study aims to investigate the impact of water conservation, wastewater treatment, and reuse on both water quantity and quality stress mitigation in China. The investigation is based on a dataset mapping water quantity and pollutant flows across 32 sectors in 31 provinces in 2017 and a dataset of 7411 wastewater treatment plants containing information on wastewater quantity and quality. The findings show that wastewater reuse can reduce provincial water quantity stress by less than 10% and alleviate water stress in 4 out of 25 water‐stressed provinces. In contrast, water conservation can contribute to water quantity stress reduction by 31% on average. When water conservation measures and reuse are jointly implemented, quantity stress levels can significantly be alleviated in 19 out of 25 water‐stressed provinces, with quantity stress reductions ranging from 25% to 74%. The contribution of wastewater treatment to water quality stress mitigation varies between 6% and 86%, with an average of 29%. Nevertheless, wastewater treatment cannot sufficiently safeguard most regions against water quality stress. This is evident as 25 out of 29 water quality‐stressed provinces continue to suffer from quality stress despite implementing wastewater treatment and water conservation practices. Additional measures such as non‐point‐source pollution control should be implemented alongside wastewater treatment to eliminate provincial quality stress.

First Report of the Molecular Prevalence of Trichomonads from Oral Cavities in Household Dogs and Cats in East China - Li-qin Gui; Xing-hua Wu; Si-lan Shi; Chen-chen Liu; Man-ting Li; Xue-li Ge; Jia-min Ma; Rong-jun Gong; Xin-chao Liu; Wen-chao Li (Acta Parasitologica, 2025)

Seasonal Variation of Phyllosphere Microbial Communities Under Warming - Chaotang Lei; Shu‐Yi‐Dan Zhou; David T. Tissue; Roy Neilson; Zhiyang Lie; Ting Wu; Xujun Liu; Chushu Meng; Xu Li; Dong Zhu; Juxiu Liu (Global Change Biology, 2025)
The phyllosphere is a complex microbial ecosystem residing on plant leaves, hosting microbes that influence plant growth and fitness. The phyllosphere is sensitive to temperature and moisture, so understanding its response to climate warming and variable moisture associated with changes in seasons is crucial for predicting ecosystem function. We conducted a 12‐year warming experiment in a sub‐tropical forest by transplanting a natural ecosystem from higher to lower elevations. We sampled phyllosphere microbial communities across wet and dry seasons for three consecutive years (years 10–12) to assess potential adaptation strategies to warming. Phyllosphere microbial community structure and diversity varied seasonally, with higher bacterial richness in the dry season; however, warming reduced bacterial richness across seasons. Co‐occurrence networks revealed stronger microbial interactions in the dry season, which exhibited reduced connectivity under warming. Community assembly was largely stochastic, with warming enhancing species turnover and dispersal. Notably, plant probiotics, enriched in the wetter season with greater environmental disturbances, played a key role in adaptation to seasonal changes and warming. Seasonal shifts in microbial function were observed: wet‐season bacteria were enriched in carbohydrate and energy metabolism, while dry‐season bacteria showed elevated sulfur metabolism, reflecting adaptive metabolic strategies to environmental conditions. Our study enhances the understanding of the seasonal patterns of phyllosphere microbial communities and the impact of climate warming, offering new insights into plant–microbial adaptation strategies in response to climate change.

Recent advances in innovative extraction techniques, comprehensive composition analysis, bioactivity assessment, and development of efficient delivery systems for sea buckthorn oil - Yazhuan Li; Zhanglian Chen; Jing Wang; Ting Wang; Wenyu Liu; Hongbin Wu; Changqing Wei (Trends in Food Science & Technology, 2025)

Organic fertilizer intensifies the vertical heterogeneity of DOM in paddy fields through interactions with soil minerals - Yi Xiao; Rong Huang; Weiliang Xiong; Binbin Liu; Qinghua Zhou; Tao Jiang; Vanessa N.L. Wong; Jiang Liu; Yingjie Wu; Youlin Luo; Qiquan Li; Qiang Xu; et al. (Soil and Tillage Research, 2025)

Association of long-term ozone exposure with the incidence and progression of hypertension, diabetes, and chronic kidney disease: A national retrospective cohort study - Yu-Ling Li; Po-Ya Chang; Ting-Wu Chuang; Yi-Chen Hsieh; Bo-Sian Wang; Szu-Ying Chen; Hung-Yi Chiou (Science of The Total Environment, 2025)

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Biochar-algae microspheres based on sodium alginate for the highly efficient adsorption of malachite green dye: Kinetics, isotherms, and mechanism of adsorption - Wei-Zhe Wu; Rui Li; Zhi-Qian-Li Ma; Chun-Xiao Liu; Wen-Ting Zhao (Journal of Contaminant Hydrology, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

One-step removal of p-arsanilic acid via constructing bifunctional Zr-CuO/α-FeOOH catalyst: Efficient peroxymonosulfate activation, cooperative oxidation and adsorption - Chaonan Tao; Kun Wu; Ting Liu; Shengjiong Yang; Zhihua Li (Chemical Engineering Journal, 2025)

Specifically targeted antimicrobial cyclic peptide to staphylococcal protein A for the treatment of S. aureus infection - Xiao-Ling Lei; Yong Li; Xue-Ting Cheng; Jie Zhuang; Fang Zhang; Xiao-Ting Xie; Lin-Fang Tan; Jin-Xuan Fan; Yuan-Di Zhao; Chuan-Liu Wu; Kai Cheng (Chemical Engineering Journal, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Arsenic Accumulation in Different Parent Materials of Rice (Oryza Sative L.) are Affected by Root Morphology - Yi Chen; Dehui Tu; Deqiang Li; Yinggang Xu; Yueyi Wu; Zhaoyong Zeng; Xiaoyan Tang; Yang Li; Chaorui Yan; Ting Lan; Fu Huang; Xuesong Gao; et al. (Journal of Plant Growth Regulation, 2025)

Experimental Study on the Hole-Forming Process at the Borehole Bottom During Hot Water Drilling in Ice and Its Influence Mechanisms - Zhipeng Deng; Youhong Sun; Xiaopeng Fan; Pavel Talalay; Yifan Yang; Ximu Liu; Da Gong; Bing Li; Ting Wang; Wei Wu; Nan Zhang; Xianzhe Wei (Journal of Marine Science and Engineering, 2025)
Hot water drilling is a drilling method that employs high-temperature and high-pressure hot water jetting to achieve ice melting drilling. Characterized by rapid drilling speed and large hole diameter, it is widely used for drilling observation holes in polar ice sheets and ice shelves. Understanding the hole-enlargement process at the bottom of hot water-drilled holes is crucial for rationally designing the structure of hot water drills. However, due to the complexity of heat transfer processes, no suitable theoretical model currently exists to accurately predict this process. To address this, this paper establishes an experimental platform for hot water drilling and conducts 24 sets of experiments under different drilling parameters using visualization techniques. The study reveals the influence mechanisms of drilling speed, hot water flow rate, hot water temperature, downhole drill shape, and nozzle structure on the hole-forming process at the borehole bottom. Experimental results indicate that the primary hole enlargement occurs near the nozzle, achieving 69–81% of the theoretical maximum borehole diameter. The thermal melting efficiency at the borehole bottom is approximately 80%, with about 20% of the input hot water energy heating the surrounding ice. Under identical hot water parameters, jet shapes and drill shapes exhibit minimal impact on borehole geometry. But the improvement of the jet speed and hot water temperature can accelerate the hole-forming process.

Disrupted coordination between primary and high-order cognitive networks in Parkinson’s disease based on morphological and functional analysis - Yunxiao Ma; Li Wang; Ting Li; Jian Zhang; Shintaro Funahashi; Jinglong Wu; Xiu Wang; Kai Zhang; Tiantian Liu; Tianyi Yan (Brain Structure and Function, 2025)

Mapping rice lodging severity using dual-pol Sentinel-1 SAR data: polarimetric parameters, lodging sensitivity, and fuzzy classification modelling - Mo Wang; Qing Sun; Xianghong Che; Li Chen; Yunpeng Cui; Juan Liu; Jinming Wu; Ting Wang; Huan Li (International Journal of Remote Sensing, 2025)

Long-term phosphate exposure effects on juvenile turbot (Scophthalmus maximus): Growth, metabolism, and adaptive responses - Xin Li; Lele Wu; Jiale Zhou; Yaolin Li; Ting Qi; Xiefa Song; Zongcheng Song; Xian Li (Marine Pollution Bulletin, 2025)

Magnolin ameliorates acetaminophen-induced liver injury in mice via modulating the MAPK pathway and lipid metabolism - Ting Yao; Youhe Wu; Liyun Fu; Lanjun Li (Toxicology and Applied Pharmacology, 2025)

Stalagmite multi-proxy records reveal spatial complexity of precipitation and monsoon variability in China over past 60 years - Yan-Xia Xue; Yao Wu; Chao-Jun Chen; Tao Fan; Huai Su; Han-Ying Li; Hai Cheng; Jian-Jun Yin; Jun-Yun Li; You-Feng Ning; Ting-Yong Li (Quaternary Science Reviews, 2025)

Odor impact patterns and health risks of various enterprises in the rubber product manufacturing industry - Yan Zhang; Yan Zhao; Li’an Hou; Zhiyang Zhang; Kehua Zou; Gen Wang; Zhiqiang Lu; Huanwen Cui; Jie Meng; Ting Wu; Jing Wang; Zengxiu Zhai (Journal of Hazardous Materials, 2025)

Impact of transglutaminase on structural and rheological properties of pea protein-cornmeal-wheat gluten blends for meat analogue production - Xiaowei Yu; Ting Li; Minghui Yue; Shanshan Zhang; Yingjuan Zhang; Xin Wang; Yubin Zhao; Jing Wu; Chenjie Wang; Chengye Ma (Journal of Food Engineering, 2025)

Fabrication of a highly efficient and stable peroxymonosulfate activator via a new sequential adsorption-encapsulation strategy induced by metal-organic framework - Ziyue Xu; Ting Wu; Yizhou Feng; Yixin Zhang; Ting Hou; Sining Yun; Zhihua Li; Weihuang Zhu (Journal of Environmental Chemical Engineering, 2025)

Source and variability of formaldehyde in the Fenwei Plain: An integrated multi-source satellite and emission inventory study - Liang Li; Keqin Duan; Yuyao Wu; Junhua Yang; Ting Yang; Peihong Shi; Rong Chen (Journal of Environmental Sciences, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Density-dependent selection effect of dominant species rather than species diversity increased aboveground biomass accumulation in a temperate oak forest - Guanjie Wang; Liu Yang; Xiuchen Wu; Ting Wang; Hongyan Liu; Zhicheng Chen; Chenyi Yu; Shengyun Liu; Zhenjiang Li (Forest Ecology and Management, 2025)

Effects of storage durations on flavour and bacterial communities in Liupao tea - Yueming Liang; Zhusheng Liu; Yuelan Pang; Min Li; Shengmeng Zheng; Fujing Pan; Chunyu Guo; Qianhua Wu; Ting Chen; Qiang Li; Zhonghua Liu (Food Chemistry, 2025)

Urinary concentrations of phthalate metabolites and the survival of high-grade serous ovarian cancer with advanced stage - Wen-Rui Zheng; Yi-Zi Li; Jin Xu; Ke-Xin Liu; Fang-Hua Liu; Wei-Yi Xing; Jia-Xin Liu; Lang Wu; Xiao-Ying Li; Dong-Hui Huang; Ting-Ting Gong; Qi-Jun Wu (Environmental Pollution, 2025)

DPP-GAN: A decentralized and privacy-preserving GAN system for collaborative smart meter data generation - Jianbin Li; Xi Xi; Shike Li; Sixing Wu; Ting Qiao (Energy and Buildings, 2025)

Cellulose nanocrystals for green remediation of contaminated soil with multiple heavy metals - Yaoyue Zhang; Zesen Ye; Weishan Liao; Qitang Wu; Zebin Wei; Rongliang Qiu; Ting Gao; Weixuan Xian; Kailong Zhang; Mi Li; Yangmei Chen (Environmental Geochemistry and Health, 2025)

Knockdown of SMYD3 by RNA Interference Regulates the Expression of Autophagy-Related Proteins and Inhibits Bone Formation in Fluoride-Exposed Osteoblasts - Jie Deng; Xiaoxiao Zeng; Kailin Zhang; Ting Zhang; Yangting Dong; Jian Zou; Changxue Wu; Yi Li; Fucheng Li; Zhizhong Guan (Biological Trace Element Research, 2025)

The Influence of Heterogeneous Processes on the Physicochemical Properties of Atmospheric Aerosols - Maofa Ge; Shengrui Tong; Lin Du; Lingyan Wu; Ting Lei; Kun Li; Minglan Xu; Narcisse T. Tsona; Wenqian Zhang; Hailiang Zhang (Advances in Atmospheric Sciences, 2025)
With the rapid development of the world economy, complex air pollution has increasingly become a serious threat; for example, with haze events occurring frequently in various regions of the globe. Recent evidence has indicated that secondary aerosols play an important role in haze formation, and that heterogeneous processes are among the main forces driving their explosive growth. In this regard, this paper reviews recent advances in the understanding of the impact of heterogeneous processes on haze chemistry, including the impact on NO 2 chemistry, marine aerosols, and the hygroscopicity and optical properties of atmospheric aerosols. It is distinguished from past reviews on this topic by focusing mainly on new insights from the past five years. We summarize the main findings of the impacts of heterogeneous processes on NO 2 chemistry, marine aerosols, and the physicochemical properties of atmospheric aerosols, and propose several future research directions.

Assembly mechanism of egg white protein-carboxymethyl cellulose based on surface patch binding effect: Interfacial complexation regulates high internal phase emulsion stability - Shanglin Li; Yajuan Li; Yulun Wu; Longjiang Tian; Hui Zhang; Ting Zhang; Jingbo Liu; Zhiyang Du (Food Chemistry, 2025)

Biotransformation of inorganic selenium into selenium nanoparticles and organic selenium by Lactiplantibacillus plantarum CXG4 - Yilong Li; Ting Wang; Daqun Liu; Chengcheng Zhang; Weicheng Wu; Huaxi Yi; Jianming Zhang (Food Bioscience, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Respiration-Driven Ammonia Sensing Mask for Multifunctional Self-powered Monitoring Application - Jinzhu Huang; Yichen Huang; Ting Li; Haoming Xu; Hanguang Wu; Zhiqiang Su (Chemical Engineering Journal, 2025)

Konjac glucomannan-based foams incorporating cellulose phase change microcapsules for efficient thermal energy regulation - Pengpeng Deng; Xinping Liu; Ting Zhang; Yuewen Li; Kao Wu; Kai Chen; Ying Kuang; Juanjuan Chen; Fatang Jiang (Carbohydrate Polymers, 2025)

Machine learning-based prediction of non-aeration linear alkylbenzene sulfonate mineralization in an oxygenic microalgal-bacteria biofilm - Libo Xia; Beibei Wu; Xiaocai Cui; Ting Ran; Qian Li; Yun Zhou (Bioresource Technology, 2025)

Rhizosphere bacterial communities mediate the effect of maize-soybean strip intercropping and nitrogen management on cadmium phytoextraction - Yuze Li; Ting Xing; Zhidan Fu; Tian Pu; Peng Ding; Yushan Wu; Feng Yang; Xiaochun Wang; Taiwen Yong; Wenyu Yang (Applied Soil Ecology, 2025)

Detecting monogenic disorders in utero non-invasively based on fetal nucleated red blood cells highly-purified by multi-functional magnetic nanoparticles - Lin Cheng; Chun Feng; Ke Wu; Zixiang Wang; Wentao Zhu; Ting Geng; Naiqi Li; Jiawei Kang; Jie Duan; Jin Li; Yuqi Shao; Saisai Yang; et al. (Analytica Chimica Acta, 2025)

Incorporating Genetic Diversity to Optimize the Plant Conservation Network in the Third Pole - Moses C. Wambulwa; Guang‐Fu Zhu; Ya‐Huang Luo; Zeng‐Yuan Wu; Jim Provan; Marc W. Cadotte; Alistair S. Jump; Francis N. Wachira; Lian‐Ming Gao; Ting‐Shuang Yi; Jie Cai; Hong Wang; et al. (Global Change Biology, 2025)
Climate change poses a significant threat to the survival of many species. Although protected areas can slow down biodiversity loss, they often lack systematic planning and do not integrate genetic diversity. Genetic diversity is a key prerequisite for species survival and the ability to tolerate new conditions. Using population genetic and distribution data from 96 plant species in the Third Pole (encompassing the Tibetan Plateau and adjacent mountains), we mapped patterns of genetic diversity, projected climate‐driven range dynamics and future genetic erosion, and designed an optimal conservation framework for the region. We identified several patches of high haplotype diversity ( H D ), with a relatively high number of haplotypes in southeastern Third Pole. Regression models revealed that climate and topography have interacted to shape patterns of genetic diversity, with latitude and precipitation being the best predictors for H D of cpDNA and nrDNA, respectively. Ecological niche modeling predicted an approximate 43 km northwestward and 86 m upward shift in suitable habitats under future climate scenarios, likely leading to a significant loss of up to 13.19% and 15.49% of cpDNA and nrDNA genetic diversity, respectively. Alarmingly, 71.20% of the newly identified conservation priority areas fall outside of the existing protected areas and planned National Park Clusters. Therefore, we recommend expanding the network by 2.02 × 10 5 km 2 (5.91%) in the Third Pole, increasing the total conserved area to 1.36 × 10 6 km 2 (39.93%) to effectively preserve the evolutionary potential of plants. This study represents an innovative attempt to incorporate genetic diversity into biodiversity conservation efforts.

The spatiotemporal variations of marine nematode populations may serve as indicators of changes in marine ecosystems - Hsuan-Tung Lin; Jiue-In Yang; Yu-Ting Wu; Yo-Jin Shiau; Li Lo; Shan-Hua Yang (Marine Pollution Bulletin, 2025)

Promoting effect of oxygen vacancies in CuZnOx-2/peroxymonosulfate system on the p-arsanilic acid degradation and secondary arsenic species immobilization - Chaonan Tao; Kun Wu; Ting Liu; Shengjiong Yang; Zhihua Li (Journal of Hazardous Materials, 2025)

Ticks jump in a warmer world: Global distribution shifts of main pathogenic ticks are associated with future climate change - Bo Cao; Chengke Bai; Kunyi Wu; Ting La; Wenwen Chen; Lianjin Liu; Xiaofang Zhou; Chong Chen; Xian Li; Yiyang Su; Lingyu Che; Guishuang Li (Journal of Environmental Management, 2025)

Double enzyme enhanced microbial induction of carbonate precipitation (E-MICP) to improve mechanical properties of sandy soil and its biocementation mechanism - Lei Niu; Yao-ting Duan; Xin Xu; Xiao-yan Wu; Zhe Wang; Chun-li Zheng (Journal of Environmental Chemical Engineering, 2025)

Evolution of the Asian summer monsoon during the Heinrich events 1–6 - Yan-Xia Xue; Yao Wu; Chao-Jun Chen; Jun-Yun Li; Hai Cheng; Chuan-Chou Shen; Jian Zhang; Ting-Yong Li (Global and Planetary Change, 2025)

Physicochemical and microstructural properties of frozen cooked noodles during frozen storage affected by enzymatically interesterified soybean oil-based plastic fat - Liuyu Hou; Beibei Zhao; Chuanjing Wu; Ting Liu; Xinru Liu; Hua Li (Food Research International, 2025)

Integrating widely targeted and oxylipin-targeted lipidomics unravels lipid characteristic evolution and oxidation markers in walnuts during deterioration - Hexin Zhang; Caiyun Wu; Mengmeng Zhang; Mei Li; Huaide Xu; Wenge Zhao; Ting Zhang; Hongjie Lei (Food Chemistry, 2025)

Enhancing the formation of functional glucosinolate degradation products in fermented broccoli stalk by-product with lactic acid bacteria - Qinghang Wu; Daqun Liu; Jianming Zhang; Ting Li; Haiyue Niu; Xiaoting Xin; Shengming Zhao; Chengyun He; Chengcheng Zhang (Food Chemistry, 2025)

Accurate discrimination of salmon species by monitoring lipid characteristics using Raman spectroscopy combined with psa-LR algorithm - Nan Zhong; Xuan Zong Li; Ting Wu (Food Control, 2025)

Influence of the main controlling factors on the tangential restitution coefficient of rockfall impact - Zhong-Min Ji; Ting-Hui Wang; Jie Wu; Fa-Quan Wu; Zhen-Hua Li; Dong-Po Wang; Yi-Ju Tang; Chang-Le Zhao; Qing-He Niu (Engineering Geology, 2025)

Charge density redistribution mechanism in dual-functional electrodes for enhanced the sulfophilic and lithiophilic of Li-S cells - Zeyu Geng; Xiaohan Wang; Junwei Li; Haifei Zhu; Ting Meng; Wencheng Qin; Penghui Wu; Yue Xiang; Fei Ma; Haifeng Zhang (Chemical Engineering Journal, 2025)

Metabolic outcomes of Cordyceps fungus and Goji plant polysaccharides during in vitro human fecal fermentation - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2025)

Comprehensive effects of biochar-assisted nitrogen and phosphorus bioremediation on hydrocarbon removal and microecological improvement in petroleum-contaminated soil - Xuhong Zhang; Manli Wu; Zeliang Liu; Yawen Ou; Ting Zhang; Mengqi Li (Bioresource Technology, 2025)

Spatiotemporal Mapping of the Oxytocin Receptor at Single-Cell Resolution in the Postnatally Developing Mouse Brain - Hao Li; Ying Li; Ting Wang; Shen Li; Heli Liu; Shuyi Ning; Wei Shen; Zhe Zhao; Haitao Wu (Neuroscience Bulletin, 2025)
The oxytocin receptor (OXTR) has garnered increasing attention for its role in regulating both mature behaviors and brain development. It has been established that OXTR mediates a range of effects that are region-specific or period-specific. However, the current studies of OXTR expression patterns in mice only provide limited help due to limitations in resolution. Therefore, our objective was to generate a comprehensive, high-resolution spatiotemporal expression map of Oxtr mRNA across the entire developing mouse brain. We applied RNAscope in situ hybridization to investigate the spatiotemporal expression pattern of Oxtr in the brains of male mice at six distinct postnatal developmental stages (P7, P14, P21, P28, P42, P56). We provide detailed descriptions of Oxtr expression patterns in key brain regions, including the cortex, basal forebrain, hippocampus, and amygdaloid complex, with a focus on the precise localization of Oxtr + cells and the variance of expression between different neurons. Furthermore, we identified some neuronal populations with high Oxtr expression levels that have been little studied, including glutamatergic neurons in the ventral dentate gyrus, Vgat + Oxtr + cells in the basal forebrain, and GABAergic neurons in layers 4/5 of the cortex. Our study provides a novel perspective for understanding the distribution of Oxtr and encourages further investigations into its functions.

The interactive effect of extreme weather events and PM2.5 on respiratory health among the elderly: a case-crossover study in a high-altitude city - Zhenxu Ning; Yanjun Ma; Shuzhen He; Genshan Li; Ting Xiao; Chunguang Ma; Jing Wu (International Journal of Biometeorology, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

First data on aquaculture of the narrow-barred Spanish mackerel (Scomberomorus commerson) in ponds - Pei-Sheng Chiu; Yeong-Torng Chu; Yen-Hung Lee; Jia-Shin He; Li-Chi Cheng; Ting-Jeng Chang; Jinn-Rong Hseu; Jinn-Shing Weng; Feng-Cheng Wu (Aquaculture International, 2025)

Involvement of copper in cell death and cancer - Jiahao Xie; Yue Su; Wenzhong Shang; Yanfang Wu; Junjia He; Ting Li; Yeyu Shen; Youni Zhang; Xiangmin Tong; Qiong Bian (Apoptosis, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Cross‐Continental Shifts of Ecological Strategy in a Global Plant Invader - Ramona E. Irimia; Weihan Zhao; Peipei Cao; Madalin Parepa; Zhi‐Yong Liao; Shengyu Wang; Jeannie M. Mounger; Conner Richardson; Fatima Elkott; Xin Zhuang; Jingwen Bi; Jieren Jin; et al. (Global Ecology and Biogeography, 2025)
Aim Plant invasions are a global problem that requires studying plants and their environmental associations across native and introduced ranges. Location 2000 km transects in China, Europe and North America. Time Period June 2019–July 2020. Major Taxa Studied Japanese knotweed ( Reynoutria japonica ). Methods We surveyed 150 populations of Japanese knotweed, a noxious invader of the temperate zone, along 2000 km transects in native China and the introduced ranges of Europe and North America. Results We found that larger plants and denser populations in the introduced ranges were associated with shifts in leaf economy and chemical defences. Introduced knotweed populations had higher SLA but reduced leaf chlorophyll, lignin, C:N ratio and leaf toughness along with altered leaf tannins, flavonoids and alkaloids. We found three distinct multivariate knotweed phenotypes primarily in the introduced ranges, and two multivariate knotweed phenotypes mainly in native populations. Main Conclusions Decreased herbivore and pathogen impacts in introduced populations and changes in environmental associations indicate that enemy release and novel habitat conditions might have driven the emergence of novel ecological strategies in this global plant invader.

Salmonella enterica serovar typhimurium effectors spiA and spiC promote replication by modulating iron metabolism and oxidative stress - Keyuan Chen; Jing Wang; Ting Hu; Yiqing Zhao; Yi Wu; Xue Wang; Wei Li; Guiyan Yang; Linlin Zhang; Jiufeng Wang; Yaohong Zhu (Veterinary Microbiology, 2025)

N-methyladenosine on the natural antisense transcript of NIA1 stabilizes its mRNA to boost NO biosynthesis and modulate stomatal movement - Jie Li; Wen Tian; Ting Chen; Qing-Yan Liu; Hua-Wei Wu; Chuan-Hui Liu; Yuan-Yuan Fang; Hui-Shan Guo; Jian-Hua Zhao (Molecular Plant, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Effects of UV-A irradiation and microbial fermentation on the physicochemical, microstructure and functional properties of okara - Ya-Ting Lei; Fan-Bing Meng; Xiao-Lei Jiao; Yuan-Mou Tang; Qi-Jun Wu; Yun-Cheng Li (Food Research International, 2025)

Fermented rhubarb alleviates metabolic dysfunction-associated steatotic liver disease symptoms by modulating gut microbiota and activating the hepatic insulin signaling pathway - Heng Yuan; Junyu Zhou; Ting Zhang; Xuangao Wu; Chen Li; Hee-Jong Yang; Do Yeon Jeong; Sunmin Park (Food Bioscience, 2025)

Photo-motivated heterojunctions coupling built-in electric field stimulating sulfur redox kinetics for lithium-sulfur batteries - Haifeng Zhang; Fei Ma; Ting Meng; Junwei Li; Haifei Zhu; Zeyu Geng; Wenbo Zhao; Xiaohan Wang; Penghui Wu; Abdelnaby M. Elshahawy; Qianrui Gao; Quande Che (Chemical Engineering Journal, 2025)

Incorporating graphene quantum dots boosts thermoelectric performance of PEDOT:PSS films - Ting Wu; Xiao-Lei Shi; Yu-Yu Deng; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Fang Yue; Pei Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2025)

Iron phthalocyanine coupled with Co-Nx sites in carbon nanostraws for Zn-Air batteries - Yi Wu; Junliang Chen; Jie Liu; Linjie Zhang; Reza Abazari; Ting-Ting Li; Jinjie Qian (Chemical Engineering Journal, 2025)

Changes of bacterial necromass and their roles in humus conversion during organic wastes composting from different sources - Wenjie Chen; Yan Yang; Su Chang; Yuquan Wei; Zhen Wu; Kaiyan Tang; Yuan Chang; Yifan Zhang; Ji Li; Ting Xu; Xia Liang (Bioresource Technology, 2025)

Aquibaculum sediminis sp. nov., a halotolerant bacteria isolated from salt lake sediment - Qing-Yu Xu; Lei Gao; Dildar Wu; Xin-Yao Li; Yong-Hong Liu; Yao Zhang; Yue-Heng Chen; Ting-Ting She; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Leaf Photosynthetic and Respiratory Thermal Acclimation in Terrestrial Plants in Response to Warming: A Global Synthesis - Ting Wu; David T. Tissue; Mingkai Jiang; Martijn Slot; Kristine Y. Crous; Junfeng Yuan; Juxiu Liu; Shaofei Jin; Chenxi Wu; Yan Deng; Chao Huang; Fuxi Shi; et al. (Global Change Biology, 2025)
Leaf photosynthesis and respiration are two of the largest carbon fluxes between the atmosphere and biosphere. Although experiments examining the warming effects on photosynthetic and respiratory thermal acclimation have been widely conducted, the sensitivity of various ecosystem and vegetation types to warming remains uncertain. Here we conducted a meta‐analysis on experimental observations of thermal acclimation worldwide. We found that the optimum temperature for photosynthetic rate ( T opt ) and the maximum rate of carboxylation of Rubisco ( T opt V) in tropical forest plants increased by 0.51°C and 2.12°C per 1°C of warming, respectively. Similarly, T opt and the optimum temperature for maximum electron transport rate for RuBP regeneration ( T opt J) in temperate forest plants increased by 0.91°C and 0.15°C per 1°C of warming, respectively. However, reduced photosynthetic rates at optimum temperature ( A opt ) were observed in tropical forest (17.2%) and grassland (16.5%) plants, indicating that they exhibited limited photosynthetic thermal acclimation to warming. Warming reduced respiration rate ( R 25 ) in boreal forest plants by 6.2%, suggesting that respiration can acclimate to warming. Photosynthesis and respiration of broadleaved deciduous trees may adapt to warming, as indicated by higher A opt (7.5%) and T opt (1.08°C per 1°C of warming), but lower R 25 (7.7%). We found limited photosynthetic thermal acclimation in needleleaved evergreen trees (−14.1%) and herbs (−16.3%), both associated with reduced A opt . Respiration of needleleaved deciduous trees acclimated to warming (reduced R 25 and temperature sensitivity of respiration (Q 10 )); however, broadleaved evergreen trees did not acclimate (increased R 25 ). Plants in grasslands and herbaceous species displayed the weakest photosynthetic acclimation to warming, primarily due to the significant reductions in A opt . Our global synthesis provides a comprehensive analysis of the divergent effects of warming on thermal acclimation across ecosystem and vegetation types, and provides a framework for modeling responses of vegetation carbon cycling to warming.

Biodegradation of imidacloprid and diuron by Simplicillium sp. QHSH-33 - Ke Xu; Xin-Ran Ke; Wan-Ting Zhang; Xin-Yuan Wu; Zhi-Jun Song; Mei-Juan Jiao; Xiao-Juan Gao; Li Zhou; Hong-Yan Ji; Fang Wang; Xiu-Li Wu (Pesticide Biochemistry and Physiology, 2024)

Discovery of polyoxygenated briaranes from octocoral Briareum stechei - Yue-Wen Chuang; Wei-Chen Ting; Su-Ying Chien; Li-Guo Zheng; Chih-Yin Huang; Zhi-Hong Wen; Yu-Jen Wu; Junichi Tanaka; You-Ying Chen; Jui-Hsin Su; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Synthesis of magnetically recyclable FeCeO nanocrystals with heterojunction between Fe2O3 and CeO2 via one-step method toward efficient organic dyes degradation by activating peroxymonosulfate - Liang Li; Chao-qun Wu; De-xiang Sun; Nan Zhang; Ting Huang; Yong Wang (Journal of Cleaner Production, 2024)

An efficient peroxymonosulfate activator derived from metal-organic frameworks: The application of Cu, Mg co-doping strategy - Ziyue Xu; Yizhou Feng; Ting Wu; Qiyu Shi; Wangbo Wang; Zhihua Li; Weihuang Zhu (Journal of Environmental Chemical Engineering, 2024)

Durable underwater superoleophobic hydrogels for oil- and Cu(II)-containing water purification - Chang-Lian Xu; Na Ji; Xingyue Wu; Xiaoxun Xu; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Shirong Zhang; Ting Li; Pietro Paolo de Oliveira e Silva; Guochun Lv; Junzhuo Cai; et al. (Journal of Environmental Chemical Engineering, 2024)

Combined application of multi-omics techniques and multivariate statistical analysis reveals the core functional microorganisms of Qula in Tibet, China - Ying Huang; Jiarong Li; Ting Li; Xingxing Deng; Qihong Zhong; Dezheng Wu; Zehuan Liu; Dawa Zhaxi; Yu Mu (Food Bioscience, 2024)

Effect of enzymatically interesterified rapeseed oil-based plastic fats on the dough properties and corresponding steamed bread - Beibei Zhao; Liuyu Hou; Xinru Liu; Chuanjing Wu; Ting Liu; Hua Li (Food Bioscience, 2024)

Bifidogenic properties of polysaccharides isolated from mushroom Lentinula edodes and enhanced immunostimulatory activities through Bifidobacterial fermentation - Lin Xi Huang; Fang Ting Gu; Yan Yu Zhu; Zi Chen Zhao; Jun Hui Li; Jian Yong Wu (Food Bioscience, 2024)

Closed-tube saltatory rolling circle amplification assay for rapid and visual detection of allergenic cashew nut in foods - Yingying Chen; Zipeng Guo; Zhaoqing Sun; Xinyu Wu; Yifan Xu; Zhengye Jin; Yuying Cheng; Zhen She; Qianqian Jiang; Yuxin Wo; Ting Wu; Hongwang Liu; et al. (Food Control, 2024)

Urine is better for rare earth elements bimonitoring in long-term exposed population: An exposure-response relationship study - Zhizhou He; Li Liu; Ting Wang; Cailan Zhou; Xuewei Zhang; Nan Wu; Mengmeng Xu; Jianqiong Gao; Bin Li; Yonglan Wang; Qiang Zhi; Chenguang Zhang; et al. (Environmental Research, 2024)

The remediation performance and mechanism for tetracycline from groundwater using controlled release materials containing mesoporous MnOx with different morphology - Ting Wang; Jing-le Chen; Rui Huang; Li-guang Wu; Kou-ping Chen; Ji-chun Wu; Hua-li Chen (Environmental Pollution, 2024)

High-performance thermoelectric PEDOT:PSS fiber bundles via rational ionic liquid treatment - Yu-Yu Deng; Xiao-Lei Shi; Ting Wu; Hao Wu; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Pei Huang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Free-standing, robust, hyperconnective hybrid nanofiber nonwovens enabled by interpenetrating network for oily aerosols purification - Weitao Zhou; Yiming Li; Zeng Qu; Sen Li; Ting Wu; Jingliang Li; Tingting Shi; Jikai Chen; Boyu Li; Haitao Huang; Shan Du (Chemical Engineering Journal, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

PinX1 plays multifaceted roles in human cancers: a review and perspectives - Dian You; Kaiwen Tong; Yuan Li; Ting Zhang; Yongqiang Wu; Ling Wang; Guangming Chen; Xiaoying Zhang (Molecular Biology Reports, 2024)

8-Br-cGMP suppresses tumor progression through EGFR/PLC γ1 pathway in epithelial ovarian cancer - Min Wu; Chunyan Mu; Huiwen Yang; Yue Wang; Ping Ma; Shibao Li; Zhongcheng Wang; Ting Lan (Molecular Biology Reports, 2024)

Synergistic effects of selenium and zinc on Bletilla striata (Thunb.) Reichb. F. growth and polysaccharide antioxidation - Changli Hu; Chengying Wang; Yan Wu; Long Liang; Liwei Yin; Xu Cheng; Conghu Li; Ting Hu (BioMetals, 2024)

Biogeography of a Global Plant Invader: From the Evolutionary History to Future Distributions - Lei Zhang; Isolde van Riemsdijk; Mu Liu; Zhiyong Liao; Armand Cavé‐Radet; Jingwen Bi; Shengyu Wang; Yujie Zhao; Peipei Cao; Madalin Parepa; Oliver Bossdorf; Armel Salmon; et al. (Global Change Biology, 2024)
Biological invasions pose a global challenge, affecting ecosystems worldwide and human societies. Knowledge of the evolutionary history of invasive species is critical to understanding their current invasion success and projecting their future spread. However, to date, few studies have addressed the evolutionary history and potential future spread of invaders simultaneously. In this study, we explored both evolutionary history and spatiotemporal dynamic patterns of the distribution of Reynoutria japonica , known as one of the world's worst plant invaders. We analysed 265 R. japonica samples from its current geographical ranges across three continents, using seven chloroplast DNA (cpDNA) markers to establish the phylogenetic relationships among extant populations. We combined these with ecological niche modelling to infer historical and more recent migration patterns and predict potential future distribution changes under climate change. Our results indicate that climate fluctuations and sea level changes likely facilitated the expansion of R. japonica from southern Japan to continental East Asia in the Pliocene, followed by a contraction in East Asian populations. In the recent Holocene, human activities have then enabled a linage of this species to spread from Japan to Europe and North America, resulting in three major global clades. Future climate scenarios suggest a northward expansion of R. japonica in Europe and North America, but shrinking habitat in China. Our study, thus, demonstrates the complex influences of historical climate‐driven migrations, human activities and future climate changes on the global distribution of an invasive species.

Co-grown novel S-scheme tubular P–UCN/S-TCN homojunction mediates photocatalysis-PMS activation synergistic system for efficient degradation of antibiotic - Ting Wu; Zhifeng Liu; Binbin Shao; Yuan Pan; Qingyun He; Xiansheng Zhang; Lingfeng Zhou; Yunze Wang; Teng Li; Sheng Liu (Chemosphere, 2024)

High emission of black carbon in heavy-duty diesel vehicles: Insights from microscopic operating conditions - Ting Chen; Xiao He; Liqiang He; Yan You; Lewei Zeng; Mingqiu Gao; Fengbin Wang; Yihuan Cao; Zhenhua Li; Xuan Zheng; Shaojun Zhang; Guangyi Xu; et al. (Science of The Total Environment, 2024)

Role of SbNRT1.1B in cadmium accumulation is attributed to nitrate uptake and glutathione-dependent phytochelatins biosynthesis - Yuan Lu; Ting Li; Ruijuan Li; Pan Zhang; XiaoXiao Li; Zhenqing Bai; Jiawen Wu (Journal of Hazardous Materials, 2024)

Mechanisms of inhibition and recovery under multi-antibiotic stress in anammox: A critical review - Xu Ji; Xiaonong Zhang; Ting Ju; Li Zhou; Da Jin; Peng Wu (Journal of Environmental Management, 2024)

TFEB/LAMP2 contributes to PM0.2-induced autophagy-lysosome dysfunction and alpha-synuclein dysregulation in astrocytes - Ben Li; Ting Liu; Yongmei Shen; Jiangnan Qin; Xiaohan Chang; Meiqiong Wu; Jianquan Guo; Liangpo Liu; Cailing Wei; Yi Lyu; Fengjie Tian; Jinzhu Yin; et al. (Journal of Environmental Sciences, 2024)

A molecular mechanism underlies grass carp (Ctenopharyngodon idella) TARBP2 regulating PKR-mediated cell apoptosis - Miao-miao Li; Chang-bai Tao; Mei-feng Li; Chu-xin Wu; Ting-ting Yu; Zhi-qing Feng; Qing-Zhang; Ze-yin Jiang; Hui-ling Mao; Shang-hong Wang; Xiao-wen Xu; Cheng-yu Hu (Fish & Shellfish Immunology, 2024)

Bioaerosols emission from source facilities in a wastewater treatment plant: Critical exposure time and sensitivity analysis - Yi-ning Hu; Wei-di Wan; Jun-ting Wu; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zhe-ren Tang; Cheng-yun Wang; Cheng Yan (Environmental Pollution, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Closed-loop recyclable wood-plastic composite as a sustainable alternative to wood: A solution for utilizing wood waste and promoting carbon sequestration - Shuang-Xi Hou; Chun-Yan Zhao; Wan-Ting Xiong; Jie Zhang; Mao-Qin Li; Guo-Qiang Tian; Gang Wu; Si-Chong Chen; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Simulated human digestion and fermentation of a high-molecular weight polysaccharide from Lentinula edodes mushroom and protective effects on intestinal barrier - Jun Hui Li; Fang Ting Gu; Ye Yang; Zi Chen Zhao; Lin Xi Huang; Yan Yu Zhu; Shiguo Chen; Jian Yong Wu (Carbohydrate Polymers, 2024)

Salinomycin, a potent inhibitor of XOD and URAT1, ameliorates hyperuricemic nephropathy by activating NRF2, modulating the gut microbiota, and promoting SCFA production - Yong-jun Chen; Zi-tao Guo; Hai-qiao Chen; Shi-fan Zhang; Ying-xia Bao; Zhoufan Xie; Jia-le Ke; Wen-jie Ye; Jia-cheng Liang; Jia-chen Chen; Ning Li; Feng-xin Zheng; et al. (Chemico-Biological Interactions, 2024)

Rill erosion and controlling factors on highway side-slopes in the permafrost region - Rui Li; Lilei Wu; Longxi Cao; Yaping Kong; Guo Chen; Ting Wu (Journal of Mountain Science, 2024)

Geographic variation in leaf traits and palatability of a native plant invader during domestic expansion - Yu‐Jie Zhao; Shengyu Wang; Zhi‐Yong Liao; Madalin Parepa; Lei Zhang; Peipei Cao; Jingwen Bi; Yaolin Guo; Oliver Bossdorf; Christina L. Richards; Jihua Wu; Bo Li; et al. (Ecology, 2024)
Like alien plant invasion, range expansion of native plants may threaten biodiversity and economies, rendering them native invaders. Variation in abiotic and biotic conditions across a large geographic scale greatly affects variation in traits and interactions with herbivores of native plant invaders, which is an interesting yet mostly unexplored issue. We used a common garden experiment to compare defensive/nutritional traits and palatability to generalist herbivores of 20 native (23.64° N–30.18° N) and introduced range (31.58° N–36.87° N) populations of Reynoutria japonica , which is a native invader following range expansion in China. We analyzed the relationships among herbivore pressure, climate, plant chloroplast haplotypes, leaf traits, and herbivore performance. Of the 16 variables tested, we observed range differences in 11 variables and latitudinal clines in nine variables. In general, herbivores performed better on the introduced plants than on the native plants, and better on the high‐latitude plants than on the low‐latitude plants within the introduced populations. Three key traits (leaf thickness, specific leaf area, and carbon‐to‐nitrogen [C:N] ratio) determined palatability to herbivores and were significantly associated with temperature and/or precipitation of plant provenance as well as with plant haplotypes but not with herbivore pressure. Our results revealed a causal sequence from plant‐range‐based environmental forces and genetic context to plant quality and palatability to herbivores in R. japonica . These findings suggest a post‐introduction evolution of R. japonica , which may partly explain the colonization success of this important native, but invasive plant.

Sirt4 Overexpression Modulates the JAK2/STAT3 and PI3K/AKT/mTOR Axes to Alleviate Sepsis-Induced Acute Lung Injury - Cancan Xie; Ting Wang; Anmin Liu; Bing Huang; Weizhong Zeng; Zhengrong Li; Suna Peng; Shuanghua Wu (Cell Biochemistry and Biophysics, 2024)

A critical review of comammox and synergistic nitrogen removal coupling anammox: Mechanisms and regulatory strategies - Da Jin; Xiaonong Zhang; Xingxing Zhang; Li Zhou; Zixuan Zhu; Ufoymungu Kisa Deogratias; Zhiqiang Wu; Kangyu Zhang; Xu Ji; Ting Ju; Xurui Zhu; Bo Gao; et al. (Science of The Total Environment, 2024)

Responses of soil organic carbon compounds to phosphorus addition between tropical monoculture and multispecies forests - Yue Li; Mengyu Wu; Ting Zhao; Zhijian Mou; Tengteng Li; Jing Zhang; Wenjia Wu; Faming Wang; Wei Zhang; Jun Wang; Yingwen Li; Dafeng Hui; et al. (Science of The Total Environment, 2024)

Beneficial effect of residential greenness on sperm quality and the role of air pollution: A multicenter population-based study - Tingting Dai; Wei Li; Lingxi Wang; Jiayi Zhou; Kaixin Zhong; Yunchong Yao; Xiaoyan Cai; Linwei Tian; Haisheng Wu; Ting Xu; Lina Xiao; Haobo Ni; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Nitrogen removal performance and functional microbial communities evolution in a continuous up-flow fixed bed anammox system - Zheng Lu; Junting Zhao; Zhenjun Wu; Ting Guo; Menghan Wang; Xiaomin Li; Dongjin Wan; Zhimin Du; Qiaochong He (Journal of Environmental Chemical Engineering, 2024)

Synthesis and characterization of Ce-BiOBr/Bi2S3 catalyst with enhanced catalytic activity for organic dye reduction under dark - Mengistu Tadesse Mosisa; Pengkun Zhang; Binghong Wu; Longyan Chen; Zhengjie Su; Ping Li; Hanya Zhang; Ambar Farooq; Ting Huang; Adugna Boke Abdeta; Osman Ahmed Zelekew; Dong-Hau Kuo; et al. (Journal of Environmental Chemical Engineering, 2024)

A combined experimental and theoretical study on the mechanism of catalytic oxidation of lignite to carboxylic acids by iron - Jiao-Xuan Bai; Cong Xu; Jie-Ping Wang; Rui Guo; Wei-Ze Wu; Ting Lu; Guang-Yue Li; Ying-Hua Liang (Fuel, 2024)

Bioactive compounds, volatile compounds, rheological properties and bacteriostatic activities of fig juices with oligosaccharides supplementation fermented by Lactiplantibacillus plantarum - Chengxin Wang; Caiyun Wu; Qiaomei Li; Ting Zhang; Hongjie Lei (Food Bioscience, 2024)

Fermented red pepper paste (kochujang) modulates glucose metabolism and gut microbiota in parasympathetic suppression: Network pharmacology and In vivo study - Ting Zhang; Chen Li; Yu Yue; Hee-Jong Yang; Myeong Seon Ryu; Xuangao Wu; Do Yeon Jeong; Sunmin Park (Food Bioscience, 2024)

Ferroptosis promotes valproate-induced liver steatosis in vitro and in vivo - Xinrui Yan; Linfeng Ma; Xue Chen; Jing Ren; Yu Zhai; Ting Wu; Yu Song; Xiaojiao Li; Yingjie Guo (Food and Chemical Toxicology, 2024)

Recyclable UV shielding film with water vapor barrier and antimicrobial properties enabled by in situ polymerization of caffeic acid phenethyl ester - Yan Lyu; Jiongjiong Li; Fangmin Liang; Wencan Ma; Hongxia Liu; Cheng Huang; Jian Jiao; Ting Wu; Guigan Fang (Chemical Engineering Journal, 2024)

Recent advances in micro/nano-robots for environmental pollutant removal: Mechanism, application, and prospect - Jia-yi Hou; Hong-tao Liu; Li-ting Huang; Shu-biao Wu; Zu-lin Zhang (Chemical Engineering Journal, 2024)

The role of rhamnolipids in the growth and defense responses of passion fruit plants - Ting Yang; Jihu Li; Yongkai Mao; Han Wu; Mingjiang Lin; Lijuan Chen (Physiology and Molecular Biology of Plants, 2024)

Thalamic Nucleus Reuniens Glutamatergic Neurons Mediate Colorectal Visceral Pain in Mice via 5-HT2B Receptors - Di Li; Han Du; Shu-Ting Qu; Jing-Lai Wu; Yong-Chang Li; Qi-Ya Xu; Xia Chen; Xiao-Xuan Dai; Ji-Tian Xu; Qian Wang; Guang-Yin Xu (Neuroscience Bulletin, 2024)
Irritable bowel syndrome (IBS) is a common functional bowel disorder characterized by abdominal pain and visceral hypersensitivity. Reducing visceral hypersensitivity is the key to effectively relieving abdominal pain in IBS. Increasing evidence has confirmed that the thalamic nucleus reuniens (Re) and 5-hydroxytryptamine (5-HT) neurotransmitter system play an important role in the development of colorectal visceral pain, whereas the exact mechanisms remain largely unclear. In this study, we found that high expression of the 5-HT 2B receptors in the Re glutamatergic neurons promoted colorectal visceral pain. Specifically, we found that neonatal maternal deprivation (NMD) mice exhibited visceral hyperalgesia and enhanced spontaneous synaptic transmission in the Re brain region. Colorectal distension (CRD) stimulation induced a large amount of c-Fos expression in the Re brain region of NMD mice, predominantly in glutamatergic neurons. Furthermore, optogenetic manipulation of glutamatergic neuronal activity in the Re altered colorectal visceral pain responses in CON and NMD mice. In addition, we demonstrated that 5-HT 2B receptor expression on the Re glutamatergic neurons was upregulated and ultimately promoted colorectal visceral pain in NMD mice. These findings suggest a critical role of the 5HT 2B receptors on the Re glutamatergic neurons in the regulation of colorectal visceral pain.

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Spatially lipidomic characterization of patient-derived organoids by whole-mount autofocusing SMALDI mass spectrometry imaging - Chunyan Lan; Ying Peng; Hengtong Zuo; Jianying Pei; Yue Li; Ting Zhang; Hainan Wu; Liyuan Du; Chang Zeng; Hongmei Zhao; Xiaofang Chen; Huafang Gao (Analytica Chimica Acta, 2024)

Nitrogenous fertilizer plays a more important role than cultivars in shaping sorghum-associated microbiomes - Fangfang Li; Anqi Sun; Xiaoyan Jiao; Dan-Ting Yu; Peixin Ren; Bing-Xue Wu; Peng He; Li Bi; Ji-Zheng He; Hang-Wei Hu (Science of The Total Environment, 2024)

Exploring the binding characteristics of bovine serum albumin with CDK4/6 inhibitors Ribociclib: Multi-spectral analysis and molecular simulation studies - Shao-Liang Jiang; Wang-Cai Chen; Yu-Ting Wu; Huan-Yu Sui; Dong Chen; Li Li; Tao Wu; Jie-Hua Shi (Journal of Photochemistry and Photobiology B: Biology, 2024)

Multifunctional bacterial cellulose-bentonite@polyethylenimine composite membranes for enhanced water treatment: Sustainable dyes and metal ions adsorption and antibacterial properties - Xueqing Zhao; Mingbo Yang; Yucheng Shi; Liyuan Sun; Haolong Zheng; Mengmeng Wu; Ge Gao; Ting Ma; Guoqiang Li (Journal of Hazardous Materials, 2024)

Geomechanical perspectives and reviews on the development and evolution of cross-scale discontinuities in the Earth's crust: Patterns, mechanisms and models - Sanbai Li; Zhijiang Kang; Moran Wang; Xi Zhang; Junliang Zhao; Xi-bing Li; Pengzhi Pan; Xin Luo; Hui Wu; Diyuan Li; Fengshou Zhang; Shunda Yuan; et al. (Gas Science and Engineering, 2024)

Development and characterization of pH-sensing films based on red pitaya (Hylocereus polyrhizus) peel treated by high-pressure homogenization for monitoring fish freshness - Hejun Wu; Luhong Chen; Ting Li; Shasha Li; Yanlin Lei; Maoxu Chen; Saiyan Chen; Xiangyang Yuan; Zhiqing Zhang; Anjun Chen (Food Hydrocolloids, 2024)

Caspase-8 promotes NLRP3 inflammasome activation mediates eye development defects in zebrafish larvae exposed to perfulorooctane sulfonate (PFOS) - Lu-Yin Wu; Jing-Lin Zhang; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Wan-Ting He; Nanxiang Jin; Ye Dai; Wei Chi; Zejin Ou; Guang-Hui Dong; Li-Zi Lin (Environmental Pollution, 2024)

The influence of hydrogeology and carbon sources on speleothem δ13C based on long-term monitoring in Furong Cave, southwest China - Jun-Yun Li; Ting-Yong Li; Hong-Chun Li; Christoph Spötl; Chao-Jun Chen; Jian Zhang; Yao Wu; Hua-Yan Li; Yue Jin; Min Zhao; Hong-Kai Li; Yan-Min Dong (Chemical Geology, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Identification and characterization of a novel type II toxin-antitoxin system in Aeromonas veronii - Caihong Ji; Ting He; Binbin Wu; Xiaomei Cao; Xiaping Fan; Xia Liu; Xiaodan Li; Miao Yang; Jihan Wang; Ling Xu; Shengbiao Hu; Liqiu Xia; et al. (Archives of Microbiology, 2024)

Performances of full-scale biological nitrogen pre-treatment process for drinking water source: Seasonal variations and microbial community - Hai-Hsuan Cheng; Yee Han Hew; Yi-Ju Wu; Tin-Yin Chen; Yi Ting Chiu; Li Ying Chen; Tsair-Fuh Lin; Liang-Ming Whang (Chemosphere, 2024)

Evaluation of a new real-time source apportionment system of PM2.5 and its implication on rapid aging of vehicle exhaust - Pei-Ting Yao; Xing Peng; Li-Ming Cao; Li-Wu Zeng; Ning Feng; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

Late Pliocene Bauhinia s.l. (Cercidoideae, Fabaceae) fossils from Tengchong, Yunnan, southwestern China - Rui Cao; Zhi-hui Song; Zhuo-er Wang; Zhao-shuai Wang; Han-shi Li; Jing-Yu Wu; Su-Ting Ding (Review of Palaeobotany and Palynology, 2024)

Quartz trace element geochemistry and internal morphology as proxies for provenance characterization: Results from the Marwar basin, NW India - Jun Zhang; Rui Li; Manoj K. Pandit; Ting-Guang Lan; Qing Xiong; Yuan-Bao Wu; Jun-Hong Zhao; Wei Wang (Precambrian Research, 2024)

Garciyunnanones A–R: Caged polycyclic polyprenylated acylphloroglucinols decorated with a lavandulyl substituent from Garcinia yunnanensis - Miaomiao Nan; Yueyou Yang; Ping Ying; Qiang Zheng; Youjun Wu; Tianjie Cao; Ting Li; Weiming Huang; Chuanlu Fu; Lingyi Kong; Wenjun Xu (Phytochemistry, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Changes in PI3K/AKT and NRF2/HO-1 signaling expression and intestinal microbiota in bleomycin-induced pulmonary fibrosis - Chenchen Li; Yuxia Cao; Yousheng Peng; Ting Ma; Fanlin Wu; Yongli Hua; Xiuqin Wang; Tong Bai; Yanming Wei; Peng Ji (Food and Chemical Toxicology, 2024)

Fish decay-accelerating factor (DAF) regulates intestinal complement pathway and immune response to bacterial challenge - Xia Zhang; Yuhan Zhang; Ting Wu; Hao He; Ran Peng; Kelan Jin; Huilan Mo; Fufa Qu; Jianzhou Tang; Yonghua Zhou; Yalin Yang; Zhigang Zhou; et al. (Fish & Shellfish Immunology, 2024)

Performance and microbial community evolution of toluene degradation in the presence of acetone vapors using hybrid membrane-aerated biofilm reactors (HMABRs) - Ziqing Wu; Ting Li; Xinglin Li; Xiwei Cao; Zhiye Sun; Ning Wang; Shuo Zhang; Baoan Li (Chemical Engineering Journal, 2024)

Hydrated eutectic electrolyte promotes the preferential growth of Zn (0 0 2) plane and suppresses side reaction for high-stability zinc anodes - Fangzhong Liu; Yinyin Zhang; Gao Li; Jinding Jiang; Lijuan Chen; Ting Song; Yong Pei; Xianyou Wang; Xiongwei Wu; Bei Long (Chemical Engineering Journal, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Dynamic intrauterine crosstalk promotes porcine embryo implantation during early pregnancy - Xupeng Zang; Shengchen Gu; Wenjing Wang; Junsong Shi; Jianyu Gan; Qun Hu; Chen Zhou; Yue Ding; Yanjuan He; Lei Jiang; Ting Gu; Zheng Xu; et al. (Science China Life Sciences, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

Saccharopolyspora mangrovi sp. nov., a novel mangrove soil actinobacterium with distinct metabolic potential revealed by comparative genomic analysis - Yi-Ting Lu; Yi-Yi Wu; Ya-Nan Li; Wei-Yi Zheng; Wen-Zheng Liu (Archives of Microbiology, 2024)

Systemic glucocorticoids link to long-term microvascular injury in COVID-19 - Qian Yang; Cai Yun Xia; Ying Cai; Yan Fang Zhang; Dao Ting Li; Shu Qi Wu; Peng Hu (Angiogenesis, 2024)

Emergence of colistin-resistant Stenotrophomonas maltophilia with high virulence in natural aquatic environments - Ting Zhang; Haiyan Wu; Chenchen Ma; Yidi Yang; Haibei Li; Zhongwei Yang; Shuqing Zhou; Danyang Shi; Tianjiao Chen; Dong Yang; Junwen Li; Min Jin (Science of The Total Environment, 2024)

Impact on sulfadiazine bio-accessibility in soils through organic diffusive gradients in thin films (o-DGT): Differentiation based on microplastic polymers, aging, and soil properties - Baochen Li; Chunli Zhu; Da Ouyang; Ting Guo; Xiaodong Wu; Yimin Cai; Haibo Zhang (Science of The Total Environment, 2024)

Functional identification of specialized diterpene synthases from Chamaecyparis obtusa and C. obtusa var. formosana to illustrate the putative evolution of diterpene synthases in Cupressaceae - Tsai-Jung Wu; Chi-Chun Lin; Li-Ting Ma; Chih-Kai Yang; Chen-Lung Ho; Sheng-Yang Wang; Fang-Hua Chu (Plant Science, 2024)

Anti-inflammatory discovery of sesquiterpenoids and a jasmonic acid derivative from Artemisia stolonifera - Ting Wu; Wen-Jing Wang; Zhou-Yuan Li; Yi-Tian Liu; Tian-Ping Yu; Shuang-Ge Li; Hong-Zhi Du; Chun Gui; Da-Hui Liu; Xiao-Long Yang (Phytochemistry, 2024)

A deep learning-based approach for fully automated segmentation and quantitative analysis of muscle fibers in pig skeletal muscle - Zekai Yao; Jingjie Wo; Enqin Zheng; Jie Yang; Hao Li; Xinxin Li; Jianhao Li; Yizhi Luo; Ting Wang; Zhenfei Fan; Yuexin Zhan; Yingshan Yang; et al. (Meat Science, 2024)

Microplastic pollutants in sediments from a water supply reservoir: Spatial heterogeneity in abundance, characteristics and pollution evaluation - Yunzhao Liu; Le Liang; Jiajun Wu; Xianfu Zhao; Jing Li; Ting Fang; Yangyang Liang; Zhongguan Jiang (Limnologica, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Characterization of Pseudomonas spp. contamination and in situ spoilage potential in pasteurized milk production process - Guanhong Chang; Qianhong Li; Ting Wang; Bozheng Zhang; Wendi Wu; Chunyang Lv; Tongzhuo Sun; Ting Zhou; Wanxiang Zheng; Yeru Wang; Xin Wang (Food Research International, 2024)

Rapid visual detection of sulfur dioxide residues in food using acid-sensitive CdTe quantum dots-loaded alginate hydrogel beads - Wei Lan; Yanmin Rao; Xiangyu Zhao; Yi Zhao; Xinyi Min; Yue Wu; Ziyi Jiang; Ting Li; Yinhua Li; Hengye Chen; Wanjun Long; Yuanbin She; et al. (Food Chemistry, 2024)

Microscopic identification of foodborne bacterial pathogens based on deep learning method - Qiong Chen; Han Bao; Hui Li; Ting Wu; Xin Qi; Changqiang Zhu; Weilong Tan; Desheng Jia; Dongming Zhou; Yong Qi (Food Control, 2024)

Viscoelastic cues to induce stem cell migration and neuronal differentiation in cell-free hydrogel-assisted TBI recovery - Xiaoyin Liu; Chengheng Wu; Yusheng Zhang; Gaowei Li; Suping Chen; Zhihong Chen; Peng Liu; Kai Wu; Xiaoyang Wu; Ting Zhou; Mingze Zeng; Zi Qiao; et al. (Chemical Engineering Journal, 2024)

Genome-wide association studies dissect low-phosphorus stress response genes underling field and seedling traits in maize - Bowen Luo; Guidi Zhang; Ting Yu; Chong Zhang; Guohui Yang; Xianfu Luo; Shuhao Zhang; Jianyong Guo; Haiying Zhang; Hao Zheng; Zirui Tang; Qile Li; et al. (Theoretical and Applied Genetics, 2024)

Deleterious variants in RNF111 impair female fertility and induce premature ovarian insufficiency in humans and mice - Chengcheng Song; Yingying Qin; Yan Li; Bingyi Yang; Ting Guo; Wenqing Ma; Dian Xu; Keyan Xu; Fangfang Fu; Li Jin; Yanhua Wu; Shuyan Tang; et al. (Science China Life Sciences, 2024)

Variable climatic conditions dominate decreased wetland vulnerability on the Qinghai‒Tibet Plateau: Insights from the ecosystem pattern-process-function framework - Zhengyuan Zhao; Bojie Fu; Yihe Lü; Ting Li; Lei Deng; Yuelu Wang; Da Lü; Yi Wang; Xing Wu (Journal of Cleaner Production, 2024)

Scalable fabrication of multifunctional polylactic acid fibrous membranes with enhanced superhydrophobicity and radiative cooling performance - Xiaolong Li; Yu Du; Mengjie Sheng; Heng Xie; Ting Wu; Jinping Qu (Journal of Cleaner Production, 2024)

Metabolomic insights into the profile, bioaccessibility, and transepithelial transport of polyphenols from germinated quinoa during in vitro gastrointestinal digestion/Caco-2 cell transport, and their prebiotic effects during colonic fermentation - Meijiao Li; Xuan Zhang; Zhe Gao; Mengying Wu; Ting Ren; Chen Wu; Jie Wang; Yanlou Geng; Wei Lv; Qian Zhou; Wen Zhao (Food Research International, 2024)

Modified halloysite nanotubes as GRAS nanocarrier for intelligent monitoring and food preservation - Qingqing Li; Yuxin Gong; Ting Du; Liang Zhang; Yiyue Ma; Tong Zhang; Zhiyi Wu; Wentao Zhang; Jianlong Wang (Food Chemistry, 2024)

Mechanism of catalytic subcritical water oxidation of m-nitroaniline and nitrogen conversion by CuCo2O4 catalyst - Mian Hu; Meiqi Chen; Zhibin Li; Zhiheng Ye; Zhong-Ting Hu; Zhiyan Pan; Dabin Guo; François Nkinahamira; Jinling Wan; Libo Wu; Baihui Cui; Junliang Wang (Chemical Engineering Journal, 2024)

High capacity and long service in sodium-ion batteries achieved by the refinement of BiOCl from lamellar to flower-like in ether electrolyte - Sheng-Li Wei; Yan-Ling Yang; Xiao-Lei Shi; Yu Sun; Jin-Geng Chen; Xue-Feng Tian; Yuan-Ting Wu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Low-voltage stimulated denitrification performance of high-salinity wastewater using halotolerant microorganisms - Long Chen; Hai Xiang; Li-Ting Zhou; Yan-Qing Zhang; Yang-Cheng Ding; Di Wu; Nan-Wen Zhu; Yi-Feng Zhang; Hua-Jun Feng (Bioresource Technology, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Effects of Different Forms of Sulfur on Plant Growth and Soil Properties in Cadmium-Contaminated Soils - Honglei Jia; Cui Chen; Qing Wang; Yuting Wei; Junkang Guo; Chunping Zhang; Guangfang Wu; Ting Wei; Xinhao Ren; Chao Zhang; Jisheng Li (Journal of Soil Science and Plant Nutrition, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Allocate electric vehicles’ public charging stations with charging demand uncertainty - Ting Wu; Emily Fainman; Yasmina Maïzi; Jia Shu; Yongzhen Li (Transportation Research Part D: Transport and Environment, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Effects of biochar immobilization of Serratia sp. F4 OR414381 on bioremediation of petroleum contamination and bacterial community composition in loess soil - Xuhong Zhang; Manli Wu; Ting Zhang; Huan Gao; Yawen Ou; Mengqi Li (Journal of Hazardous Materials, 2024)

Exploring of multi-functional umami peptides from Stropharia rugosoannulata: Saltiness-enhancing effect and mechanism, antioxidant activity and potential target sites - Wanchao Chen; Wen Li; Di Wu; Zhong Zhang; Zhengpeng Li; Long Li; Ting Wu; Yan Yang (Food Chemistry, 2024)

E-eye and FT-NIR combined with multivariate algorithms to rapidly evaluate the dynamic changes in the quality of Gastrodia elata during steaming process - Jiu-ba Zhang; Bin Wang; Yun-fei Zhang; Yi Wu; Ming-xuan Li; Ting Gao; Tu-lin Lu; Zhen-hua Bian; Lian-lin Su (Food Chemistry, 2024)

Eggshell powder as a bio-filler for starch and gelatin: Ternary biodegradable composite films manufactured by extrusion compression molding - Ting Li; Ruofei Li; Haodan Luo; Lu Peng; Jie Wang; Shasha Li; Man Zhou; Xiangyang Yuan; Zhiqing Zhang; Hejun Wu (Food Hydrocolloids, 2024)

Comparative study of reactive oxygen species and tetracycline degradation pathways in catalytic peroxodisulfate activation by asymmetric mesoporous TiO2 and the corresponding controlled-release materials - Ting Wang; Rui Huang; Hua-Li Chen; Kun-Miao Xu; Li-Guang Wu; Kou-Ping Chen; Ji-Chun Wu (Environmental Pollution, 2024)

Advanced “turn-on” colorimetric uranium platform based on the enhanced nanozyme activity of a donor-acceptor structured covalent organic framework - Sai Jin Xiao; Jing Huang; An Ting Qiu; Guang Zhou Liu; Li Zhang; Ting Wu; Ya Di Shi; Jian-Ding Qiu (Analytica Chimica Acta, 2024)

Mechanisms of biochar assisted di-2-ethylhexyl phthalate (DEHP) biodegradation in tomato rhizosphere by metabolic and metagenomic analysis - Zhong Lin; Weijian Wu; Changhong Yang; Guiqiong Yang; Weilong Wu; Ting Wei; Fengcheng Huang; Huijun Li; Lei Ren; Yanqiu Liang; Dayi Zhang; Zhe Li; et al. (Chemosphere, 2024)

NKX2-1-AS1 promotes the lymphangiogenesis of lung adenocarcinoma through regulation of ERG-mediated FABP4 - Ting Tao; Hui Chen; Qimei Xu; Zhen Li; Xuelian Chen; Xunjian Zhou; Wu Luo (Tissue and Cell, 2024)

Preparing a heavy-metal adsorbent based on alginate-like extracellular polymers from conventional activated sludge via polyethyleneimine grafting - Chen Shi; Run-Gen Zeng; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Xiao-Di Hao; Nan Zhang; Yuan-Yuan Wu (Sustainable Chemistry and Pharmacy, 2024)

Simplified estimates of soil nematode body mass using maximum diameter: Insights from large-scale grasslands across China - Quanhui Ma; Yu Zhu; Ying Chen; Wenjia Wu; Xue Qing; Ting Liu; Yibo Li; Yao Wang; Yanan Li; Deli Wang; Jushan Liu; Ling Wang (Soil Biology and Biochemistry, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

The phytocytokine systemin enhances postharvest tomato fruit resistance to Botrytis cinerea - Pingyu Wang; Ting Wu; Yulin Cheng; Ying Gao; Baowen Huang; Zhengguo Li (Postharvest Biology and Technology, 2024)

Plasma-activated water regulates water distribution to resist softening of goji berries - Kai-Ping Cong; Cai-E. Wu; Ting-Ting Li; Gong-Jian Fan; Dan-dan Zhou; Xiao-jing Li; An-Di Suo; Xu Li (Postharvest Biology and Technology, 2024)

TFN nanofiltration membrane incorporating ZIF-8@MXene for efficient removal ReO4- from simulated nuclear-contaminated wastewater - Ning-xiao Wei; Yu-xing Wang; Hua-li Chen; Li-guang Wu; Ting Wang (Journal of Environmental Chemical Engineering, 2024)

A review of cumulative toxic effects of environmental endocrine disruptors on the zebrafish immune system: Characterization methods, toxic effects and mechanisms - Zixu Li; Muge Li; Dan Li; Yao Chen; Weiwei Feng; Ting Zhao; Liuqing Yang; Guanghua Mao; Xiangyang Wu (Environmental Research, 2024)

Ozone and its precursors at an urban site in the Yangtze River Delta since clean air action plan phase II in China - Hua Fang; Wenjing Wang; Ran Wang; Hongling Xu; Ying Zhang; Ting Wu; Ruicheng Zhou; Jianxi Zhang; Zhirong Ruan; Feng Li; Xinming Wang (Environmental Pollution, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Machine-learning-aided prediction and engineering of nitrogen-containing functional groups of biochar derived from biomass pyrolysis - Lijian Leng; Xinni Lei; Naif Abdullah Al-Dhabi; Zhibin Wu; Zequn Yang; Tanghao Li; Weijin Zhang; Wei Liu; Hao Zhan; Haoyi Peng; Wangwang Tang; Ting Xiong; et al. (Chemical Engineering Journal, 2024)

A novel method to quantify chitosan in aqueous solutions by ultrahigh-performance liquid chromatography–tandem mass spectrometry - Ting Xue; Lei Zhou; Fanjun Wang; Zhuang Tian; Nanxi Li; Tong Ye; Ruolin Hao; Lei Yang; Ruolan Gu; Hui Gan; Zhuona Wu; Xiaoxia Zhu; et al. (Carbohydrate Polymers, 2024)

Interactive effects of soil erosion and mechanical compaction on soil DOC dynamics and CO2 emissions in sloping arable land - Huizhou Gao; Xiaojun Song; Xueping Wu; Naiyu Zhang; Ting Liang; Zhufeng Wang; Xun Yu; Chengjiao Duan; Zixuan Han; Shengping Li (CATENA, 2024)

Tailpipe volatile organic compounds (VOCs) emissions from Chinese gasoline vehicles under different vehicle standards, fuel types, and driving conditions - Peiji Liu; Yajun Wu; Zongxuan Li; Zongyan Lv; Jinsheng Zhang; Yan Liu; Ainan Song; Ting Wang; Lin Wu; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2024)

Phosphorus mining activities alter endophytic bacterial communities and metabolic functions of surrounding vegetables and crops - Qiang Li; Peng Xiang; Lijiao Li; Ting Zhang; Qian Wu; Zhijie Bao; Wenying Tu; Changsong Zhao (Plant and Soil, 2024)

Combined effects of copper and cadmium exposure on ovarian function and structure in Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Ting Huang; Qiyu Wei; Xin Yan; Liting Chen; Zhirui Ma; Liming Luo; Jinling Cao; Hongxing Chen; Xinxian Wei; Honglian Tan; Fuyan Chen; et al. (Ecotoxicology, 2024)

Transforming waste brake pads from automobiles into Nano-Catalyst: Synergistic Fe-C-Cu triple sites for efficient fenton-like oxidation of organic pollutants - Fuyuan Qi; Jianfei Peng; Zilu Liang; Jiliang Guo; Jiawei Yin; Ainan Song; Zongxuan Li; Jiayuan Liu; Tiange Fang; Jinsheng Zhang; Lin Wu; Qijun Zhang; et al. (Waste Management, 2024)

Polyethylene microplastic modulates lettuce root exudates and induces oxidative damage under prolonged hydroponic exposure - Yimin Cai; Yangyang Xu; Guanlin Liu; Baochen Li; Ting Guo; Da Ouyang; Mei Li; Shuai Liu; Yingyu Tan; Xiaodong Wu; Haibo Zhang (Science of The Total Environment, 2024)

Mixed plantations do not necessarily provide higher ecosystem multifunctionality than monoculture plantations - Xu Li; Yue Liu; Guopeng Wu; Zhiyang Lie; Han Sheng; Luis Carlos Ramos Aguila; Muhammmad Sadiq Khan; Xujun Liu; Shuyidan Zhou; Ting Wu; Wenfang Xu; Juxiu Liu (Science of The Total Environment, 2024)

Soil freeze–thaw cycles affect spring phenology by changing phenological sensitivity in the Northern Hemisphere - Ting Li; Bojie Fu; Yihe Lü; Chenjun Du; Zhengyuan Zhao; Fangfang Wang; Guangyao Gao; Xing Wu (Science of The Total Environment, 2024)

Molecular intelligent perception on soft interfaces - Shuangshuang Wu; Songrui Liu; Ting Li; Jinxing Li; Lianhui Wang; Ting Wang (Science Bulletin, 2024)

Pigmentiphaga kullae CHJ604 improved the growth of tobacco by degrading allelochemicals and xenobiotics in continuous cropping obstacles - Jia-Xi Xiong; Ling-Shan Du; Na-Na Li; Xiu-Ting Wu; Yang Xiang; Sha Li; Lei Zou; Dongqi Liu; Duo Huang; Ze Feng Xie; Ying Wang; Jinhua Li; et al. (Journal of Hazardous Materials, 2024)

OPEs-ID: A software for non-targeted screening of organophosphate esters based on liquid chromatography-high-resolution mass spectrometry - Yinran Xiong; Jinyue Liu; Jing Yu; Da Chen; Tiantian Li; Fengli Zhou; Ting Wu; Xiaotu Liu; Yiping Du (Journal of Hazardous Materials, 2024)

Oxidative stress-activated Nrf2 remitted polystyrene nanoplastic-induced mitochondrial damage and inflammatory response in HepG2 cells - Menghao Guo; Yunjing Li; Shuyan Niu; Rui Zhang; Xin Shen; Yu Ma; Liqing Wu; Tianshu Wu; Ting Zhang; Meng Tang; Yuying Xue (Environmental Toxicology and Pharmacology, 2024)

Molecular layer deposited mechanically and chemically robust niobicone interface empowering silicon nanowire anodes with competent cyclabilities - Jiabin Fang; Jianguo Li; Wangle Zhang; Lijun Qin; Kang Wu; Longfei Hui; Ting Gong; Dan Li; Yiyun Hu; Aidong Li; Hao Feng (Chemical Engineering Journal, 2024)

The Effect of Copper–Cadmium Co-Exposure and Hormone Remediation on the Ovarian Transcriptome of Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Liting Chen; Xin Yan; Jun Xiao; Zhirui Ma; Zhanyang Tang; Zhongbao Guo; Liping Li; Guixiang Tong; Honglian Tan; Fuyan Chen; Xinxian Wei; et al. (Fishes, 2024)
The escalating problem of copper (Cu) and cadmium (Cd) pollution in aquatic environments poses a significant threat to the ovarian tissue and reproductive capacity of fish, hindering the development of the aquaculture industry. However, the combined effects of Cu and Cd on fish gonadal development remain unclear. In this study, the fish species Nile tilapia was stressed with rearing water containing 300 μg/L Cu2+ and 100 μg/L Cd2+ for 30 days, followed by an intraperitoneal injection of luteinizing hormone-releasing hormone (LHRH-α) and human chorionic gonadotropin (HCG) at various concentrations. We investigated the ovarian transcriptome profiles before and after injection. Prior to injection, combined treatment with Cu and Cd resulted in reproductive dysfunction and metal ion imbalance in tilapia. Transcriptomic profiling revealed differential gene annotation concentrated in the MAPK signaling pathway and regulation of GTPase activity. Post-injection, all concentrations of LHRH-α and HCG groups showed an upregulated gonadosomatic index (G.S.I) and higher levels of vitellogenin (VTG), gonadotropin-releasing hormone (GnRH), gonadotropin (GTH), and estrogen (E2) in serum compared to the negative control group. Transcriptomic analysis revealed alterations in various ovarian signaling pathways, preliminarily revealing the in vivo molecular mechanisms and differences in LHRH-α and HCG. The findings from this study could help us better understand how to counteract the effects of combined Cu and Cd exposure on tilapia ovarian development, which has significant implications for the Nile tilapia aquaculture industry.

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

l-valine supplementation disturbs vital molecular pathways and induces apoptosis in mouse testes - Zi-Wei Wu; Li Wang; Qiao Mou; Fang Wang; Yi Wang; Ting Fang; Zongjun Yin; Zhi-Qiang Du; Cai-Xia Yang (Theriogenology, 2024)

Nonlinear proinflammatory effect of short-term PM2.5 exposure: A potential role of lipopolysaccharide - Fangxia Shen; Mutong Niu; Haoxuan Chen; Ting Zhang; Jing Li; Haijie Tong; Yan Wu (Journal of Environmental Sciences, 2024)

Research progress of the effects of bisphenol analogues on the intestine and its underlying mechanisms: A review - Min Zhu; Ran Zeng; Dan Wu; Yuanyuan Li; Ting Chen; Aijie Wang (Environmental Research, 2024)

MOF derived MnFeOX supported on carbon cloth as electrochemical anode for peroxymonosulfate electro-activation and persistent organic pollutants degradation - Xiansheng Zhang; Yuan Pan; Yunze Wang; Ting Wu; Binbin Shao; Qingyun He; Lingfeng Zhou; Teng Li; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Application of 3D hierarchical porous NiCo-spinel nanosheet array for enhancement of synergistic activation of peroxymonosulfate: Degradation, Intermediates, mechanism and degradation pathway of tetracycline - Yuan Pan; Xiansheng Zhang; Ting Wu; Binbin Shao; Teng Li; Qingyun He; Zehua Chen; Lingfeng Zhou; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Activated carbon-boosted BiOI in CO2 adsorption and electron transfer for photothermally catalyzed CO2 oxidative dehydrogenation of propane - Run-Qing Miao; Zhen-Hong He; Bao-Ting Wu; Jiajie Liu; Sen-Wang Wang; Kuan Wang; Weitao Wang; Lu Li; Zhao-Tie Liu (Chemical Engineering Journal, 2024)

Hydrogel sensors for biomedical electronics - Jingyun Ma; Jiaqi Zhong; Fuqin Sun; Botao Liu; Zhaoxiang Peng; Jiangfang Lian; Xiang Wu; Lianhui Li; Mingming Hao; Ting Zhang (Chemical Engineering Journal, 2024)

Sources and secondary transformation potentials of aromatic hydrocarbons observed in a medium-sized city in yangtze river delta region: Emphasis on intermediate-volatility naphthalene - Hua Fang; Wenjing Wang; Hongling Xu; Yuzhe Huang; Han Jiang; Ting Wu; Jun Li; Shuping Zha; Jianxi Zhang; Ruicheng Zhou; Xinming Wang (Atmospheric Environment, 2024)

Nitrogen-mediated distinct rhizosphere soil microbes contribute to Sorghum bicolor (L.) Moench and Solanum nigrum L. for phytoremediation of cadmium-polluted soil - Jiawen Wu; Na Zhao; Xiaoxiao Li; Pan Zhang; Ting Li; Yuan Lu (Plant and Soil, 2024)

RETRACTED ARTICLE: Carnosic acid nanocluster-based framework combined with PD-1 inhibitors impeded tumorigenesis and enhanced immunotherapy in hepatocellular carcinoma - Wenhua Wu; Yaping Li; Xiaokang Wu; Junrong Liang; Weiming You; Xinyuan He; Qinhui Feng; Ting Li; Xiaoli Jia (Functional & Integrative Genomics, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Effects of uranium mining on soil bacterial communities and functions in the Qinghai-Tibet plateau - Qiang Li; Zhuang Xiong; Peng Xiang; Lin Zhou; Ting Zhang; Qian Wu; Changsong Zhao (Chemosphere, 2024)

Gentamicin administration leads to synaptic dysfunction in inner hair cells - Gen Li; Yunge Gao; Hao Wu; Ting Zhao (Toxicology Letters, 2024)

The effects of boar seminal plasma extracellular vesicles on sperm fertility - Zhiqian Xu; Yanshe Xie; Changhua Wu; Ting Gu; Xianwei Zhang; Jie Yang; Huaqiang Yang; Enqin Zheng; Sixiu Huang; Zheng Xu; Zicong Li; Gengyuan Cai; et al. (Theriogenology, 2024)

Oropharyngeal aspirated Ag/TiO2 nanohybrids: Transformation, distribution and toxicity - Xiaoquan Huang; Congcong Li; Tingting Wei; Na Liu; Yongshuai Yao; Zhihui Wang; Yuanyuan Hu; Qing Fang; Shujing Guan; Yuying Xue; Tianshu Wu; Ting Zhang; et al. (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Arsenic induced neurotoxicity in the brain of ducks: The potential involvement of the gut-brain axis - Shaofeng Wu; Gaolong Zhong; Qian Su; Ting Hu; Gan Rao; Tong Li; Yuhan Wu; Zhiyan Ruan; Hui Zhang; Zhaoxin Tang; Lianmei Hu (Journal of Trace Elements in Medicine and Biology, 2024)

Combined antimicrobial effect of high pressure processing and ethyl lauroyl arginate (LAE)-containing films and its application in coconut water preservation - Ting Li; Junyu Chen; Xiaorong Duan; Xiaomeng Wu; Xiaojun Liao (Food Control, 2024)

Critical role of post-treatment induced surface reconstruction for high performance inorganic tin-lead perovskite solar cells - Ting Zhang; Feng Qian; Hao Chen; Hualin Zheng; Lei Wang; Shihao Yuan; Yafei Wu; Zhi David Chen; Shibin Li (Chemical Engineering Journal, 2024)

An injectable selenite-containing hydrogel for synergistic tumor therapy by triggering ROS/RNS generation and disrupting NADPH homeostasis - Weiyong Tao; Xiaodan Wu; Jiaqi Li; Feige Wu; Chen Chen; Ting Jiang; Cunjing Xu; Shangtong Jiang; Jianglin Wang; Bo Xiao; Yingying Du; Shengmin Zhang (Chemical Engineering Journal, 2024)

Boosting H2O2 utilization efficiency in benzene hydroxylation to phenol via isolated single VO4 site on hydrophobic poly(ionic liquid)-derivative - Zhe Chen; Chao Wu; Xiaoling Liu; Ting Li; Menglin Xie; Shibo Xi; Yu Zhou; Jun Wang (Chemical Engineering Journal, 2024)

Initial soil moisture prewinter affects the freeze–thaw profile dynamics of a Mollisol in Northeast China - Yanru Wen; Bao Liu; Heng Jiang; Ting-Yong Li; Bin Zhang; Wenbin Wu (CATENA, 2024)

Recent advances in SERS-based immunochromatographic assay for pathogenic microorganism diagnosis: A review - Qing Yu; Ting Wu; Benshun Tian; Jiaxuan Li; Yun Liu; Zelan Wu; Xiong Jin; Chaoguang Wang; Chongwen Wang; Bing Gu (Analytica Chimica Acta, 2024)

Long‐term warming increased carbon sequestration capacity in a humid subtropical forest - Xujun Liu; Zhiyang Lie; Peter B. Reich; Guoyi Zhou; Junhua Yan; Wenjuan Huang; Yingping Wang; Josep Peñuelas; David T. Tissue; Mengdi Zhao; Ting Wu; Donghai Wu; et al. (Global Change Biology, 2024)
Tropical and subtropical forests play a crucial role in global carbon (C) pools, and their responses to warming can significantly impact C‐climate feedback and predictions of future global warming. Despite earth system models projecting reductions in land C storage with warming, the magnitude of this response varies greatly between models, particularly in tropical and subtropical regions. Here, we conducted a field ecosystem‐level warming experiment in a subtropical forest in southern China, by translocating mesocosms (ecosystem composed of soils and plants) across 600 m elevation gradients with temperature gradients of 2.1°C (moderate warming), to explore the response of ecosystem C dynamics of the subtropical forest to continuous 6‐year warming. Compared with the control, the ecosystem C stock decreased by 3.8% under the first year of 2.1°C warming; but increased by 13.4% by the sixth year of 2.1°C warming. The increased ecosystem C stock by the sixth year of warming was mainly attributed to a combination of sustained increased plant C stock due to the maintenance of a high plant growth rate and unchanged soil C stock. The unchanged soil C stock was driven by compensating and offsetting thermal adaptation of soil microorganisms (unresponsive soil respiration and enzyme activity, and more stable microbial community), increased plant C input, and inhibitory C loss (decreased C leaching and inhibited temperature sensitivity of soil respiration) from soil drying. These results suggest that the humid subtropical forest C pool would not necessarily diminish consistently under future long‐term warming. We highlight that differential and asynchronous responses of plant and soil C processes over relatively long‐term periods should be considered when predicting the effects of climate warming on ecosystem C dynamics of subtropical forests.

Trade‐off in the partitioning of recent photosynthate carbon under global change - Fangping Li; Ting Qing; Fuzhong Wu; Kai Yue; Jingjing Zhu; Xiangyin Ni (Global Change Biology, 2024)
There may be trade‐offs in the allocation patterns of recent photosynthetic carbon (RPC) allocation in response to environmental changes, with a greater proportion of RPC being directed towards compartments experiencing limited resource availability. Alternatively, the allocation of RPC could shift from sources to sinks as plants processing excess photosynthates. It prompts the question: Does the pattern of RPC allocation vary under global changes? If so, is this variation driven by optimal or by residual C allocation strategies? We conducted a meta‐analysis by complicating 273 pairwise observations from 55 articles with 13 C or 14 C pulse or continuous labeling to assess the partitioning of RPC in biomass (leaf, stem, shoot, and root), soil pools (soil organic C, rhizosphere, and microbial biomass C) and CO 2 fluxes under elevated CO 2 (eCO 2 ), warming, drought and nitrogen (N) addition. We propose that the increased allocation of RPC to belowground under sufficient CO 2 results from the excretion of excess photosynthates. Warming led to a significant reduction in the percentage of RPC allocated to shoots, alongside an increase in roots allocation, although this was not statistically significant. This pattern is due to the reduced water availability resulting from warming. In conditions of drought, there was a notable increase in the partitioning of RPC to stems (+7.25%) and roots (+36.38%), indicative of a greater investment of RPC in roots for accessing water from deeper soil. Additionally, N addition led to a heightened allocation of RPC in leaves (+10.18%) and shoots (+5.78%), while reducing its partitioning in soil organic C (−8.92%). Contrary to the residual C partitioning observed under eCO 2 , the alterations in RPC partitioning in response to warming, drought, and N supplementation are more comprehensively explained through the lens of optimal partitioning theory, showing a trade‐off in the partitioning of RPC under global change.

Chinese perspectives on aquaculture careers: Insights from post‐graduate students and early career researchers - Caixia Wu; Changxu Sui; Chenxiang Zhang; Manxi Zhao; Ting Xu; Zhijie Shi; Yueru Li; Giovanni M. Turchini (Reviews in Aquaculture, 2024)

Design, Synthesis, and Cellular Imaging Application of a Fluorescent Probe Based on Fluoride Ion-Induced Cyclization of Phenothiazine Derivatives - Tingting Feng; Jiaxue Yang; San Tu; Ting Yang; Ting Wu; Wenqiang Zhu; Yi Le; Li Liu (Journal of Fluorescence, 2023)

The dual effect of disodium anthraquinone-2,6-disulfonate (AQDS) on the Cr(VI) removal by biochar: The enhanced electron transfer and the inhibited adsorption - Xue Wang; Peng Zhang; Meixuan Wu; Ting He; Can Li; Lijuan Liu; Shunling Li; Zhaofeng Chang; Di Lang; Wei Du; Hao Li; Bo Pan (Chemosphere, 2023)

Mitochondrial transplantation inhibits cholangiocarcinoma cells growth by balancing oxidative stress tolerance through PTEN/PI3K/AKT signaling pathway - Xiaocong Liu; Yuanyuan Zhang; Xiaoyan Yang; Yan Zhang; Yulan Liu; Li Wang; Ting Yi; Jing Yuan; Wu Wen; Yi Jian (Tissue and Cell, 2023)

CREB1 alleviates the apoptosis and potentiates the osteogenic differentiation of zoledronic acid-treated human periodontal ligament stem cells via up-regulating VEGF - Yao Duan; Chanyuan Jin; Yuwei Wu; Yan Chen; Minjuan Zhang; Jun Qian; Ting Shuai; Jian Li; Huimin Chen; Dan Li (Tissue and Cell, 2023)

Enhancing microbial salt tolerance through low-voltage stimulation for improved p-chloronitrobenzene (p-CNB) removal in high-salinity wastewater - Long Chen; Li-Ting Zhou; Yang-Cheng Ding; Di Wu; Hua-Jun Feng (Science of The Total Environment, 2023)

Characteristics and potential human health risks of microplastics identified in typical clams from South Yellow Sea Mudflat - Qingyuan Guo; Cheng Ding; Zhaoxia Li; Xiao Chen; Jinling Wu; Xuan Li; Jianwei Yu; Chunmiao Wang; Feng Liang; Ting Chen; Bairen Yang; Tianming Chen (Science of The Total Environment, 2023)

Intraspecific variations of leaf hydraulic, economic, and anatomical traits in Cinnamomum camphora along an urban-rural gradient - Cheng Zhang; Nuo Huang; Fengyu Zhang; Ting Wu; Xianjin He; Jianan Wang; Yiyong Li (Science of The Total Environment, 2023)

A new Trapa from the middle Miocene of Zhangpu, Fujian, southeastern China - Xie-Ting Wu; Zi-Xi Wang; Jun-Wu Shu; Su-Xin Yin; Li-Mi Mao; Gong-Le Shi (Palaeoworld, 2023)

The treatment of As(III)-contaminated water by using granular Fe-Mn-Cu composite oxide: Removing As(III) via the oxidation-adsorption process and handling the release of manganese ions - Rong Liu; Kun Wu; Birong Miao; Xuan Sun; Angzhen Li; Ting Liu; Changhui Duan; Zhihua Li (Journal of Water Process Engineering, 2023)

Fabrication of double-shell CuOx@Fe3O4 hollow spheres for efficient adsorption removal of tetracycline and oxytetracycline from water - Kun Wu; Chaonan Tao; Chuanqiao Zhang; Zebiao Hao; Angzhen Li; Changhui Duan; Ting Liu; Zhihua Li (Journal of Water Process Engineering, 2023)

Neuroprotective mechanism of walnut-derived peptide via C1q-mediated synaptic plasticity in HT22 cells - Yihang Xing; Dingwen Zhang; Li Fang; Ji Wang; Chunlei Liu; Dan Wu; Yiding Yu; Ting Zhang; Xiyan Wang; Weihong Min (Food Bioscience, 2023)

Artemisia selengensis Turcz. leaves extract ameliorates hyperuricemia in mice by inhibiting hepatic xanthine oxidase activity, modulating renal uric acid transporters, and improving metabolic disorders - Lin Xiang; Yuting Huang; Rong Li; Yexing Tao; Ting Wu; Siyi Pan; Xiaoyun Xu (Food Bioscience, 2023)

Transformation from Knudsen diffusion to facilitated diffusion for CO2 in confined mass transfer channels of polyimide mixed matrix membranes - Ting Wang; Ke Zhang; Shi-wen Du; Li-guang Wu; Chun-juan Li; Hua-li Chen; Hai-Chang Guo (Chemical Engineering Journal, 2023)

Research Progress on TRPA1 in Diseases - Jiajing Li; Hongfei Zhang; Qian Du; Junyu Gu; Jiangbo Wu; Qi Liu; Zhuo Li; Ting Zhang; Jingyu Xu; Rui Xie (The Journal of Membrane Biology, 2023)
For a long time, the physiological activity of TRP ion channels and the response to various stimuli have been the focus of attention, and the physiological functions mediated by ion channels have subtle links with the occurrence of various diseases. Our group has been engaged in the study of ion channels. In recent years, the report rate of TRPA1 , the only member of the TRPA subfamily in the newly described TRP channel, has been very high. TRPA1 channels are not only abundantly expressed in peptidergic nociceptors but are also found in many nonneuronal cell types and tissues, and through the regulation of Ca 2+ influx, various neuropeptides and signaling pathways are involved in the regulation of nerves, respiration, circulation, and various diseases and inflammation throughout the body. In this review, we mainly summarize the effects of TRPA1 on various systems in the body, which not only allows us to have a more systematic and comprehensive understanding of TRPA1 but also facilitates more in-depth research on it in the future. Graphical Abstract

Metabolome and Transcriptome Association Analysis Reveals the Link Between Pigmentation and Nutrition Utilization in the Juveniles of Sea Cucumber Holothuria leucospilota - Jiasheng Huang; Zixuan E; Wenjie Pan; Zhi Li; Tiehao Lin; Chunhua Ren; Peng Luo; Bo Ma; Yang Liu; Xugan Wu; Chaoqun Hu; Xiao Jiang; et al. (Marine Biotechnology, 2023)

17β-Estradiol Mediates Staphylococcus aureus Adhesion in Vaginal Epithelial Cells via Estrogen Receptor α-Associated Signaling Pathway - Lina Yan; Can Rui; Bin Zhuang; Xia Liu; Ting Luan; Lisha Jiang; Zhiyong Dong; Qing Wang; Aiwen Wu; Ping Li; Xinyan Wang; Xin Zeng (Current Microbiology, 2023)

Factors affecting the accumulation of organotins by wild fish: A case study in the Three Gorges Reservoir, China - Jun-min Gao; Jia You; Jing-cheng Wu; Jin-song Guo; Ping-ting Fu; Li-xia Zhang (Environmental Science and Pollution Research, 2023)

Socioeconomic status, lifestyle and risk of incident dementia: a prospective cohort study of 276730 participants - Ya-Nan Ou; Yan-Bo Zhang; Yu-Zhu Li; Shu-Yi Huang; Wei Zhang; Yue-Ting Deng; Bang-Sheng Wu; Lan Tan; Qiang Dong; An Pan; Ren-Jie Chen; Jian-Feng Feng; et al. (GeroScience, 2023)

Application of TCN-biGRU neural network in $$ PM_{2.5}$$ concentration prediction - Ting Shi; Pengyu Li; Wu Yang; Ailin Qi; Junfei Qiao (Environmental Science and Pollution Research, 2023)

Ag/TiO2 nanohybrids induce fibrosis-related epithelial-mesenchymal transition in lung epithelial cells and the influences of silver content and silver particle size - Xiaoquan Huang; Congcong Li; Tingting Wei; Na Liu; Lingyue Zou; Changcun Bai; Yongshuai Yao; Zhihui Wang; Yuying Xue; Tianshu Wu; Ting Zhang; Meng Tang (Science of The Total Environment, 2023)

A novel fusion framework embedded with zero-shot super-resolution and multivariate autoregression for precipitable water vapor across the continental Europe - Jinhua Wu; Linyuan Xia; Ting On Chan; Joseph Awange; Peng Yuan; Bo Zhong; Qianxia Li (Remote Sensing of Environment, 2023)

Integrating suitable habitat dynamics under typical hydrological regimes as guides for the conservation and restoration of different waterbird groups - Pingyang Zhang; Siqi Zhang; Yeai Zou; Ting Wu; Feng Li; Zhengmiao Deng; Hong Zhang; Yucheng Song; Yonghong Xie (Journal of Environmental Management, 2023)

Metagenomics insights into high-rate nitrogen removal from municipal wastewater by integrated nitrification, partial denitrification and Anammox at an extremely short hydraulic retention time - Junjiang Chen; Xiaonong Zhang; Li Zhou; Zixuan Zhu; Zhiqiang Wu; Kangyu Zhang; Yiwen Wang; Ting Ju; Xu Ji; Da Jin; Peng Wu; Xingxing Zhang (Bioresource Technology, 2023)

Ultrafine particles in urban settings: A combined study of volatility and effective density revealed by VT-DMA-APM - Che-An Wu; Yu-Ting Chen; Li-Hao Young; Po-Kai Chang; Li-Ti Chou; Albert Y. Chen; Ta-Chih Hsiao (Atmospheric Environment, 2023)

Improvement of Learning and Memory by Elevating Brain D-Aspartate in a Mouse Model of Fragile X Syndrome - Yu-Jiao Li; Kun Zhang; Ting Sun; Yan-Yan Guo; Qi Yang; Shui-Bing Liu; Yu-Mei Wu; Ming-Gao Zhao (Molecular Neurobiology, 2023)
Fragile X syndrome (FXS) is an inherited human mental retardation that arises from expansion of a CGG repeat in the Fmr1 gene, causing loss of the fragile X mental retardation protein (FMRP). It is reported that N-methyl-D-aspartate receptor (NMDAR)-mediated facilitation of long-term potentiation (LTP) and fear memory are impaired in Fmr1 knockout (KO) mice. In this study, biological, pharmacological, and electrophysiological techniques were performed to determine the roles of D-aspartate (D-Asp), a modulator of NMDAR, and its metabolizing enzyme D-aspartate oxidase (DDO) in Fmr1 KO mice. Levels of D-Asp were decreased in the medial prefrontal cortex (mPFC ); however, the levels of its metabolizing enzyme DDO were increased. Electrophysiological recordings indicated that oral drinking of D-Asp recovered LTP induction in mPFC from Fmr1 KO mice. Moreover, chronic oral administration of D-Asp reversed behavioral deficits of cognition and locomotor coordination in Fmr1 KO mice. The therapeutic action of D-Asp was partially through regulating functions of NMDARs and mGluR5/mTOR/4E-BP signaling pathways. In conclusion, supplement of D-Asp may benefit for synaptic plasticity and behaviors in Fmr1 KO mice and offer a potential therapeutic strategy for FXS.

Long-term field translocation differentially affects arbuscular mycorrhizal and ectomycorrhizal trees in a sub-tropical forest - Ting Wu; David T Tissue; Wei Su; Xu Li; Shimin Yang; Xujun Liu; Yue Liu; Zhiyang Lie; Shuyidan Zhou; Ze Meng; Junhua Yan; Xuli Tang; et al. (Agricultural and Forest Meteorology, 2023)

Ventilation arrangement evaluation and proactive goaf inertisation for spontaneous combustion and gas explosion management during longwall panel sealing-off process - Ming Qiao; Ting Ren; Jon Roberts; Zhongbei Li; Jianming Wu (Environmental Science and Pollution Research, 2023)

Biofilm bioactivity affects nitrogen metabolism in a push-flow microalgae-bacteria biofilm reactor during aeration-free greywater treatment - Beibei Wu; Ting Ran; Sibei Liu; Qian Li; Xiaocai Cui; Yun Zhou (Water Research, 2023)

Breaking the salty spell: Understanding action mechanism of melatonin and beneficial microbes as nature's solution for mitigating salt stress in soybean - Zhenyu Fan; Feifei He; Ting Wu; Bowen Li; Jin Xiao; Zhigang Wang (South African Journal of Botany, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Carbon storage capacity of Castanopsis hystrix plantations at different stand–ages in South China - Xu Li; Luis Carlos Ramos Aguila; Jinchu Luo; Yue Liu; Ting Wu; Zhiyang Lie; Xujun Liu; Yan Cheng; Fen Jiang; Juxiu Liu (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

MdGRF11-MdARF19-2 module acts as a positive regulator of drought resistance in apple rootstock - Lizhong Jiang; Jiahong Lv; Keting Li; Longmei Zhai; Yue Wu; Ting Wu; Xinzhong Zhang; Zhenhai Han; Yi Wang (Plant Science, 2023)

Impurity removal of acid leachates from rare earth slag with sodium hydroxide and ammonium bicarbonate: Mechanism and efficiency optimization - Yilin Wu; Shirong Zhang; Guiyin Wang; Ting Li; Xiaoxun Xu; Yulin Pu; Wei Zhou; Yun Li; Yongxia Jia (Journal of Cleaner Production, 2023)

Sulfur-doped Sb4Mo10O31 bimetallic sulfur-oxide catalyst for highly efficient reduction of toxic organic and hexavalent chromium under dark - Ping Li; Qinhan Wu; Qiao Ji; Adugna Boke Abdeta; Dong-Hau Kuo; Ting Huang; Hanya Zhang; Osman Ahmed Zelekew; Jinguo Lin; Xiaoyun Chen (Journal of Environmental Chemical Engineering, 2023)

Per- and polyfluoroalkyl substances in ambient fine particulate matter in the Pearl River Delta, China: Levels, distribution and health implications - Lu-Sheng Liu; Yu-Ting Guo; Qi-Zhen Wu; Mohammed Zeeshan; Shuang-Jian Qin; Hui-Xian Zeng; Li-Zi Lin; Wei-Chun Chou; Yun-Jiang Yu; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2023)

Two-point-one-line modularized strategy combined with Holliday-junction button probes for multiloci SNPs long-range distribution analysis - Wang Luo; You Wu; Xueping Chen; Li Zhang; Li Wang; Dan Bai; Qian Liu; Ting Wang; Hongyan Yu; Yaxing Xie; Yixin Fu; Zhongzhong Wang; et al. (Chemical Engineering Journal, 2023)

Biotransformation of nitrogen and tetracycline by counter-diffusion biofilm system: Multiple metabolic pathways, mechanism, and slower resistance genes enrichment - Ting Li; Xiwei Cao; Ziqing Wu; Jun Liu; Boyang Hu; Hao Chen; Baoan Li (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Single-molecule recognition of Nucleolin and the interactions with DNA/RNA G-quadruplexes via nanopore decoding - Zhong Wang; Fupeng Qin; Ji Wu; Wenhao Ma; Rongjie Li; Ting Weng; Bohua Yin; Liang Wang; Deqiang Wang; Liyuan Liang (Chemical Engineering Journal, 2023)

Size-dependent chemical composition of atmospheric nanoparticles in urban Beijing during springtime - Yan Chen; Chenjuan Deng; Ting Lei; Junling Li; Chaofan Lian; Yiran Li; Jun Zheng; Jun Zhao; Dongbin Wang; Zhijun Wu; Lin Wang; Lei Li; et al. (Atmospheric Environment, 2023)

Genome-wide identification of GH9 gene family and the assessment of its role during fruit abscission zone formation in Vaccinium ashei - Yingying Wang; Yue Xu; Fangfang Liao; Ting Li; Xiaolong Li; Boping Wu; Seung-Beom Hong; Kai Xu; Yunxiang Zang; Weiwei Zheng (Plant Cell Reports, 2023)

Molecular weight of dissolved organic matter determines its interactions with microbes and its assembly processes in soils - Pengfa Li; Meng Wu; Ting Li; Alex J. Dumbrell; Muhammad Saleem; Lu Kuang; Lu Luan; Shuang Wang; Zhongpei Li; Jiandong Jiang (Soil Biology and Biochemistry, 2023)

Genome-wide analysis of the MdZR gene family revealed MdZR2.2-induced salt and drought stress tolerance in apple rootstock - Keting Li; Longmei Zhai; Sitong Fu; Ting Wu; Xinzhong Zhang; Xuefeng Xu; Zhenhai Han; Yi Wang (Plant Science, 2023)

Geochemical characteristics of the Chang 7 Member in the southwestern Ordos Basin, China: the influence of sedimentary environment on the organic matter enrichment - Chen Li; Shi-Jia Chen; Jian-Bo Liao; Yu-Ting Hou; Jian Yu; Guang-Lin Liu; Kun Xu; Xue-Ting Wu (Palaeoworld, 2023)

New mechanisms of biochar-assisted vermicomposting by recognizing different active di-(2-ethylhexyl) phthalate (DEHP) degraders across pedosphere, charosphere and intestinal sphere - Shuwen Luo; Zhen Zhen; Tingting Teng; Weilong Wu; Guiqiong Yang; Changhong Yang; Huijun Li; Fengcheng Huang; Ting Wei; Zhong Lin; Dayi Zhang (Journal of Hazardous Materials, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

A novel bacterial combination for efficient degradation of polystyrene microplastics - Peng Xiang; Yunfeng Zhang; Ting Zhang; Qian Wu; Changsong Zhao; Qiang Li (Journal of Hazardous Materials, 2023)

Surface engineering of Al2O3 nanotubes by ureasolysis method for activating persulfate degradation of antibiotics - Zheng-Wu Wang; Mei-Yun Xiao; Jun-Feng Tang; Ming-Qian Li; Xia-Yin Yin; Ting Wang; Yi-Zhou Zhu; Dai-Wen Pang; He-Fang Wang (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Catalytic co-liquefaction of microalgae + corn straw over K3PO4+γ-Al2O3 supported Fe and Ni mono- / bimetallic in-situ composite catalysts for the production of liquid biofuel - Xin Ding; Ting Li; Junqian Wang; Le Wu; Lan Zheng; Yuqi Wang (Chemical Engineering Journal, 2023)

Ultrasound-driven nanoreactor with USP39 ShRNAi-intensified ferroptosis for synergistic sono-chemodynamic therapy - Zhiyu Zhao; Jiajing Liu; Yanjie Wu; Xiaochen Liang; Yijia Zhang; Tingting Li; Yunjie Wang; Yi Luo; Shengyu Wang; Gang Song; Ting Wu; Shaoliang Zhang; et al. (Chemical Engineering Journal, 2023)

Overexpression of Taetr1-1 promotes enhanced seed dormancy and ethylene insensitivity in wheat - Jun Wei; Xing-ting Wu; Xiao-ying Li; Wim J. J. Soppe; Hong Cao; Yong-xiu Liu (Planta, 2023)

Orally Induced High Serum Level of Trimethylamine N-oxide Worsened Glial Reaction and Neuroinflammation on MPTP-Induced Acute Parkinson’s Disease Model Mice - Chen-Meng Qiao; Wei Quan; Yu Zhou; Gu-Yu Niu; Hui Hong; Jian Wu; Li-Ping Zhao; Ting Li; Chun Cui; Wei-Jiang Zhao; Yan-Qin Shen (Molecular Neurobiology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

MiR-425-5p suppression of Crebzf regulates oocyte aging via chromatin modification - Kadiliya Jueraitetibaike; Ting Tang; Rujun Ma; Shanmeizi Zhao; Ronghua Wu; Yang Yang; Xuan Huang; Xi Cheng; Cheng Zhou; Hong Zhang; Lu Zheng; Xie Ge; et al. (GeroScience, 2023)
Female infertility due to declining oocyte quality with age remains a significant challenge for patients and physicians, despite extensive research efforts. Recent studies suggest that microRNAs (miRNAs), which respond to various stressors in the aging process, may provide a promising solution. With the approval of small RNA drugs for clinical use, miRNA-based treatment of oocyte aging appears to be a viable option. Through high-throughput sequencing, miR-425-5p was identified as the only miRNA elevated under natural aging and oxidative stress. Microinjection of inhibitors to inhibit miR-425-5p effectively improved compromised phenotypes of old oocytes in vitro. Further investigation revealed that Crebzf acts as a mediator of miR-425-5p 's age-related functions in old oocytes. In vivo treatment with miR-425-5p antagomirs significantly improved impaired oocyte development in reproductively old females by targeting Crebzf . Single-cell RNA sequencing revealed that Crebzf plays a vital role in regulating mRNAs targeting histone H3, trimethylated lysine 4 (H3K4me3), a crucial marker for transcriptional silencing. Overexpression of miR-425-5p could hinder oocyte maturation by downregulating Crebzf expression and disrupting transcriptional regulation. Our findings provide new insights into the potential of miR-425-5p antagomirs as a treatment for female infertility and highlight an elegant mechanism by which miR-425-5p inhibition of Crebzf inhibits a developmental switch in GV oocytes by regulating a group of histone methyltransferase mRNAs.

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Jinggangmycin stimulates reproduction and increases CHCs-dependent desiccation tolerance in Drosophila melanogaster - Wei Dong; Wen-Jun Wu; Chen-Yang Song; Ting Li; Jian-Zhen Zhang (Pesticide Biochemistry and Physiology, 2023)

Construction of PES mixed matrix membranes incorporating ZnFe2O4 @MXene composites with high permeability and antifouling performance - Ping Zhou; Ting Wang; Chun-Hui Du; Guo-qin Wang; Li-guang Wu; Xiao-jia Jiang; Hai-Chang Guo (Journal of Environmental Chemical Engineering, 2023)

Synthetic phylogenetically diverse communities promote denitrification and stability - Min Zhou; Xiaotong Guan; Ting Deng; Ruiwen Hu; Lu Qian; Xueqin Yang; Bo Wu; Juan Li; Qiang He; Longfei Shu; Qingyun Yan; Zhili He (Environmental Research, 2023)

Mechanism study of synergistic effect of organic and inorganic foulants in membrane distillation - Haifu Gao; Ting Dai; Jiahui Li; Ziping Song; Wangwang Guan; Yue Jia; Xiaolong Lu; Zongli Xie; Chunrui Wu; Jianhua Zhang (Desalination, 2023)

Population structure and genetic diversity of Triticum araraticum Jakubz. and Triticum timopheevii Zhuk. - Ting Peng; Xiaomei Jiang; Dinghao Wang; Minghu Zhang; Xin Liu; Ming Hao; Wei Li; Dengcai Liu; Bo Jiang; Lin Huang; Shunzong Ning; Zhongwei Yuan; et al. (Genetic Resources and Crop Evolution, 2023)

Quantifying source effects based on rainwater δ18O from 10-year monitoring records in Southwest China - Yan-Xia Xue; Jian Zhang; Zhen Su; Yao Wu; Qi-sheng Liang; Ming-Qiang Liang; Xiang-Zhuo Liu; Chao-Jun Chen; Hai-Ying Qiu; Jun-Yun Li; Ting-Yong Li (Applied Geochemistry, 2023)

Hsa-miR-195-5p Inhibits Autophagy and Gemcitabine Resistance of Lung Adenocarcinoma Cells via E2F7/CEP55 - Linhai Fu; Zhupeng Li; Yuanlin Wu; Ting Zhu; Zhifeng Ma; Lingjun Dong; Jianyi Ding; Chu Zhang; Guangmao Yu (Biochemical Genetics, 2023)

A systematic review: on the mercaptoacid metabolites of acrylamide, N-acetyl-S-(2-carbamoylethyl)-L-cysteine - Fang-Fang Zhao; Xiao-Li Wang; Ya-Ting Lei; Hong-Qiu Li; Zhi-Ming Li; Xiao-Xiao Hao; Wei-Wei Ma; Yong-Hui Wu; Sheng-Yuan Wang (Environmental Science and Pollution Research, 2023)

A new butenolide with antifungal activity from solid co-cultivation of Irpex lacteus and Nigrospora oryzae - Ya-Mei Wu; Xue-Qiong Yang; Jing-Xin Chen; Ting Wang; Tai-Ran Li; Fan-Rong Liao; Run-Tong Liu; Ya-Bin Yang; Zhong-Tao Ding (Natural Product Research, 2023)

Change of tetracycline speciation and its impacts on tetracycline removal efficiency in vermicomposting with epigeic and endogeic earthworms - Zhong Lin; Yijie Chen; Gaoyang Li; Ting Wei; Huijun Li; Fengcheng Huang; Weijian Wu; Weijian Zhang; Lei Ren; Yanqiu Liang; Zhen Zhen; Dayi Zhang (Science of The Total Environment, 2023)

Hypothermic neuroprotection by targeted cold autologous blood transfusion in a non-human primate stroke model - Jian Chen; Shuaili Xu; Hangil Lee; Longfei Wu; Xiaoduo He; Wenbo Zhao; Mo Zhang; Yanhui Ma; Yuchuan Ding; Yongjuan Fu; Chuanjie Wu; Ming Li; et al. (Science Bulletin, 2023)

Microbial community composition and cooccurrence patterns driven by co-contamination of arsenic and antimony in antimony-mining area - Wei-song Pan; Qi Zou; Min Hu; Wai-chin Li; Xiao-ran Xiong; Yan-ting Qi; Chuan Wu (Journal of Hazardous Materials, 2023)

The bound polyphenols of foxtail millet (Setaria italica) inner shell inhibit breast cancer by promoting lipid accumulation-induced autophagic death - Li-chao Zhang; Ya-ning Liu; Xiao-qin La; Shuai-tao Li; Li-na Wen; Ting Liu; Han-qing Li; Ai-ping Li; Haitao Wu; Chang-xin Wu; Zhuo-yu Li (Food and Chemical Toxicology, 2023)

Insights into the Involvement and Therapeutic Target Potential of the Dopamine System in the Posttraumatic Stress Disorder - Meng-Nan Liu; Xiao-Yu Tian; Ting Fang; Ning Wu; Hong Li; Jin Li (Molecular Neurobiology, 2023)

Correction: Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)

Application of the metal ions as potential population biomarkers for wastewater-based epidemiology: estimating tobacco consumption in Southern China - Lei Xu; Yu-ting Lu; Dong-feng Wu; Xuan Li; Min Song; Tai-jun Hang; Meng-xiang Su (Environmental Geochemistry and Health, 2023)

Tracing the future of epidemics: Coincident niche distribution of host animals and disease incidence revealed climate‐correlated risk shifts of main zoonotic diseases in China - Bo Cao; Chengke Bai; Kunyi Wu; Ting La; Yiyang Su; Lingyu Che; Meng Zhang; Yumeng Lu; Pufan Gao; Jingjing Yang; Ying Xue; Guishuang Li (Global Change Biology, 2023)
Climate has critical roles in the origin, pathogenesis and transmission of infectious zoonotic diseases. However, large‐scale epidemiologic trend and specific response pattern of zoonotic diseases under future climate scenarios are poorly understood. Here, we projected the distribution shifts of transmission risks of main zoonotic diseases under climate change in China. First, we shaped the global habitat distribution of main host animals for three representative zoonotic diseases (2, 6, and 12 hosts for dengue, hemorrhagic fever, and plague, respectively) with 253,049 occurrence records using maximum entropy (Maxent) modeling. Meanwhile, we predicted the risk distribution of the above three diseases with 197,098 disease incidence records from 2004 to 2017 in China using an integrated Maxent modeling approach. The comparative analysis showed that there exist highly coincident niche distributions between habitat distribution of hosts and risk distribution of diseases, indicating that the integrated Maxent modeling is accurate and effective for predicting the potential risk of zoonotic diseases. On this basis, we further projected the current and future transmission risks of 11 main zoonotic diseases under four representative concentration pathways (RCPs) (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) in 2050 and 2070 in China using the above integrated Maxent modeling with 1,001,416 disease incidence records. We found that Central China, Southeast China, and South China are concentrated regions with high transmission risks for main zoonotic diseases. More specifically, zoonotic diseases had diverse shift patterns of transmission risks including increase, decrease, and unstable. Further correlation analysis indicated that these patterns of shifts were highly correlated with global warming and precipitation increase. Our results revealed how specific zoonotic diseases respond in a changing climate, thereby calling for effective administration and prevention strategies. Furthermore, these results will shed light on guiding future epidemiologic prediction of emerging infectious diseases under global climate change.

Ultrasensitive and simultaneous monitoring of multiple small-molecule pollutants on an immunochromatographic strip with multilayered film-like fluorescent tags - Wenqi Wang; Qing Yu; Shuai Zheng; Jiaxuan Li; Ting Wu; Shu Wang; Chongwen Wang; Bing Gu (Science of The Total Environment, 2023)

Hyperspectral imaging technique supports dynamic emission inventory of coal-fired power plants in China - Jinan Lin; Chengzhi Xing; Cheng Liu; Wei Tan; Wei Wang; Peng Wu; Chuan Lu; Qihua Li; Ting Liu (Science Bulletin, 2023)

CircFhit Modulates GABAergic Synaptic Transmission via Regulating the Parental Gene Fhit Expression in the Spinal Dorsal Horn in a Rat Model of Neuropathic Pain - Ting Xu; Zhen-Yu Li; Meng Liu; Su-Bo Zhang; Huan-Huan Ding; Jia-Yan Wu; Su-Yan Lin; Jun Liu; Jia-You Wei; Xue-Qin Zhang; Wen-Jun Xin (Neuroscience Bulletin, 2023)

GSH-Dependent PTMs of Proteins Differ Significantly Between Ontogenetic Phases of Apple Trees - Jing Yang; Qingbo Zheng; Yi Wang; Ting Wu; Wei Li; Changpeng Qiu; Xuefeng Xu; Xi Zhang; Zhenhai Han; Xinzhong Zhang (Journal of Plant Growth Regulation, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Bioinformatic and functional analysis of OsDHN2 under cadmium stress - Wen-jun Jiang; Meng-ting Wang; Zhi-ye Du; Jia-hao Li; Yang Shi; Xin Wang; Long-ying Wu; Ji Chen; Min Zhong; Ju Yang; Bin-hua Hu; Jin Huang (Functional & Integrative Genomics, 2023)

Target-independent hybridization chain reaction-fluorescence resonance energy transfer for sensitive assay of ctDNA based on Cas12a - Xuelan Wu; Ting Ju; Zeyang Li; Jingwen Li; Xingwei Zhai; Kun Han (Analytica Chimica Acta, 2023)

Geographic variation of litter chemistry and palatability in an invasive plant versus its native competitor - Yaolin Guo; Youzheng Zhang; Jihua Wu; Christina L. Richards; Oliver Bossdorf; Bo Li; Rui‐Ting Ju (Journal of Biogeography, 2023)
Aim Latitudinal variation in biotic interactions is recognized as a driver underlying variation in plant invasion success and therefore an important issue in conservation biogeography. However, previous studies have mainly focused on interactions between living plants and herbivores, whereas litter traits and detritivory have been hardly studied along latitude or compared between native and invasive plants. Our aim was to compare latitudinal variation in leaf litter chemistry and palatability to detritivores between invasive and native plants, and investigate which chemical traits determine detritivory and whether they are climate‐driven. Location China. Taxa Spartina alterniflora , Phragmites australis , Porcellio laevis , Chiromantes dehaani . Methods We combined field surveys with laboratory experiments to compare latitudinal variation in litter chemistry between the widespread invasive Spartina alterniflora and its native competitor Phragmites australis across their co‐occurring range (20.9–40.7° N, ~2200 km). For both species, we examined litter palatability to two common detritivores ( Porcellio laevis and Chiromantes dehaani ) along the same latitude. We also analysed relationships among climate, litter traits and detritivory. Results In five of nine litter traits, we found latitudinal clines, with little difference between the two plant species in how they responded across the gradient. Litter palatability decreased with increasing latitude, but was generally higher in Spartina than Phragmites . Two key litter traits (C:P ratio and flavonoid content) were significantly associated with temperature of origin and with detritivory. Main Conclusions There were geographic clines in litter traits and palatability, with strong links between climate, litter chemistry and detritivory, in both Spartina and Phragmites . Spartina litter, however, was more rapidly decomposed by detritivores, which could create positive feedbacks, and contributes to the successful Spartina invasion along China's coast. Future ecological restoration projects should therefore dispose Spartina plant tissue or litter off‐site, to reduce the competitiveness of Spartina and support the conservation of native Phragmites .

Watershed urbanization dominated the spatiotemporal pattern of riverine methane emissions: Evidence from montanic streams that drain different landscapes in Southwest China - Xianxiang Li; Yixin He; Xiaofeng Wang; Huai Chen; Tingting Liu; Yizi Que; Xingzhong Yuan; Shengnan Wu; Ting Zhou (Science of The Total Environment, 2023)

Atomic-level chemical reaction promoting external quantum efficiency of organic photomultiplication photodetector exceeding 108% for weak-light detection - Linlin Shi; Yizhi Zhu; Guohui Li; Ting Ji; Wenyan Wang; Ye Zhang; Yukun Wu; Yuying Hao; Kaiying Wang; Jun Yuan; Yingping Zou; Beng S. Ong; et al. (Science Bulletin, 2023)

Brt9SIDA/IDALs as peptide signals mediate diverse biological pathways in plants - Pingyu Wang; Ting Wu; Chen Jiang; Baowen Huang; Zhengguo Li (Plant Science, 2023)

Applications of vacancy defect engineering in persulfate activation: Performance and internal mechanism - Ting Zhang; Shuang Wu; Ning Li; Guanyi Chen; Li’an Hou (Journal of Hazardous Materials, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

Fabrication and characterization of self-assembled whey protein isolate/short linear glucan core–shell nanoparticles for sustained release of curcumin - Xiaojing Li; Ting Xu; Caie Wu; Gongjian Fan; Tingting Li; Yaosong Wang; Dandan Zhou (Food Chemistry, 2023)

Development and characterization of antioxidant composite films based on starch and gelatin incorporating resveratrol fabricated by extrusion compression moulding - Hejun Wu; Ting Li; Lu Peng; Jie Wang; Yuixiao Lei; Shasha Li; Qingye Li; Xiangyang Yuan; Man Zhou; Zhiqing Zhang (Food Hydrocolloids, 2023)

Photo-Fenton catalytic anti-fouling membranes for efficient elimination of radionuclides and organic contaminants - Daping Ye; Qian Gao; Ting Li; Xilong Wu; Yundi Wu (Desalination, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Time-resolved ICP-MS analysis of mineral element contents and distribution patterns in spermatogenic cells of different types - Yinghui Wu; Yang Chao; Yueyue Miao; Yamei Li; Ting Xu; Shengqing Li; Jian Peng (Analytica Chimica Acta, 2023)

Rab7a-mTORC1 signaling-mediated cholesterol trafficking from the lysosome to mitochondria ameliorates hepatic lipotoxicity induced by aflatoxin B1 exposure - Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Lin Che; Ting-Yu Li; Su-Min Mo; Dong-Bei Guo; Zhong-Ning Lin; Yu-Chun Lin (Chemosphere, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Effect of corn straw or corncobs in total mixed ration during peri-puberty on testis development in Hu lambs - Wanhong Li; Jiamei Liu; Weiwei Wu; Ting Yao; Xiuxiu Weng; Xiangpeng Yue; Fadi Li (Theriogenology, 2023)

The role of reactive astrocytes in neurotoxicity induced by ultrafine particulate matter - Ben Li; Xiaohan Chang; Xiaomin Liang; Ting Liu; Yongmei Shen; Qianwen Zhang; Xiaohui Yang; Yi Lyu; Liangpo Liu; Jianquan Guo; Meiqiong Wu; Yi Gao; et al. (Science of The Total Environment, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

MdbZIP74 negatively regulates osmotic tolerance and adaptability to moderate drought conditions of apple plants - Qinyuan Zhu; Jiahong Lv; Yue Wu; Mengqun Peng; Xinyi Wu; Jie Li; Ting Wu; Xinzhong Zhang; Xuefeng Xu; Yi Wang; Yi Feng (Journal of Plant Physiology, 2023)

Introduction of multilayered magnetic core–dual shell SERS tags into lateral flow immunoassay: A highly stable and sensitive method for the simultaneous detection of multiple veterinary drugs in complex samples - Jian Tu; Ting Wu; Qing Yu; Jiaxuan Li; Shuai Zheng; Kezong Qi; Guohui Sun; Rui Xiao; Chongwen Wang (Journal of Hazardous Materials, 2023)

Insights into the pigment and non-pigment phenolic profile of polyphenol extracts of jujube peel and their antioxidant and lipid-lowering activities - Jin-Feng Dou; Cai-E Wu; Gong-Jian Fan; Ting-Ting Li; Xiao-Jing Li; Dan-Dan Zhou; Jin-Peng Zhu; Chun-Mei Li (Food Bioscience, 2023)

Prenatally VPA exposure is likely to cause autistic-like behavior in the rats offspring via TREM2 down-regulation to affect the microglial activation and synapse alterations - Lijuan Luo; Jie Chen; Qionghui Wu; Binlin Yuan; Chaoqun Hu; Ting Yang; Hua Wei; Tingyu Li (Environmental Toxicology and Pharmacology, 2023)

High-titer production of myo-inositol by a co-immobilized four-enzyme cocktail in biomimetic mineralized microcapsules - Pingping Han; Chun You; Yunjie Li; Ting Shi; Hong Wu; Yi-Heng P. Job Zhang (Chemical Engineering Journal, 2023)

Water-favored reaction mechanism for selective catalytic conversion of 2-methylfuran to 1,4-pentanediol - Min Wu; Ting Wang; Wenhui Li; Qin Zhang; Bin Zhang; Kaiqin Chen; Siyuan Peng; Guojia Li; Jinning Huang; Qiang Wang; Chuan Wang (Chemical Engineering Journal, 2023)

LncRNA PCAT6 promotes proliferation, migration, invasion, and epithelial-mesenchymal transition of lung adenocarcinoma cell by targeting miR-545-3p - Chuyi Yang; Hongyu Huang; Yongpeng Li; Ting Zhuo; Lu Zhu; Chenyang Luo; Yanbin Wu; Shouming Qin (Molecular Biology Reports, 2023)
Background Lung cancer is a high incidence cancer on a worldwide basis and has become a major public health problem. Lung adenocarcinoma (LUAD) makes up approximately half of all lung cancers and is a threat to human health. Long non-coding RNAs (lncRNAs) is an important regulator of the development and progression of lung adenocarcinoma. In this manuscript we examined the role and potential mechanism of lncRNA PCAT6 in the development of LUAD. Methods and results Differences in lncRNA PCAT6 levels between LUAD samples and normal samples were first explored in the GEPIA database. We found that lncRNA PCAT6 expression was elevated, which was also validated in lung adenocarcinoma tissues and cell lines. Using western blotting, CCK-8, EdU, wound healing and transwell assays, we found that knockdown of lncRNA PCAT6 inhibited EMT, proliferation, migration, and invasion of LUAD cells. We noted a predicted a binding site for lncRNA PCAT6 and miR-545-3p through conducting bioinformatic analyses, and their binding was subsequently verified by a dual-luciferase reporter assay. Rescue experiments confirmed that miR-545-3p inhibitor partially abolished the inhibition function of lncRNA PCAT6 knockdown on LUAD cells. In addition, we predicted the downstream target genes of miR-545-3p and verified them by RT-qPCR. We found that EGFR was reduced in the silence of lncRNA PCAT6 and upregulated after miR-545-3p inhibition. Conclusion This study demonstrates that lncRNA PCAT6 promotes a more aggressive LUAD phenotype by sponging miR-545-3p. This finding may provide new ideas for the treatment of lung cancer.

Effectiveness of Combined Exercise and Physiotherapy Intervention in Improving Functional Activity of Patients with Knee Osteoarthritis in Muslim Pray Movements - Rakhmad Rosadi; Po-Ting Wu; Yu-Lin You; Li-Chieh Kuo; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2023)

Altered microstructural pattern of the cortex and basal forebrain cholinergic system in wilson’s disease: an automated fiber quantification tractography study - Yutong Wu; Sheng Hu; Yi Wang; Ting Dong; Hongli Wu; Anqin Wang; Chuanfu Li; Hongxing Kan (Brain Imaging and Behavior, 2023)

Rapid prediction models for 3D geometry of landslide dam considering the damming process - Hao Wu; Ting-kai Nian; Zhi-gang Shan; Dong-yang Li; Xing-sen Guo; Xian-gang Jiang (Journal of Mountain Science, 2023)

Occurrence of antibiotic resistance genes carried by plastic waste from mangrove wetlands of the South China Sea - Ruikun Sun; Ting Li; Shijie Qiu; Yu Liu; Zijie Wu; Zhenqing Dai; Yuantao Liao; Xin Chen; Shuying Chen; Chengyong Li (Science of The Total Environment, 2023)

Predatory protists play predominant roles in suppressing soil-borne fungal pathogens under organic fertilization regimes - Peixin Ren; Anqi Sun; Xiaoyan Jiao; Ju-Pei Shen; Dan-Ting Yu; Fangfang Li; Bingxue Wu; Ji-Zheng He; Hang-Wei Hu (Science of The Total Environment, 2023)

Sonocatalytic degradation of tetracycline by BiOBr/FeWO4 nanomaterials and enhancement of sonocatalytic effect - Liang Xu; Xue-Qian Wu; Chun-Yu Li; Ni-Ping Liu; Hui-Li An; Wan-Ting Ju; Wen Lu; Bin Liu; Xiao-Fang Wang; Yang Wang; Xin Wang (Journal of Cleaner Production, 2023)

ApCYP4C6 participates in the metabolism of glucosinolates in pea aphids Acyrthosiphon pisum - Lei Liu; Wen-Jun Wang; Li-Wen Song; Yi-Ting Wu; Jiang-Wen Wei; Sen-Shan Wang; Jing-Jiang Zhou (Journal of Asia-Pacific Entomology, 2023)

Efficient acquisition of high-purity cyanidin-3-O-glucoside from mulberry fruits: An integrated process of ATPS whole-cell transformation and semi-preparative HPLC purification - Yi-Tong Li; Ting Huang; Jin-Zheng Wang; Cheng-Hai Yan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Chemistry, 2023)

Sustained-release antibacterial gelatin films: Effects of diatomite/carvacrol complex on their structure, physicochemical and antibacterial properties - Hejun Wu; Ling Ma; Sen Li; Jie Wang; Ting Li; Lu Peng; Shasha Li; Qingye Li; Xiangyang Yuan; Man Zhou; Zhiqing Zhang; Yuntao Liu (Food Packaging and Shelf Life, 2023)

Theoretically thermal-varying models of the neutral axis position for local damage detection of bridge girders - Guang-Ming Wu; Sheng-Li Li; Ting-Hua Yi; Xiu-Dao Mei; Ya-Fei Wang (Engineering Structures, 2023)

Friction anomaly alarm for bridge sliding bearings under operating environmental conditions - Guang-Ming Wu; Ting-Hua Yi; Dong-Hui Yang; Hong-Nan Li; Hua Liu (Engineering Structures, 2023)

UV-Laser ablation enhanced Joule-heating catalyst support for electrified MSR in microreactor - Xinying Li; Ding Yuan; Tian Xie; Quancong Zhang; Wenjun Xu; Ting Fu; Xuyang Chu; Tao Luo; Linjing Wu; Wei Zhou (Chemical Engineering Journal, 2023)

Cross-species binding spectrum of ACE2 to SARS-CoV-2 RBD - Xihao Liao; Changge Guan; Chenghua Wang; Xinjie Chen; Xiaomei Lin; Lianghua Lu; Lu Li; Ting Wang; Nan Su; Bian Wu; Xinquan Wang; Chong Zhang; et al. (Science China Life Sciences, 2023)

Diversity and distribution of bryophytes in ion-type rare earth mines in southern Jiangxi Province, southeast China, and the implications for vegetation restoration - Qi Ying Cai; Bin Li; Mei Ting Cai; Yi Zhen Liu; Lan Wu; Gang Ge (Plant and Soil, 2023)

DEGENERATED LEMMA (DEL) regulates lemma development and affects rice grain yield - You Jing; Chen Wenbo; He Zhifeng; Xiang Yan; Zhang XinFang; Wei Mi; Wu RuHui; Shen Wenqiang; Zhang Jun; Duan QianNan; He Guanghua; Li Yunfeng; et al. (Physiology and Molecular Biology of Plants, 2023)

Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Nicosulfuron stress on the glyoxalase system and endogenous hormone content in sweet maize seedlings - Zhen-Xing Wu; Jian Wang; Xiao-Hu Lin; Qing Yang; Ting-Zhen Wang; Jian-Jian Chen; Xiang-Nan Li; Yuan Guan; Gui-Hua Lv (Environmental Science and Pollution Research, 2023)

Associations between short-term and long-term exposure to particulate matter and preterm birth - Yun-Fei Su; Cheng Li; Jing-Jing Xu; Fang-Yue Zhou; Tao Li; Cong Liu; Yan-Ting Wu; He-Feng Huang (Chemosphere, 2023)

Acute low-dose phosphate disrupts glycerophospholipid metabolism and induces stress in juvenile turbot (Scophthalmus maximus) - Ting Qi; Lele Wu; Jiachen Yu; Zongcheng Song; Feng Liu; Jun Li; Xiefa Song; Xian Li (Science of The Total Environment, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

GSH-responsive and O2-economizing virus-like nanocapsule for photothermal-augmented sonodynamic therapy - Jiajing Liu; Mengqi Li; Zhiyu Zhao; Xian Luo; Li Wang; Tingting Li; Cong Liu; Shengyu Wang; Ting Wu; Dong Yang; Yang Li; Peiyuan Wang; et al. (Chemical Engineering Journal, 2023)

Injectable Host-Guest supramolecular hydrogel Co-Delivers hydrophobic and hydrophilic agents for enhanced wound healing - Jie Xu; Kangning Wang; Yanyan Li; Yue Li; Bingxin Li; Hangqi Luo; Huiling Shi; Xueran Guan; Ting Zhang; Yixiao Sun; Feng Chen; Huacheng He; et al. (Chemical Engineering Journal, 2023)

Tumor microenvironment activated nanoreactors for chemiluminescence imaging-guided simultaneous elimination of breast tumors and tumor-resident intracellular pathogens - Xinxin Li; Ting Wu; Zefan Zhang; Sha Liu; Hongmei Cui; Zhongxiong Fan; Baodui Wang; Jun Hai (Chemical Engineering Journal, 2023)

A topical platelet-independent multilevel clotting initiator for intraoperative hemostasis - Fenglin Miao; Huirong Lin; Tianhong Yao; Ruyi Zhang; Xinfei Sun; Hongwei Cheng; Lingwei Gu; Xiaogang Xia; Ting Wu; Wengang Li; Gang Liu (Chemical Engineering Journal, 2023)

Efficient fabrication of desert beetle-inspired micro/nano-structures on polypropylene/graphene surface with hybrid wettability, chemical tolerance, and passive anti-icing for quantitative fog harvesting - Wei-long Zhou; Ting Wu; Yu Du; Xiao-hu Zhang; Xin-chang Chen; Jin-bo Li; Heng Xie; Jin-ping Qu (Chemical Engineering Journal, 2023)

Optimizing the Schoenemann Reaction for Colorimetric Assays of VX and GD - Shaoxiong Wu; Lianyuan Wang; Haiyan Zhu; Ling Yuan; Jian Li; Liang Ge; Hongpeng Zhang; Ting Miao; Zhenxing Cheng (Bulletin of Environmental Contamination and Toxicology, 2023)

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

Insights into the Relationship between Intestinal Microbiota of the Aquaculture Worm Sipunculus nudus and Surrounding Sediments - Junwei Li; Suwen Chen; Peng Wu; Changbo Zhu; Ruiping Hu; Ting Li; Yongjian Guo (Fishes, 2023)
Sipunculus nudus is an important intertidal aquaculture species that can ingest organic matter from the surface sediment and shows a high transportation capacity in sediment. However, little is known about the influence of intertidal aquaculture species on the sediment microbial community and the exchange of microbiota between the intestine and the surrounding sediment. In this study, the microbial communities in the intestine of S. nudus and three kinds of surrounding sediments were analyzed using high-throughput sequencing of the 16S rRNA gene amplicon, and the relationships between different communities were examined. Principal coordinate analysis and ANOSIM/Adonis analysis showed that the microbial communities of worm intestine samples were significantly different from those of surrounding sediments (p

Nondestructive and rapid method for sex identification of the tropical sea cucumber Holothuria scabra by anal swab sampling - Zixuan E; Chuhang Cheng; Feifei Wu; Chunhua Ren; Rong Chen; Yingzhu Rao; Bo Ma; Xiao Jiang; Peng Luo; Xiaomin Li; Xin Zhang; Fajun Jiang; et al. (Aquaculture, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

Effect of gradual increase of atmospheric CO2 concentration on nitrification potential and communities of ammonia oxidizers in paddy fields - Bing-jie Ren; Li-dong Shen; Xin Liu; Jing-hao Jin; He-chen Huang; Mao-hui Tian; Yu-ling Yang; Wang-ting Yang; Jia-qi Liu; Cai-yu Geng; Hong-sheng Wu; Zheng-hua Hu (Journal of Environmental Management, 2023)

Liquid metal embrittlement to boost reactivity and combustion performance of Al in composite propellants - An Chen; Bo Wu; Lan Li; Ting You; Jun Wang; Jinpeng Shen; Chonghua Pei (Fuel, 2023)

Modifying functional properties of food amyloid-based nanostructures from rice glutelin - Ting Li; Jiangtao Zhou; Qinglan Wu; Xinxia Zhang; Zhengxing Chen; Li Wang (Food Chemistry, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Molecular cloning and characteristic analysis of polymeric immunoglobulin receptor-like (plgRL) in large yellow croaker (Larimichthys crocea) - Du Yang; Xiaoman Hu; Hao Li; Wenlong Xu; Ting Wu; Jiong Chen (Fish & Shellfish Immunology, 2023)

Fluoroalkane modified cationic polymers for personalized mRNA cancer vaccines - Junyan Li; Yuanyuan Wu; Jian Xiang; Hairong Wang; Qi Zhuang; Ting Wei; Zhiqin Cao; Qingyang Gu; Zhuang Liu; Rui Peng (Chemical Engineering Journal, 2023)

A thin LiGa alloy layer from in-situ electroreduction to suppress anode dendrite formation in lithium-sulfur pouch cell - Rong Li; Liwen Yang; Lei Song; Changan Zhou; Jiayu Zhou; Ting Chen; Chen Wu; Yujia Zeng; Kui Ma; Hairong Yue (Chemical Engineering Journal, 2023)

Inner phase hybridization engineering of core-shell structure confined in graphene scroll for boosting electromagnetic wave absorption - Ting Shi; Yuan Yao; Yang Li; Songtao Lu; Wei Qin; Xiaohong Wu (Chemical Engineering Journal, 2023)

Photothermal activation of peroxydisulfate using iron nanoparticles/MXene@polyurethane sponge module for treatment of landfill leachate: From lab to pilot scale - Haoran Song; Rui Zhou; Shiting Pan; Yuwei Wang; Yang Cai; Qingyun Li; Ting Wu; Yongming Shen; Changping Li (Chemical Engineering Journal, 2023)

Synergistic effect of F doping and WO3 loading on electrocatalytic oxygen evolution - Ke Lu; Zongyuan Wang; Yaoxin Wu; Xingwu Zhai; Chenxu Wang; Ju Li; Zhimou Wang; Xinyi Li; Yuxuan He; Ting An; Kun Yang; Dezheng Yang; et al. (Chemical Engineering Journal, 2023)

Volatile organic compound emissions from typical industries: Implications for the importance of oxygenated volatile organic compounds - Wenjing Wang; Yunzhi Yan; Hua Fang; Jun Li; Shuping Zha; Ting Wu (Atmospheric Pollution Research, 2023)

High Fe and Mn groundwater in the Nanchang, Poyang Lake Basin of China: hydrochemical characteristics and genesis mechanisms - Xiaodong Chu; Zhifei Ma; Daishe Wu; Hao Wang; Jingyuan He; Ting Chen; Ziyin Zheng; Hugang Li; Peng Wei (Environmental Monitoring and Assessment, 2023)

The prenatal weekly temperature exposure and neonatal congenital heart disease: a large population-based observational study in China - Weize Xu; Die Li; Zehua Shao; Yanqin You; Feixia Pan; Hongliang Lou; Jing Li; Yueqin Jin; Ting Wu; Lulu Pan; Jing An; Junqiu Xu; et al. (Environmental Science and Pollution Research, 2022)

Effects of STAT3 Inhibitor BP-1-102 on The Proliferation, Invasiveness, Apoptosis and Neurosphere Formation of Glioma Cells in Vitro - Cheng-Chen Zhang; Ting Wu; Li Guan; Yu-Jue Wang; Rui-Qin Yao; Dian-Shuai Gao; Feng Li (Cell Biochemistry and Biophysics, 2022)

6-O-desulfated heparin attenuates myocardial ischemia/reperfusion injury in mice through the regulation of miR-199a-5p/klotho axis - Yujie Wang; Ting Li; Niansheng Li; Chuyi Huang; Xiaoming Xiong; Xu Xie; Meiting Wu; Lianchun Wang; Junlin Jiang (Glycoconjugate Journal, 2022)

Genome-Wide Identification, Expression, and Interaction Analysis of BEL-Like Homeodomain Gene Family in Peach - Hui-feng Li; Ya-ting Wu; Qiang Zhao; Qing-long Dong (Biochemical Genetics, 2022)

MicroRNA-133 suppresses cell viability and migration of rheumatoid arthritis fibroblast-like synoviocytes by down-regulation of MET, EGFR, and FSCN1 expression - Shih-Yao Chen; Jeng-Long Hsieh; Po-Ting Wu; Ai-Li Shiau; Chao-Liang Wu (Molecular and Cellular Biochemistry, 2022)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

AKR1B10 accelerates the production of proinflammatory cytokines via the NF-κB signaling pathway in colon cancer - Cong Liu; Lei Shi; Wanyun Li; Zilan Huang; Shengyu Wang; Peilan Xu; Tingting Li; Zhenyu Li; Fanghong Luo; Wengang Li; Jianghua Yan; Ting Wu (Journal of Molecular Histology, 2022)

The enhanced removal of arsenite from water by double-shell CuOx@MnOy hollow spheres (DCMHS): behavior and mechanisms - Kun Wu; Birong Miao; Yuyang Xiao; Yang Li; Chuanqiao Zhang; Ting Liu; Shengjiong Yang; Jinfu Liu (Environmental Science and Pollution Research, 2022)

Genome-wide association study reveals a NAC transcription factor TaNAC074 linked to pre-harvest sprouting tolerance in wheat - Hao Jiang; Yu Fang; Dong Yan; Si-tong Liu; Jun Wei; Fei-long Guo; Xing-ting Wu; Hong Cao; Chang-bin Yin; Fei Lu; Li-feng Gao; Yong-xiu Liu (Theoretical and Applied Genetics, 2022)

Transcriptomic analysis reveals yolk accumulation mechanism from the hepatopancreas to ovary in the pacific white shrimp Litopenaeus vannamei - Zhi Li; Minyu Zhou; Yao Ruan; Xiaoli Chen; Chunhua Ren; Hao Yang; Xin Zhang; Jinshang Liu; Huo Li; Lvping Zhang; Chaoqun Hu; Ting Chen; et al. (Frontiers in Marine Science, 2022)
The Pacific white shrimp Litopenaeus vannamei is an economically important penaeid species worldwide. Under farming conditions, the full ovarian maturation of L. vannamei generally depends on the combination of artificial ablation of unilateral eyestalk and feeding high-quality natural diets, suggesting that nutrient accumulation is important to ovarian maturation. In this study, we aimed to investigate the gene expression related to nutritional accumulation in L. vannamei during ovarian development by transcriptomic analysis. A total of 52.45 Gb of high-quality transcriptome data were obtained from 8 samples from the hepatopancreas and ovaries from shrimp in gonadal developmental stages I-IV. A total of 23,149 expressed genes were detected, of which 19,852 were known genes and 3,297 were novel genes. Our study found that genes related to amino acid, carbohydrate and lipid metabolism were expressed at higher levels in the hepatopancreas than in the ovary. The genes for most lipoproteins and their receptors were predominantly expressed in the hepatopancreas, while vitellogenin receptor ( VgR ) was specifically expressed in the ovary. Moreover, two vitellogenin ( Vg ) genes were identified, in which one was specifically expressed in the hepatopancreas and defined as Hp-Vg , and the other was specifically expressed in the ovary and defined as Ov-Vg . In addition, genes related to carotenoid metabolism were enriched in the hepatopancreas. This study provides solid evidence that the hepatopancreas is the major exogenous vitellogenesis site for ovarian maturation of L. vannamei . Two distinct Vg genes perform exogenous and endogenous vitellogenesis in the hepatopancreas and ovary in L. vannamei , respectively. The results of this study also presented some new insights for understanding the nutritional dynamics from the hepatopancreas to ovary during ovarian maturation in penaeids.

Time Trends and Forecasts of Atmospheric Heavy Metals in Lanzhou, China, 2015–2019 - Meixia Du; Xiaochun Yin; Yongjun Li; Ting Ke; Hai Zhu; Jianjun Wu; Guisen Zheng (Water, Air, & Soil Pollution, 2022)

Human Umbilical Cord-Derived Mesenchymal Stem Cells Ameliorate Skin Aging of Nude Mice Through Autophagy-Mediated Anti-Senescent Mechanism - Ting Li; Li Zhou; Mengqiang Fan; Zuxiang Chen; Li Yan; Haishan Lu; Ming Jia; Huiling Wu; Letian Shan (Stem Cell Reviews and Reports, 2022)

Uncertainties in Prediction of Near-Fault Long-Period Ground Motion: An Application to the 1970 Tonghai Earthquake (Ms 7.8) - Zhiwei Ji; Zongchao Li; Xueliang Chen; Tiefei Li; Qing Wu; Bo Zhang; Qi Li; Ting Huang (Pure and Applied Geophysics, 2022)

Biomechanical Effects of Bone Atrophy, Implant Design, and Vertical or Tilted of Posterior Implant on All-on-Four Concept Implantation: Finite Element Analysis - Heng-Li Huang; Ting-Wei Lin; Hui-Ling Tsai; Yu-Ling Wu; Aaron Yu-Jen Wu (Journal of Medical and Biological Engineering, 2022)

Effects of U on the growth, reactive oxygen metabolism and osmotic regulation in radish (Raphanus sativus L.) - Guo Wu; Xi Chen; Ting Zheng; Pi-xian Xiao; Ning-ying Zhong; Xiu-lin Yang; Yi Li; Wei Li (Environmental Science and Pollution Research, 2022)

Improving protected area effectiveness through consideration of different human‐pressure baselines - Chun‐Ting Feng; Ming Cao; Fang‐Zheng Liu; Yue Zhou; Jin‐Hong Du; Li‐Bo Zhang; Wen‐Jie Huang; Jian‐Wu Luo; Jun‐Sheng Li; Wei Wang (Conservation Biology, 2022)
Previous assessments of the effectiveness of protected areas (PAs) focused primarily on changes in human pressure over time and did not consider the different human‐pressure baselines of PAs, thereby potentially over‐ or underestimating PA effectiveness. We developed a framework that considers both human‐pressure baseline and change in human pressure over time and assessed the effectiveness of 338 PAs in China from 2010 to 2020. The initial state of human pressure on PAs was taken as the baseline, and changes in human pressure index (HPI) were further analyzed under different baselines. We used the random forest models to identify the management measures that most improved effectiveness in resisting human pressure for the PAs with different baselines. Finally, the relationships between the changes in the HPI and the changes in natural ecosystems in PAs were analyzed with different baselines. Of PAs with low HPI baselines, medium HPI baselines, and high HPI baselines, 76.92% ( n =150), 11.11% ( n =12), and 22.86% ( n =8) , respectively, showed positive effects in resisting human pressure. Overall, ignoring human‐pressure baselines somewhat underestimated the positive effects of PAs, especially for those with low initial human pressure. For PAs with different initial human pressures, different management measures should be taken to improve effectiveness and reduce threats to natural ecosystems. We believe our framework is useful for assessing the effectiveness of PAs globally, and we recommend it be included in the Convention on Biological Diversity Post‐2020 Strategy.

Particle Design and Inhalation Delivery of Iodine for Upper Respiratory Tract Infection Therapy - Kaikai Zhang; Xiaohong Ren; Jiacai Chen; Caifen Wang; Siyu He; Xiaojin Chen; Ting Xiong; Jiawen Su; Shujun Wang; Weifeng Zhu; Jiwen Zhang; Li Wu (AAPS PharmSciTech, 2022)

Dataset-based assessment of heavy metal contamination in freshwater fishes and their health risks - Xiao-Bo Liu; Congtian Lin; Yang-Yu Wu; Hai-Ning Huang; Li-Ting Zhu; Ru Jiang; Qiansheng Huang (Environmental Science and Pollution Research, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Testing the isotopic equilibrium fractionation on active speleothem based on cave monitoring - Yang-Yang Huang; Ting-Yong Li; Chao-Jun Chen; Ran Huang; Tao Wang; Yao Wu; Si-Ya Xiao; Yu-Zhen Xu; Hai-Ying Qiu; Yan Yang; Jun-Yun Li (Journal of Earth System Science, 2022)

Clinical efficacy of melatonin as adjunctive therapy to non-surgical treatment of periodontitis: a systematic review and meta-analysis - Ru-Yue Liu; Lin Li; Zhong-Ti Zhang; Ting Wu; Shuang Lin; Xu-Tong Zhang (Inflammopharmacology, 2022)

The relative importance of intraspecific variation in above- and belowground plant traits in shaping salt marsh soil bacterial diversity and composition - Hao Liu; Ting Zhu; Xiao Xu; Jia Yao; Chenhao Zhou; Jihua Wu; Bo Li; Ming Nie (Plant and Soil, 2022)

Hypothermal Effects on Energy Supply for Ionocytes in Gills of Freshwater- and Seawater-Acclimated Milkfish, Chanos chanos - Chia-Hao Chang; Chia-Jui Liu; Wei-Jie Lu; Li-Yang Wu; Kuang-Jie Lai; Yu-Ting Lin; Tsung-Han Lee (Frontiers in Marine Science, 2022)
The milkfish, Chanos chanos , is an important aquaculture species that can be cultured in freshwater (FW) and seawater (SW) ponds because of its high euryhalinity. In winter, cold snap leading to high mortality of this tropical species is a critical issue for the aquaculture industry in Taiwan. Under hypothermal stress, however, changes in energy supply for osmoregulation of this euryhaline species is intriguing. In this study, we used an antibody against glycogen phosphorylase (GP) to identify glycogen-rich (GR) cells distributed adjacent to the mitochondria-rich (MR) ionocytes in milkfish gills. Glucose transporter 1 (GLUT1), which plays a major role in energy supply, was also identified and localized in GR cells. Moreover, the expression of indicators of aerobic metabolism and energy production, citrate synthase (CS) and cytochrome c oxidase (COX), were analyzed in gills of FW- and SW-acclimated milkfish to reveal different strategies of energy utilization under hypothermal stress. When exposed to a low-temperature environment, SW individuals used branchial glycogen and lactate to match the energy demands of aerobic metabolism in ionocytes, and elevated aerobic capacity to support and maintain normal functions in gills. However, branchial glycogen mainly localized in the GR cells of FW milkfish was not utilized under hypothermal stress. Meanwhile, a similar level of branchial COX activity and COXIV protein abundance at low temperatures between FW and SW milkfish indicated similar energy requirements in gills. This suggested that another source, but not branchial glycogen, maintained the energy demand in FW milkfish. The present study illustrated differential energy supply strategies in gills between SW- and FW-acclimated milkfish for osmoregulation under low temperatures.

Crocin Alleviates Intracerebral Hemorrhage–Induced Neuronal Ferroptosis by Facilitating Nrf2 Nuclear Translocation - Fei Wang; Wu-lin Li; Li-juan Shen; Ting-ting Jiang; Jian-jun Xia; Da-li You; Shan-you Hu; Li Wang; Xiao Wu (Neurotoxicity Research, 2022)

Transcriptomic analyses provide insight into adventitious root formation of Euryodendron excelsum H. T. Chang during ex vitro rooting - Yuping Xiong; Shuangyan Chen; Zhenpeng Wei; Xiaohong Chen; Beiyi Guo; Ting Zhang; Yuying Yin; Xincheng Yu; Jinhui Pang; Meiyun Niu; Xinhua Zhang; Yuan Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Mutant library resources for legume crops and the emerging new screening technologies - Wenjun Xia; Peipei Zhang; Xinyang Wu; Mingxuan Li; Ting Sun; Pingping Fang; Arun K. Pandey; Pei Xu (Euphytica, 2022)

Engineering and Characterization of a Biomimetic Microchip for Differentiating Mouse Adipocytes in a 3D Microenvironment - Yu-ting Chen; Latha Ramalingam; Celine R. Garcia; Zhenya Ding; Jiangyu Wu; Naima Moustaid-Moussa; Wei Li (Pharmaceutical Research, 2022)

Basal ganglia-orbitofrontal circuits are associated with prospective memory deficits in Wilson’s disease - Sheng Hu; ChunSheng Xu; Yi Wang; Ting Dong; Hongli Wu; Anqin Wang; Chuanfu Li; BenSheng Qiu (Brain Imaging and Behavior, 2022)

A Facile Probe for Fluorescence Turn-on and Simultaneous Naked-Eyes Discrimination of H2S and biothiols (Cys and GSH) and Its Application - Ting-Ting Liu; Shi-Jie Li; Xiao-Song Zhang; Jing Wang; Yun-Xiu Deng; Xue-Jiao Sun; Zhi-Yong Xing; Ruo-Fei Wu (Journal of Fluorescence, 2022)

Luteirhabdus pelagi gen. nov., sp. nov., a novel member of the family Flavobacteriaceae, isolated from the West Pacific Ocean - Wen-Ting Ren; Fan-Xu Meng; Li-Li Guo; Li Sun; Xue-Wei Xu; Peng Zhou; Yue-Hong Wu (Archives of Microbiology, 2021)
A Gram-stain-negative, aerobic, and yellow-pigmented bacterium, designated A3-108 T , was isolated from seawater of the West Pacific Ocean. Cells were non-motile and rod-shaped, with carotenoid-type pigments. Strain A3-108 T grew at pH 6.0–8.5 (optimum 6.5) and 15–40 °C (optimum 28 °C), in the presence of 0.5–10% (w/v) NaCl (optimum 1.0%). It possessed the ability to produce H 2 S. Based on the 16S rRNA gene analysis, strain A3-108 T exhibited highest similarity with Aureisphaera salina A6D-50 T (90.6%). Phylogenetic analysis shown that strain A3-108 T affiliated with members of the family Flavobacteriaceae and represented an independent lineage. The principal fatty acids were iso-C 15:0 , iso-C 17:0 3-OH, iso-C 15:1 G, and summed feature 3 (C 16:1 ω 7 c and/or C 16:1 ω 6 c ). The sole isoprenoid quinone was MK-6. The major polar lipids were phosphatidylethanolamine, one unidentified aminophospholipid, one unidentified aminolipid and one unidentified lipid. The ANIb, in silico DDH and AAI values among the genomes of strain A3-108 T and three reference strains were 67.3–71.1%, 18.7–22.1%, and 58.8–71.4%, respectively. The G + C content was 41.0%. Distinctness of the phylogenetic position as well as differentiating chemotaxonomic and other phenotypic traits revealed that strain A3-108 T represented a novel genus and species of the family Flavobacteriaceae , for which the name Luteirhabdus pelagi gen. nov., sp. nov. is proposed (type strain, A3-108 T = CGMCC 1.18821 T = KCTC 82563 T ).

Pivotal role of the gut microbiota in congenital insensitivity to pain with anhidrosis - Mi Zhang; Yishun Hong; Wenyao Wu; Ningbo Li; Baowen Liu; Jiaoli Sun; Xueqin Cao; Ting Ye; Ling Zhou; Cunming Liu; Chun Yang; Xianwei Zhang (Psychopharmacology, 2021)

Plant growth–promoting bacteria improve maize growth through reshaping the rhizobacterial community in low-nitrogen and low-phosphorus soil - La Chen; Keke Li; Jiaoying Shang; Yue Wu; Ting Chen; Yuqian Wanyan; Entao Wang; Changfu Tian; Wenfeng Chen; Wenxin Chen; Guohua Mi; Xinhua Sui (Biology and Fertility of Soils, 2021)

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N 2 with a previously unknown pathway - Meng‐Ru Wu; Ting‐Ting Hou; Ying Liu; Li‐Li Miao; Guo‐Min Ai; Lan Ma; Hai‐Zhen Zhu; Ya‐Xin Zhu; Xi‐Yan Gao; Craig W. Herbold; Michael Wagner; De‐Feng Li; et al. (Environmental Microbiology, 2021)
Summary Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen‐rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO‐1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO‐1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia monooxygenases or hydroxylamine oxidoreductases. Our results demonstrated strain HO‐1 denitrified nitrite (not nitrate) to N 2 and N 2 O at anaerobic and aerobic conditions respectively. Further experiments demonstrated that inhibition of aerobic denitrification did not stop ammonia oxidation and N 2 production. A gene cluster ( dnfT1RT2ABCD ) was cloned from strain HO‐1 and enabled E . coli accumulated hydroxylamine. Sub‐cloning showed that genetic cluster dnfAB or dnfABC already enabled E . coli cells to produce hydroxylamine and further to 15 N 2 from ( 15 NH 4 ) 2 SO 4 . Transcriptome analysis revealed these three genes dnfA , dnfB and dnfC were significantly upregulated in response to ammonia stimulation. Taken together, we concluded that strain HO‐1 has a novel dnf genetic cluster for ammonia oxidation and this dnf genetic cluster encoded a previously unknown pathway of di rect amm onia ox idation (Dirammox) to N 2 .

A network pharmacology study with molecular docking to investigate the possibility of licorice against posttraumatic stress disorder - Zhi-Kun Qiu; Zhi-Ting Liu; Jia-Li Pang; Han-Biao Wu; Xu Liu; Ze-Min Yang; Xiong Li; Ji-Sheng Chen (Metabolic Brain Disease, 2021)

γ-Aminobutyric Acid Participates in the Adult-Phase Adventitious Rooting Recalcitrance - Xu Li; Xiaozhao Xu; Fei Shen; Wei Li; Changpeng Qiu; Ting Wu; Yi Wang; Xuefeng Xu; Zhenhai Han; Xinzhong Zhang (Journal of Plant Growth Regulation, 2021)
In many tree species especially the rooting-recalcitrant woody perennials, the adventitious root (AR) in the juvenile phase can be easily induced by exogenous auxin, but AR formation becomes recalcitrant in the adult phase. Also, it is reported that the γ-aminobutyric acid (GABA) inhibits primary root growth in Arabidopsis and the AR formation in poplar ( Populus ssp). So far, how GABA affects or is affected by the ontogenetic phase or auxin remains unclear. Here, we used an apple rootstock, Malus xiaojinensis, and tobacco ( Nicotiana benthamiana ) to investigate this question. We first analyzed the content of GABA, the activity of GABA synthetic enzyme GAD, and the expression of the coding gene MxGADs, respectively, in leafy cuttings of juvenile and adult phase. Next, the effect of exogenous GABA on AR formation was examined in in vitro shoots of M. xiaojinensis and tobacco. Interestingly, significant and consistent increases in GABA concentration, GAD activity, and expression of MxGAD genes in response to exogenous indole butyric acid (IBA) were detected in adult-phase cuttings, but not in juvenile-phase cuttings. Exogenous GABA application inhibited the AR formation by delaying rooting time and reducing root number and the total root length in in vitro shoots of both M. xiaojinensis and tobacco. The expression of MxPIN members increased in response to IBA application, but these changes were restrained by the addition of GABA. These results indicate that both the loss of juvenility and IBA are required to trigger GABA accumulation. GABA may affect the AR formation as a co-actor by inhibiting polar auxin transport. Together, these findings facilitate the understanding of the regulatory network among GABA, juvenility, and auxin signaling on the AR formation.

CARMA1 is required for Notch1-induced NF-κB activation in SIL-TAL1-negative T cell acute lymphoblastic leukemia - Ninghan Zhang; Jiawen Xu; Rong Wang; Ting Pan; Huanxin Zhang; Lingling Yin; Yao Yao; Linyan Xu; Shengyun Zhu; Qingyun Wu; Zhenyu Li; Xuejiao Liu; et al. (Journal of Molecular Medicine, 2021)

Quantitative microbial risk assessment for occupational health of temporary entrants and staffs equipped with various grade PPE and exposed to microbial bioaerosols in two WWTPs - Cheng Yan; Ya-li Leng; Jun-ting Wu (International Archives of Occupational and Environmental Health, 2021)

Maternal exposure to sulfur dioxide and the risk of oral clefts in Liaoning Province, China: a population-based case-control study - Fang-Hua Liu; Ze Xing; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; et al. (Environmental Science and Pollution Research, 2021)

Longitudinal associations of sleep duration and sleep quality with coronary heart disease risk among adult population: classical meta-analysis and Bayesian network meta-analysis - Rui Zeng; Yu-ting Jiang; Tian-wu Chen; Dan-dan Guo; Rui Li (Sleep and Biological Rhythms, 2021)

Exploring the validity of using immersive virtual reality technique on perceived crowding of recreational environment - Ting-Hsuan Wang; Wan-Hsuan Wu; Li Shen; Chia-Kuen Cheng (Landscape and Ecological Engineering, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Syntheses and anticancer activities of novel glucosylated (−)-epigallocatechin-3-gallate derivatives linked via triazole rings - Bo-Ya Shi; Ze-Hao Wang; Ning Zhang; Yin-Rong Xie; Xiu-Li Sun; Hao-Nan Yang; Yi-Long Wu; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Medicinal Chemistry Research, 2021)

Immobilization of Cd and Pb in a contaminated acidic soil amended with hydroxyapatite, bentonite, and biochar - Di Zhang; Aifang Ding; Ting Li; Xiaoxia Wu; Yanju Liu; Ravi Naidu (Journal of Soils and Sediments, 2021)

Intraspecific recurrent selection in V. vinifera: an effective method for breeding of high quality, disease-, cold-, and drought -resistant grapes - Zhi-Lei Wang; Ting-Ting Xue; Fei-Fei Gao; Liang Zhang; Xing Han; Ying Wang; Miao Hui; Dong Wu; Hua Li; Hua Wang (Euphytica, 2021)

Two new dihydroisocoumarins with antimicrobial activities from the fungus Penicillium sp. XR046 collected from Xinren coal area - Guo-Bo Xu; Fei-Yu Yang; Xin-Yu Wu; Rui Li; Meng Zhou; Bing Wang; Xiao-Sheng Yang; Ting-Ting Zhang; Shang-Gao Liao (Natural Product Research, 2021)

Antifungal Effect of Long Noncoding RNA 9708-1 in the Vulvovaginal Candidiasis Murine Model - Ying Wu; Lisha Jiang; Lingling Zhang; Xia Liu; Lina Yan; Ting Luan; Can Rui; Zhiyuan Mao; Chong Fan; Yu Liu; Ping Li; Xin Zeng (Mycopathologia, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida spp. affects 70–75% of women at least once during their lives. We aim to elucidate the potential mechanism of VVC and investigate the therapeutic effects of long noncoding RNA 9708-1. Female BALB/c mice were randomized to four treatment groups, including the blank control group, VVC control group, vehicle control group and lncRNA 9708-1-overexpressed group. Mice were euthanized on Day 4, Day 7 and Day 14 after treatment. Colony-forming unit (CFU) was measured, and the inflammation was detected by hematoxylin and eosin (H&E). Gene and protein expression levels of lncRNA 9708-1 and FAK were determined by real-time PCR, Western blot and immunohistochemistry. The overexpression of lncRNA 9708-1 significantly decreased the fungal load from Day 4 to 7. H&E staining indicated that the impaired histological profiles were improved in lncRNA 9708-1-overexpressed group. LncRNA 9708-1 led to a significant increase in FAK level of vagina tissue which is expressed mainly in epithelial basal layer. This study suggests that lncRNA 9708-1 played a protective role on murine experimental VVC by upregulating the expression levels of FAK.

The hand-arm vibration syndrome associated with the grinding of handheld workpieces in a subtropical environment - Nuoyan Wei; Hansheng Lin; Ting Chen; Bin Xiao; Maosheng Yan; Li Lang; Hongyu Yang; Shan Wu; Paul-Émile Boileau; Qingsong Chen (International Archives of Occupational and Environmental Health, 2021)

Variation of Soil Bacterial and Fungal Communities from Fluvo-Aquic Soil Under Chemical Fertilizer Reduction Combined with Organic Materials in North China Plain - Xian Wu; Ting Zhang; Jianning Zhao; Lili Wang; Dianlin Yang; Gang Li; Weiming Xiu (Journal of Soil Science and Plant Nutrition, 2021)

Maternal exposure to ambient SO2 and risk of polydactyly and syndactyly: a population-based case-control study in Liaoning Province, China - Yu-Ting Jiang; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; Qi-Jun Wu (Environmental Science and Pollution Research, 2021)

Relationship between p38 signaling pathway and arsenic-induced apoptosis: a meta-analysis - Liping Wu; Xi Li; Shaofeng Wei; Ting Hu; Changyan Wu; Wen Jian; Peng Luo (Environmental Geochemistry and Health, 2021)

Macrolactins: biological activity and biosynthesis - Ting Wu; Fei Xiao; Wenli Li (Marine Life Science & Technology, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Warming leads to more closed nitrogen cycling in nitrogen‐rich tropical forests - Zhiyang Lie; Wenjuan Huang; Xujun Liu; Guoyi Zhou; Junhua Yan; Yuelin Li; Chumin Huang; Ting Wu; Xiong Fang; Mengdi Zhao; Shizhong Liu; Guowei Chu; et al. (Global Change Biology, 2021)
Warming may have profound effects on nitrogen (N) cycling by changing plant N demand and underground N supply. However, large uncertainty exists regarding how warming affects the integrated N dynamic in tropical forests. We translocated model plant‐soil ecosystems from a high‐altitude site (600 m) to low‐altitude sites at 300 and 30 m to simulate warming by 1.0°C and 2.1°C, respectively, in tropical China. The effects of experimental warming on N components in plant, soil, leaching, and gas were studied over 6 years. Our results showed that foliar δ 15 N values and inorganic N (NH 4 ‐N and NO 3 ‐N) leaching were decreased under warming, with greater decreases under 2.1°C of warming than under 1.0°C of warming. The 2.1°C of warming enhanced plant growth, plant N uptake, N resorption, and fine root biomass, suggesting higher plant N demand. Soil total N concentrations, NO 3 ‐N concentrations, microbial biomass N and arbuscular mycorrhizal fungal abundance were decreased under 2.1°C of warming, which probably restricted bioavailable N supply and arbuscular mycorrhizal contribution of N supply to plants. These changes in plants, soils and leaching indicated more closed N cycling under warming, the magnitude of which varied over time. The closed N cycling became pronounced during the first 3 years of warming where the sustained reductions in soil inorganic N could not meet plant N demand. Subsequently, the closed N cycling gradually mitigated, as observed by attenuated positive responses of plant growth and less negative responses of microbial biomass N to warming during the last 3 years. Overall, the more closed N cycling under warming could facilitate ecosystem N retention and affect production in these tropical forests, but these effects would be eventually mitigated with long‐term warming probably due to the restricted plant growth and microbial acclimation.

Diversity and potential biogeochemical impacts of viruses in bulk and rhizosphere soils - Li Bi; Dan‐Ting Yu; Shuai Du; Li‐Mei Zhang; Li‐Yu Zhang; Chuan‐Fa Wu; Chao Xiong; Li‐Li Han; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Viruses can affect microbial dynamics, metabolism and biogeochemical cycles in aquatic ecosystems. However, viral diversity and functions in agricultural soils are poorly known, especially in the rhizosphere. We used virome analysis of eight rhizosphere and bulk soils to study viral diversity and potential biogeochemical impacts in an agro‐ecosystem. The order Caudovirales was the predominant viral type in agricultural soils, with Siphoviridae being the most abundant family. Phylogenetic analysis of the terminase large subunit of Caudovirales identified high viral diversity and three novel groups. Viral community composition differed significantly between bulk and rhizosphere soils. Soil pH was the main environmental driver of the viral community structure. Remarkably, abundant auxiliary carbohydrate‐active enzyme (CAZyme) genes were detected in viromes, including glycoside hydrolases, carbohydrate esterases and carbohydrate‐binding modules. These results demonstrate that virus‐encoded putative auxiliary metabolic genes or metabolic genes that may change bacterial metabolism and indirectly contribute to biogeochemical cycling, especially carbon cycling, in agricultural soil.

Hypoxia/reoxygenation-induced upregulation of miRNA-542-5p aggravated cardiomyocyte injury by repressing autophagy - Fei Wang; Xin Min; Shan-you Hu; Da-li You; Ting-ting Jiang; Li Wang; Xiao Wu (Human Cell, 2021)

Reactive oxygen species altering the metabolite profile of the marine-derived fungus Dichotomomyces cejpii F31-1 - Sharpkate Shaker; Ting-Ting Sun; Liang-Yue Wang; Wen-Zhe Ma; Dong-Lan Wu; Yong-Wei Guo; Jun Dong; Yan-Xiu Chen; Long-Ping Zhu; De-Po Yang; Hou-Jin Li; Wen-Jian Lan (Natural Product Research, 2021)

Strategic interactions in environmental regulation enforcement: evidence from Chinese cities - Kangkang Zhang; Deyi Xu; Shiran Li; Ting Wu; Jinhua Cheng (Environmental Science and Pollution Research, 2021)

Temperature-controlled molecular weight of hyaluronic acid produced by engineered Bacillus subtilis - Yingying Li; Zhuangzhuang Shi; Yuzhe Shao; Mengmeng Wu; Guoqiang Li; Ting Ma (Biotechnology Letters, 2021)

Characteristics of the potential vorticity and its budget in the surface layer over the Tibetan plateau - Chen Sheng; Guoxiong Wu; Yiqiong Tang; Bian He; Yongkun Xie; Tingting Ma; Ting Ma; Jinxiao Li; Qing Bao; Yimin Liu (International Journal of Climatology, 2021)
The variability of interior atmospheric potential vorticity (PV) is linked with PV generation at the Earth's surface. The present paper reveals the features of the surface PV and provides a stepping stone to investigate the surface PV budget. In this study, the formats of the PV and PV budget adopting a generalized vertical coordinate were theoretically examined to facilitate the calculation of the surface PV and its budget. Results show that the formats of the PV and PV budget equations are independent of the vertical coordinate. While the vertical component of the surface PV dominates over the platform of the Tibetan Plateau, the horizontal component plays an important role over the slopes of the Tibetan Plateau, especially the southern slope owing to the strong in‐situ meridional gradient of the potential temperature. These results indicate that the employment of complete surface PV not only provides a finer PV structure but also more appropriately reveals its effect on atmospheric circulation. Diagnosis based on reanalysis and model output demonstrates that the surface PV budget equation is well balanced both in terms of the climate mean and synoptic process, and the surface PV budget in June has a prominent diurnal cycle. The diabatic heating with a minimum in the early morning and a maximum from evening to midnight contributes dominantly to this diurnal cycle. It is further indicated that positive PV generation due to diabatic heating is essential for the formation, development, and movement of the Tibetan Plateau vortex.

Chemical composition, antioxidant, antibacterial and cholinesterase inhibitory activities of three Juniperus species - Yujia Zhang; Dong Wu; Shun Kuang; Mingliang Qing; Yue Ma; Tong Yang; Ting Wang; Dengwu Li (Natural Product Research, 2020)

OsRbohB-mediated ROS production plays a crucial role in drought stress tolerance of rice - Yi Shi; Yan-Li Chang; Hai-Tao Wu; Abdullah Shalmani; Wen-Ting Liu; Wen-Qiang Li; Jian-Wei Xu; Kun-Ming Chen (Plant Cell Reports, 2020)

YAP/TAZ affects the development of pulmonary fibrosis by regulating multiple signaling pathways - Ting Zhu; Zhifeng Ma; Haiyong Wang; Xiaoxiao Jia; Yuanlin Wu; Linhai Fu; Zhupeng Li; Chu Zhang; Guangmao Yu (Molecular and Cellular Biochemistry, 2020)

Improving the Diagnostic Ability of the Sleep Apnea Screening System Based on Oximetry by Using Physical Activity Data - Cheng-Han Wu; Jui-Hsuan Lee; Terry B. J. Kuo; Chun-Ting Lai; Lieber P. H. Li; Cheryl C. H. Yang (Journal of Medical and Biological Engineering, 2020)

Relationships among cigarette smoking, urinary biomarkers, and urothelial carcinoma risk: a case-control study - Chi-Jung Chung; Hui-Tsung Hsu; Chao-Hsiang Chang; Sheng-Wei Li; Chiu-Shong Liu; Mu-Chi Chung; Guo-Wei Wu; Wei-Ting Jung; Yen-Jung Kuo; Hui-Ling Lee (Environmental Science and Pollution Research, 2020)

Dynamic reconfiguration of functional brain networks supporting response inhibition in a stop-signal task - Bin Wang; Yaqing Hao; Qionghui Zhan; Shuo Zhao; Dandan Li; Sumaira Imtiaz; Jie Xiang; Jinglong Wu; Hidenao Fukuyama; Ting Yan (Brain Imaging and Behavior, 2020)

Long‐term effects of 7‐year warming experiment in the field on leaf hydraulic and economic traits of subtropical tree species - Ting Wu; David T. Tissue; Xu Li; Shizhong Liu; Guowei Chu; Guoyi Zhou; Yuelin Li; Mianhai Zheng; Ze Meng; Juxiu Liu (Global Change Biology, 2020)
Rising temperature associated with climate change may have substantial impacts on forest tree functions. We conducted a 7‐year warming experiment in subtropical China by translocating important native forest tree species ( Machilas breviflora , Syzygium rehderianum , Schima superba and Itea chinensis ) from cooler high‐elevation sites (600 m) to 1–2°C warmer low‐elevation sites (300 and 30 m) to investigate warming effects on leaf hydraulic and economic traits. Here, we report data from the last 3 years (Years 5–7) of the experiment. Warming increased leaf hydraulic conductance of S. superba to meet the higher evaporative demand. M. breviflora (300 m), S. rehderianum , S. superba and I. chinensis (300 and 30 m) exhibited higher area‐based and mass‐based maximum photosynthetic rates ( A a and A m , respectively) related to increasing stomatal conductance ( g s ) and stomatal density in the wet season, which led to rapid growth; however, we observed decreased growth of M. breviflora at 30 m due to lower stomatal density and decreased A a in the wet season. Warming increased photosynthetic nitrogen‐use efficiency and photosynthetic phosphorus‐use efficiency, but reduced leaf dry mass per unit area due to lower leaf thickness, suggesting that these tree species allocated more resources into upregulating photosynthesis rather than into structural investment. Our findings highlight that there was trait variation in the capacity of trees to acclimate to warmer temperatures such that I. chinensis may benefit from warming, but S. superba may be negatively influenced by warming in future climates.

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

Experimental investigation on the formation process of landslide dams and a criterion of river blockage - Ting-kai Nian; Hao Wu; Dong-yang Li; Wei Zhao; Kaoru Takara; De-feng Zheng (Landslides, 2020)

JAB1 promotes palmitate-induced insulin resistance via ERK pathway in hepatocytes - Yun Zhao; Suxian Ma; Xingna Hu; Min Feng; Rong Xiang; Min Li; Chenxiao Liu; Ting Lu; Aijie Huang; Jiaqi Chen; Mian Wu; Honghong Lu (Journal of Physiology and Biochemistry, 2020)

Structural Variability and Functional Prediction in the Epiphytic Bacteria Assemblies of Myriophyllum spicatum - Ling Xian; Tao Wan; Yu Cao; Junyao Sun; Ting Wu; Andrew Apudo Apudo; Wei Li; Fan Liu (Current Microbiology, 2020)

A photogrammetric method for laboratory-scale investigation on 3D landslide dam topography - Hao Wu; De-feng Zheng; Yan-jun Zhang; Dong-yang Li; Ting-kai Nian (Bulletin of Engineering Geology and the Environment, 2020)

Chronic minocycline treatment exerts antidepressant effect, inhibits neuroinflammation, and modulates gut microbiota in mice - Qi Yang; Li Luo; Ting Sun; Le Yang; Li-Fei Cheng; Yan Wang; Qing-Qing Liu; An Liu; Hai-Yan Liu; Ming-Gao Zhao; Sheng-Xi Wu; Bin Feng (Psychopharmacology, 2020)

Constraints of salinity- and sediment-induced stratification on the turbidity maximum in a tidal estuary - Ting Lu; Hao Wu; Fan Zhang; Jiasheng Li; Liang Zhou; Jianjun Jia; Zhanhai Li; Ya Ping Wang (Geo-Marine Letters, 2020)

Fine mapping of the Ca3GT gene controlling anthocyanin biosynthesis in mature unripe fruit of Capsicum annuum L. - Jinqiu Liu; Xiyin Ai; Yihao Wang; Qiaohua Lu; Ting Li; Lang Wu; Liang Sun; Huolin Shen (Theoretical and Applied Genetics, 2020)

SARS-CoV-2-encoded nucleocapsid protein acts as a viral suppressor of RNA interference in cells - Jingfang Mu; Jiuyue Xu; Leike Zhang; Ting Shu; Di Wu; Muhan Huang; Yujie Ren; Xufang Li; Qing Geng; Yi Xu; Yang Qiu; Xi Zhou (Science China Life Sciences, 2020)

Chopper Sugarcane Combine Harvester with Middle-Mounted Primary Extractor - Tao Wu; Xiao-Ling Liang; Qing-Ting Liu; Zeng-Xue Zhang; Hai Xu; Ji-Bai Huang; Jin-Xin Li; Xiao-Ping Zou (Sugar Tech, 2020)

Synergistic effects of pazopanib and hyperthermia against uterine leiomyosarcoma growth mediated by downregulation of histone acetyltransferase 1 - Chiao-Yun Lin; Angel Chao; Ren-Chin Wu; Li-Yu Lee; Shir-Hwa Ueng; Chia-Lung Tsai; Yun-Shien Lee; Meng-Ting Peng; Lan-Yan Yang; Huei-Jean Huang; Hsin-Shih Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2020)

Antifungal, anti-inflamatory and neuritogenic activity of newly-isolated compounds from Disporopsis aspersa - Fang-Li Gang; Feng Zhu; Chao-Fu Yang; Xiao-Ting Li; Hua Yang; Ming-Xia Sun; Wen-Jun Wu; Ji-Wen Zhang (Natural Product Research, 2020)

Genome-wide characterization and expression analysis of the auxin response factor (ARF) gene family during melon (Cucumis melo L.) fruit development - Bei Wu; Lu Wang; Gaoyang Pan; Ting Li; Xin Li; Jinghong Hao (Protoplasma, 2020)
ARFs in plants mediate auxin signaling transduction and regulate growth process. To determine genome-wide characterization of ARFs family in melon ( Cucumis melo L.), ARFs were identified via analysis of information within the melon genomic database, and bioinformatic analyses were performed using various types of software. Based on different treatment methods involving dipping with the growth regulator Fengchanji No. 2 and artificial pollination, Jingmi No. 11 melon was used as the test material, and melon plants with unpollinated ovaries served as controls. The expression of ARF s during the early development of melon was analyzed via qRT-PCR. Seventeen genes that encode ARF proteins were identified in the melon genome for the first time. The expression of these ARF s differed in different tissues. The expression levels of CmARF2 , CmARF16-like , CmARF18-like2 , and CmARF19-like were especially high in melon fruits. The expression of ARF s during the early development of melon fruits differed in response to the different treatments, which suggested that CmARF9 , CmARF16-like , CmARF19-like , CmARF19 , CmARF1 , CmARF2 , CmARF3 , and CmARF5 may be associated with melon fruit growth during early development. Interestingly, the increase in the transverse diameter of fruits treated with growth regulators was significantly greater than that of fruits resulting from artificial pollination, while the increase in the longitudinal diameter of the fruits resulting from artificial pollination was significantly greater.

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Phenotypic, genetic, and molecular function of msc-2, a genic male sterile mutant in pepper (Capsicum annuum L.) - Qing Cheng; Ting Li; Yixin Ai; Qiaohua Lu; Yihao Wang; Lang Wu; Jinqiu Liu; Liang Sun; Huolin Shen (Theoretical and Applied Genetics, 2020)

Hostaflavanol A, a new anti-inflammatory and antioxidant activities flavanol from the flowers of Hosta plantaginea - Li Yang; Yi-min Lin; Zhong-wei He; Ting-fang Zhang; Yu Li; Xiao-tong Xie; Yi-feng Wu; Jun-wei He (Medicinal Chemistry Research, 2020)

Major ions in drinking and surface waters from five cities in arid and semi-arid areas, NW China: spatial occurrence, water chemistry, and potential anthropogenic inputs - Xiaoping Li; Yu Zhang; Ting Wu; Xuemeng Sun; Tao Yang; Lijun Wang; Xiaoyu Li; Jingzhi Wang; Yanhua Wang; Hongtao Yu (Environmental Science and Pollution Research, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

The relationship among probabilistic, deterministic and potential skills in predicting the ENSO for the past 161 years - Ting Liu; Youmin Tang; Dejian Yang; Yanjie Cheng; Xunshu Song; Zhaolu Hou; Zheqi Shen; Yanqiu Gao; Yanling Wu; Xiaojing Li; Banglin Zhang (Climate Dynamics, 2019)
Here, we explored in depth the relationship among the deterministic prediction skill, the probabilistic prediction skill and the potential predictability. This was achieved by theoretical analyses and, in particular, by an analysis of long-term ensemble ENSO hindcast over 161 years from 1856 to 2016. First, a nonlinear monotonic relationship between the deterministic prediction skill and the probabilistic prediction skill, derived by theoretical analysis, was examined and validated using the ensemble hindcast. Further, the co-variability between the potential predictability and the deterministic prediction skill was explored in both perfect model assumption and actual model scenario. On these bases, we investigated the relationship between the potential predictability and probabilistic prediction skill from both the practice of ENSO forecast and theoretical perspective. The results of the study indicate that there are nonlinear monotonic relationships among these three kinds of measures. The potential predictability is considered to be a good indicator for the actual prediction skill in terms of both the deterministic measures and the probabilistic framework. The relationships identified here exhibit considerable significant practical sense to conduct predictability researches, which provide an inexpensive and moderate approach for inquiring prediction uncertainties without the requirement of costly ensemble experiments.

Environmentally persistent free radicals in PM2.5: a review - Mengxia Xu; Tao Wu; Yu-Ting Tang; Tong Chen; Lavrent Khachatryan; Poornima Ramesh Iyer; Dengting Guo; Anran Chen; Miao Lyu; Jinhu Li; Jiaqi Liu; Dan Li; et al. (Waste Disposal & Sustainable Energy, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Warming effects on leaf nutrients and plant growth in tropical forests - Ting Wu; Chao Qu; Yiyong Li; Xu Li; Guoyi Zhou; Shizhong Liu; Guowei Chu; Ze Meng; Zhiyang Lie; Juxiu Liu (Plant Ecology, 2019)

Distribution, source, and environmental risk assessment of phthalate esters (PAEs) in water, suspended particulate matter, and sediment of a typical Yangtze River Delta City, China - Hui Chen; Wei Mao; Yiqiu Shen; Weiwei Feng; Guanghua Mao; Ting Zhao; Lanqin Yang; Liuqing Yang; Chunfeng Meng; Yong Li; Xiangyang Wu (Environmental Science and Pollution Research, 2019)

Crystal Transformation of β-CD-MOF Facilitates Loading of Dimercaptosuccinic Acid - Yuehuai Xiong; Li Wu; Tao Guo; Caifen Wang; Wenting Wu; Yan Tang; Ting Xiong; Yong Zhou; Weifeng Zhu; Jiwen Zhang (AAPS PharmSciTech, 2019)

Quantification of cardiac pumping mechanics in rats by using the elastance–resistance model based solely on the measured left ventricular pressure and cardiac output - Chih-Hsien Wang; Ru-Wen Chang; En-Ting Wu; Chun-Yi Chang; Hsien-Li Kao; Ming-Shiou Wu; Ya-Jung Cheng; Yih-Sharng Chen; Kuo-Chu Chang (Pflügers Archiv - European Journal of Physiology, 2019)

Dynamics of oxytetracycline and resistance genes in soil under long-term intensive compost fertilization in Northern China - Ming Wu; Hui Han; Xiangnan Zheng; Mohan Bai; Ting Xu; Guo-chun Ding; Ji Li (Environmental Science and Pollution Research, 2019)

Combined expression and prognostic significance of PPFIA1 and ALG3 in head and neck squamous cell carcinoma - Hong Zhou; Ting Cao; Wen Ping Li; Gang Wu (Molecular Biology Reports, 2019)

Evaluation of the adsorption of ammonium-nitrogen and phosphate on a granular composite adsorbent derived from zeolite - Kun Wu; Yang Li; Ting Liu; Nan Zhang; Meng Wang; Shengjiong Yang; Wendong Wang; Pengkang Jin (Environmental Science and Pollution Research, 2019)

Biological perchlorate reduction: which electron donor we can choose? - Li He; Yu Zhong; Fubing Yao; Fei Chen; Ting Xie; Bo Wu; Kunjie Hou; Dongbo Wang; Xiaoming Li; Qi Yang (Environmental Science and Pollution Research, 2019)

Characterization of Cucurbita maxima Fruit Metabolomic Profiling and Transcriptome to Reveal Fruit Quality and Ripening Gene Expression Patterns - He-Xun Huang; Ting Yu; Jun-Xing Li; Shu-Ping Qu; Man-Man Wang; Ting-Quan Wu; Yu-Juan Zhong (Journal of Plant Biology, 2019)

Time-dependent shake map for Uttarakhand Himalayas, India, using recorded earthquakes - Himanshu Mittal; Yih-Min Wu; Ting-Li Lin; Cédric P. Legendre; Sushil Gupta; Benjamin M. Yang (Acta Geophysica, 2019)

An aseptic rapid propagation system for obtaining plumbagin of Ceratostigma willmottianum Stapf - Ju Hu; Suping Gao; Shiliang Liu; Meiting Hong; Yuan Zhu; Yichao Wu; Di Hu; Li Zhang; Ting Lei (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Using the seasonal FGM(1,1) model to predict the air quality indicators in Xingtai and Handan - LF Wu; Nu Li; Ting Zhao (Environmental Science and Pollution Research, 2019)

The antitoxin MqsA homologue in Pseudomonas fluorescens 2P24 has a rewired regulatory circuit through evolution - Yong Wang; Si‐Ping Zhang; Meng‐Yuan Zhang; Megan L. Kempher; Ding‐Ding Guo; Jian‐Ting Han; Xuanyu Tao; Yi Wu; Li‐Qun Zhang; Yong‐Xing He (Environmental Microbiology, 2019)
Summary The mqsRA operon encodes a toxin–antitoxin pair that was characterized to participate in biofilm and persister cell formation in Escherichia coli . Notably, the antitoxin MqsA possesses a C‐terminal DNA‐binding domain that recognizes the [5’‐AACCT(N) 2‐4 AGGTT‐3′] motif and acts as a transcriptional regulator controlling multiple genes including the general stress response regulator RpoS. However, it is unknown how the transcriptional circuits of MqsA homologues have changed in bacteria over evolutionary time. Here, we found mqsA in Pseudomonas fluorescens ( PfmqsA ) is acquired through horizontal gene transfer and binds to a slightly different motif [5′‐TACCCT(N) 3 AGGGTA‐3′], which exists upstream of the PfmqsRA operon. Interestingly, an adjacent GntR‐type transcriptional regulator, which was termed AgtR, is under negative control of PfMqsA. It was further demonstrated that PfMqsA reduces production of biofilm components through AgtR, which directly regulates the pga and fap operons involved in the synthesis of extracellular polymeric substances. Moreover, through quantitative proteomics analysis, we showed AgtR is a highly pleiotropic regulator that influences up to 252 genes related to diverse processes including chemotaxis, oxidative phosphorylation and carbon and nitrogen metabolism. Taken together, our findings suggest the rewired regulatory circuit of PfMqsA influences diverse physiological aspects of P. fluorescens 2P24 via the newly characterized AgtR.

Arrangement of High-standard Basic Farmland Construction Based on Village-region Cultivated Land Quality Uniformity - Wen Song; Kening Wu; Huafu Zhao; Rui Zhao; Ting Li (Chinese Geographical Science, 2019)

Dynamic monitoring of resuspension in the multiple eco-types of the littoral zone of a shallow wind-disturbed lake - Chuang Qi; Yang Zhou; Xiao-guang Xu; Li-min Zhang; Hui Lin; Xin-ting Wu; Kuan Shi; Guo-xiang Wang (Aquatic Sciences, 2019)

Invasive Spartina alterniflora exhibits increased resistance but decreased tolerance to a generalist insect in China - Rui-Ting Ju; Ding Ma; Evan Siemann; Xiang Liu; Ji-Hua Wu; Bo Li (Journal of Pest Science, 2019)

In situ resuspension rate monitoring method in the littoral zone with multi-ecotypes of a shallow wind-disturbed lake - Chuang Qi; Xiao-guang Xu; Kuan Shi; Li-min Zhang; Yang Zhou; Hui Lin; Xin-ting Wu; Guo-xiang Wang; Han Meng (Environmental Science and Pollution Research, 2019)

Neuregulin-1β attenuates sepsis-induced diaphragm atrophy by activating the PI3K/Akt signaling pathway - Jin Wu; Hua Liu; Ting Chu; Peng Jiang; Shi-tong Li (Journal of Muscle Research and Cell Motility, 2019)

Novel mutation of type-1 insulin-like growth factor receptor (IGF-1R) gene in a severe short stature pedigree identified by targeted next-generation sequencing - Yu Yang; Hui Huang; Ka Chen; Li Yang; Li-ling Xie; Ting Xiong; Xian Wu (Journal of Genetics, 2019)

Contribution of Cathepsin L to Autolysis of Sea Cucumber Stichopus japonicus Intestines - Jia-Nan Yan; Xiao-Kun Guo; Yue Tang; Ao-Ting Li; Zhi-Mo Zhu; Xiao-Qian Chai; Xiu-Hong Duan; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2019)

Selenium Biofortification and Antioxidant Activity in Cordyceps militaris Supplied with Selenate, Selenite, or Selenomethionine - Ting Hu; Yue Liang; Guishen Zhao; Wenliang Wu; Huafen Li; Yanbin Guo (Biological Trace Element Research, 2019)

Influence of Chronic Toxicity, Lipid Metabolism, Learning and Memory Ability, and Related Enzyme in Sprague-Dawley Rats by Long-Term Chromium Malate Supplementation - Weiwei Feng; Qian Li; Wei Wang; Yao Chen; Weijie Zhang; Ting Zhao; Guanghua Mao; Xiangyang Wu; Liuqing Yang (Biological Trace Element Research, 2019)

Arctic Climate Changes Based on Historical Simulations (1900‒2013) with the CAMS-CSM - Ting Wei; Jian Li; Xinyao Rong; Wenjie Dong; Bingyi Wu; Minghu Ding (Journal of Meteorological Research, 2018)

Two new alkylated furan derivatives with antifungal and antibacterial activities from the plant endophytic fungus Emericella sp. XL029 - Xia Wu; Xue-Jiao Pang; Lu-Lin Xu; Ting Zhao; Xin-Yu Long; Qiong-Yin Zhang; Hai-Li Qin; Deng-Feng Yang; Xiao-Long Yang (Natural Product Research, 2018)

Abnormal intrinsic cerebro-cerebellar functional connectivity in un-medicated patients with bipolar disorder and major depressive disorder - Yuan He; Ying Wang; Ting-Ting Chang; Yanbin Jia; Junjing Wang; Shuming Zhong; Huiyuan Huang; Yao Sun; Feng Deng; Xiaoyan Wu; Chen Niu; Li Huang; et al. (Psychopharmacology, 2018)

Immobilization of heavy metals in two contaminated soils using a modified magnesium silicate stabilizer - Xingzhong Yuan; Ting Xiong; Hou Wang; Zhibin Wu; Longbo Jiang; Guangming Zeng; Yue Li (Environmental Science and Pollution Research, 2018)

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor of 30-Day Mortality of Intracerebral Hemorrhage Patients: a Validation Cohort Study - Fei Wang; Li Wang; Ting-ting Jiang; Jian-jun Xia; Feng Xu; Li-juan Shen; Wen-hui Kang; Yong Ding; Li-xia Mei; Xue-feng Ju; Shan-you Hu; Xiao Wu (Neurotoxicity Research, 2018)

Sex Differences in Neuropathology and Cognitive Behavior in APP/PS1/tau Triple-Transgenic Mouse Model of Alzheimer’s Disease - Jun-Ting Yang; Zhao-Jun Wang; Hong-Yan Cai; Li Yuan; Meng-Ming Hu; Mei-Na Wu; Jin-Shun Qi (Neuroscience Bulletin, 2018)

Absorption, translocation, and detoxification of Cd in two different castor bean (Ricinus communis L.) cultivars - Wenling Ye; Guifeng Guo; Fan Wu; Ting Fan; Hongjuan Lu; Haiyan Chen; Xuede Li; Youhua Ma (Environmental Science and Pollution Research, 2018)

Chromium malate alleviates high-glucose and insulin resistance in L6 skeletal muscle cells by regulating glucose uptake and insulin sensitivity signaling pathways - Weiwei Feng; Yangyang Ding; Weijie Zhang; Yao Chen; Qian Li; Wei Wang; Hui Chen; Yun Feng; Ting Zhao; Guanghua Mao; Liuqing Yang; Xiangyang Wu (BioMetals, 2018)

The relative abundance of alkane‐degrading bacteria oscillated similarly to a sinusoidal curve in an artificial ecosystem model from oil‐well products - Guoqiang Li; Peike Gao; Bo Zhi; Bing Fu; Ge Gao; Zhaohui Chen; Mengli Gao; Mengmeng Wu; Ting Ma (Environmental Microbiology, 2018)
Summary Microbial phylogenetic diversity and species interactions in natural ecosystems have been investigated extensively, but our knowledge about their ecological roles, community dynamics and succession patterns is far from complete. This knowledge is essential to understand the complicated interactions of microorganisms in natural ecosystems. Here, an artificial ecosystem model of microorganisms was constructed from oil‐well products and cultivated in a chemostat to investigate the succession pattern of alkane‐degrading bacteria, a functional population in oil reservoirs. Their abundance was quantified by an improved qPCR technique. Our results showed that the phylogenetic structure of this artificial ecosystem model is stable during most of the chemostat cultivation process, while the genotype structure of alkane‐degrading bacteria containing alk B genes shifted and their relative abundance oscillated similarly to a sinusoidal curve, like the succession pattern of producers in the Lotka–Volterra model. These results suggest that some theoretical frameworks of macroecology may work well in microbial ecosystems and be an efficient tool to understand them.

Negative regulation of MAVS-mediated innate immune response by ASC - Yue Han; Xiang He; Congwen Wei; Ting Song; Ling Zou; Zihui Li; Jiazhou Ye; Lunan Qi; Lequn Li; Hui Zhong; Feixiang Wu (Molecular and Cellular Biochemistry, 2018)

Variation in accumulation, transport, and distribution of phthalic acid esters (PAEs) in soil columns grown with low- and high-PAE accumulating rice cultivars - Yang Wu; Xue-Xue Chen; Ting-Kai Zhu; Xing Li; Xiao-Hong Chen; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

River habitat assessment for ecological restoration of Wei River Basin, China - Tao Yang; Shuo Wang; Xiaoping Li; Ting Wu; Li Li; Jia Chen (Environmental Science and Pollution Research, 2018)

Synthesis, crystal structure, and antinociceptive effects of some new riluzole derivatives - Xiang-Long Wu; Liu Liu; You-Jia Li; Jie Luo; Dong-Wei Gai; Ting-Li Lu; Qi-Bing Mei (Medicinal Chemistry Research, 2018)

Occurrence and health risk assessment of organotins in waterworks and the source water of the Three Gorges Reservoir Region, China - Ting Deng; Lei Wu; Jun-Min Gao; Bin Zhou; Ya-Li Zhang; Wen-Nan Wu; Zhuo-Heng Tang; Wen-Chao Jiang; Wei-Lin Huang (Environmental Science and Pollution Research, 2018)

Isolation and identification of bovine nasopharyngeal mucosal epithelial cells and establishment of cell models of acute infection by foot-and-mouth disease virus - Wan-fu Bai; Lu Li; Ting Zhang; Xiao-hu Su; Yong-wei Wang; Bing-wu Zhao; Tao Zhang; Huan-min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2018)

Long-term agronomic practices alter the composition of asymbiotic diazotrophic bacterial community and their nitrogen fixation genes in an acidic red soil - Weibing Xun; Wei Li; Ting Huang; Yi Ren; Wu Xiong; Youzhi Miao; Wei Ran; Dongchu Li; Qirong Shen; Ruifu Zhang (Biology and Fertility of Soils, 2018)

In Situ Observation of Hard Surrounding Rock Displacement at 2400-m-Deep Tunnels - Xia-Ting Feng; Zhi-Bin Yao; Shao-Jun Li; Shi-Yong Wu; Cheng-Xiang Yang; Hao-Sen Guo; Shan Zhong (Rock Mechanics and Rock Engineering, 2018)

Molecular characterization and tissue expression profiles of insulin-like growth factor binding protein-1 (IGFBP-1) in Chinese alligator Alligator sinensis during the active and hibernating periods - Mengyun Li; Ting Meng; Fei Peng; Shengzhou Zhang; Yongkang Zhou; Xiaobing Wu (Biologia, 2018)

Epigenetic modification of TLE1 induce abnormal differentiation in diabetic mice intestinal epithelium - Ji-hao Xu; Guang-cheng Chen; Can-ze Huang; Di Cheng; Ting-feng Wu; Si-yi Wang; Jie-yao Li; Tao Yu; Qi-kui Chen (Molecular and Cellular Biochemistry, 2018)

Viral metagenomics of six bat species in close contact with humans in southern China - Xue-yan Zheng; Min Qiu; Wei-jie Guan; Jin-ming Li; Shao-wei Chen; Ming-ji Cheng; Shu-ting Huo; Zhong Chen; Yi Wu; Li-na Jiang; Qing Chen (Archives of Virology, 2018)

Rare earth elements in street dust and associated health risk in a municipal industrial base of central China - Guangyi Sun; Zhonggen Li; Ting Liu; Ji Chen; Tingting Wu; Xinbin Feng (Environmental Geochemistry and Health, 2017)

Assessment of tidal range energy resources based on flux conservation in Jiantiao Bay, China - Min Du; He Wu; Huaming Yu; Ting Lv; Jiangyu Li; Yujun Yu (Journal of Ocean University of China, 2017)

Comprehensive risk assessment and source identification of selected heavy metals (Cu, Cd, Pb, Zn, Hg, As) in tidal saltmarsh sediments of Shuangtai Estuary, China - Chang-Fa Liu; Bing Li; Yi-Ting Wang; Yuan Liu; Heng-Jiang Cai; Hai-Feng Wei; Jia-Wen Wu; Jin Li (Environmental Monitoring and Assessment, 2017)

20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol negatively regulates activation of STAT3 and ERK pathways and exhibits anti-cancer effects in HepG2 cells - Hui-Han Ai; Zi-Long Zhou; Lu-Guo Sun; Mei-Ting Yang; Wei Li; Chun-Lei Yu; Zhen-Bo Song; Yan-Xin Huang; Yin Wu; Lei Liu; Xiao-Guang Yang; Yu-Qing Zhao; et al. (Apoptosis, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Characterization of a new isolate of pepper chlorotic spot virus from Yunnan province, China - Kuanyu Zheng; Tsung-Chi Chen; Shyi-Dong Yeh; Md. Siddiqur Rahman; Xiaoxia Su; Kuo Wu; Ting Li; Zhongkai Zhang; Jiahong Dong (Archives of Virology, 2017)

Potential toxic trace element (PTE) contamination in Baoji urban soil (NW China): spatial distribution, mobility behavior, and health risk - Xiaoping Li; Ting Wu; Hongxiang Bao; Xianyu Liu; Changlin Xu; Yanan Zhao; Dongying Liu; Hongtao Yu (Environmental Science and Pollution Research, 2017)

Complete genome sequence of a new isolate of potato virus M in Yunnan, China - Xiaoxia Su; Kuo Wu; Li Zhen Zhang; Mohammad Siddiqur Rahman; Kuanyu Zheng; Ting Li; Zhongkai Zhang; Jiahong Dong (Archives of Virology, 2017)

Evaluation of the antioxidant property and effects in Caenorhabditis elegans of Xiangxi flavor vinegar, a Hunan local traditional vinegar - Run-ting Huang; Qing Huang; Gen-liang Wu; Chun-guang Chen; Zong-jun Li (Journal of Zhejiang University-SCIENCE B, 2017)

Nr3C1-Bhlhb2 Axis Dysregulation Is Involved in the Development of Attention Deficit Hyperactivity - Li Hui Wu; Wei Cheng; Mei Yu; Bao Mei He; Hui Sun; Qi Chen; Yi Wei Dong; Xiao Ting Shao; Qian Qian Cai; Min Peng; Xing Zhong Wu (Molecular Neurobiology, 2017)

Vimentin is important in the neural differentiation of PC12 cells promoted by sialylation - Li Hui Wu; Xiao Ting Shao; Jun Xia Guo; Hui Sun; Qi Chen; Jing Pan; Qian Qian Cai; Yi Wei Dong; Zhong Yi Chen; Xiao Mei Yan; Min Peng; Nanbert Zhong; et al. (Glycoconjugate Journal, 2017)

Purified isolation of vacuoles from Sedum alfredii leaf-derived protoplasts - Xiao-yu Gao; Xing-cheng Liao; Ruo-lai Wu; Ting Liu; Hai-xing Wang; Ling-li Lu (Journal of Zhejiang University-SCIENCE B, 2017)

Development of high-density interspecific genetic maps for the identification of QTLs conferring resistance to Valsa ceratosperma in apple - Yi Tan; Song Lv; Xinying Liu; Ting Gao; Tianhong Li; Yi Wang; Ting Wu; Xinzhong Zhang; Yuepeng Han; Schuyler S. Korban; Zhenhai Han (Euphytica, 2017)

A new armored archosauriform (Diapsida: Archosauromorpha) from the marine Middle Triassic of China, with implications for the diverse life styles of archosauriforms prior to the diversification of Archosauria - Chun Li; Xiao-chun Wu; Li-jun Zhao; Sterling J. Nesbitt; Michelle R. Stocker; Li-Ting Wang (The Science of Nature, 2016)

Analgesic Effects of Danggui-Shaoyao-San on Various “Phenotypes” of Nociception and Inflammation in a Formalin Pain Model - Jun-Bin Yin; Ke-Cheng Zhou; Huang-Hui Wu; Wei Hu; Tan Ding; Ting Zhang; Li-Ying Wang; Jun-Ping Kou; Alan David Kaye; Wen Wang (Molecular Neurobiology, 2016)

The status evaluation of the permafrost environment along the Chaida’er-Muli Railway in southern Qilian Mountains in northern Qinghai Province, China - Wei Cao; Yu Sheng; Ya-ling Chou; Ji-chun Wu; Jing Li; Sheng-ting Wang (Journal of Mountain Science, 2016)

Mineral and pore structure characteristics of gas shale in Longmaxi formation: a case study of Jiaoshiba gas field in the southern Sichuan Basin, China - Liang Wang; Yonghong Fu; Jun Li; Liqiang Sima; Qingzhao Wu; Wujun Jin; Ting Wang (Arabian Journal of Geosciences, 2016)

Influence of genetic polymorphisms in cytochrome P450 oxidoreductase on the variability in stable warfarin maintenance dose in Han Chinese - Wu-Tao Zeng; Qing Xu; Cheng-Hsun Li; Wei-Yan Chen; Xiu-Ting Sun; Xiang Wang; Yi-Ying Yang; Hui Shi; Zhi-Sheng Yang (European Journal of Clinical Pharmacology, 2016)

Transgenesis of Agrobacterium rhizogenes K599 orf3 into plant alters plant phenotype to dwarf and branch - Shasha Wang; Yaling Song; Taihe Xiang; Pan Wu; Ting Zhang; Daze Wu; Shuyu Zhou; Yafei Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Ethanol Increases Mechanical Pain Sensitivity in Rats via Activation of GABAA Receptors in Medial Prefrontal Cortex - Kai-Wen Geng; Ting He; Rui-Rui Wang; Chun-Li Li; Wen-Jun Luo; Fang-Fang Wu; Yan Wang; Zhen Li; Yun-Fei Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Erratum to: Initiation and evolution of the South China Sea: an overview - Wei-dong Sun; Chiou-ting Lin; Chan-chan Zhang; Yong-bin Hu; Ming-xing Ling; Xing Ding; Cong-ying Li; He Li; Kai Wu; Wei-ming Fan (Acta Geochimica, 2016)

Investigation of diarrhetic shellfish toxins in Lingshan Bay, Yellow Sea, China, using solid-phase adsorption toxin tracking (SPATT) - Feng-Ling Li; Zhao-Xin Li; Meng-Meng Guo; Hai-Yan Wu; Ting-Ting Zhang; Cai-Hu Song (Food Additives & Contaminants: Part A, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Reconstructing paleoatmospheric CO2 levels based on fossil Ginkgoites from the Upper Triassic and Middle Jurassic in Northwest China - Jing-yu Wu; Su-ting Ding; Qi-jia Li; Bai-nian Sun; Yong-dong Wang (PalZ, 2016)

Improved production of carotenoid-free welan gum in a genetic-engineered Alcaligenes sp. ATCC31555 - Wenwen Zhang; Zhaohui Chen; Mengmeng Wu; Zhong Shi; Feng Zhu; Guoqiang li; Ting Ma (Biotechnology Letters, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Silibinin Prevents Autophagic Cell Death upon Oxidative Stress in Cortical Neurons and Cerebral Ischemia-Reperfusion Injury - Min Wang; Yu-Jiao Li; Yi Ding; Hui-Nan Zhang; Ting Sun; Kun Zhang; Le Yang; Yan-Yan Guo; Shui-Bing Liu; Ming-Gao Zhao; Yu-Mei Wu (Molecular Neurobiology, 2016)

Construction of a high density linkage map and its application in the identification of QTLs for soluble sugar and organic acid components in apple - Baiquan Ma; Shuang Zhao; Benhong Wu; Dongmei Wang; Qian Peng; Albert Owiti; Ting Fang; Liao Liao; Collins Ogutu; Schuyler S. Korban; Shaohua Li; Yuepeng Han (Tree Genetics & Genomes, 2016)

Complete genome sequence of a distinct calla lily chlorotic spot virus isolated in mainland China - Ye Xu; Si-bo Wang; Yong-zhong Li; Hong-zheng Tao; Ya-ning Huang; Bao-wei Wu; Yu-mei Dong; John Hu; Ya-ting Liu (Archives of Virology, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Advanced oxidation protein products induce chondrocyte apoptosis via receptor for advanced glycation end products-mediated, redox-dependent intrinsic apoptosis pathway - Qian Wu; Zhao-Ming Zhong; Si-Yuan Zhu; Cong-Rui Liao; Ying Pan; Ji-Huan Zeng; Shuai Zheng; Ruo-Ting Ding; Qing-Song Lin; Qing Ye; Wen-Bin Ye; Wei Li; et al. (Apoptosis, 2016)

Protective Effect of Porcine Cerebral Hydrolysate Peptides on Learning and Memory Deficits and Oxidative Stress in Lead-Exposed Mice - Ye Zou; Weiwei Feng; Wei Wang; Yao Chen; Zhaoxiang Zhou; Qian Li; Ting Zhao; Guanghua Mao; Xiangyang Wu; Liuqing Yang (Biological Trace Element Research, 2015)

Influence of the Ring Size on the Binding Ability of FTO Investigated by Fluorescence Spectroscopy - Wu He; Zhigang Li; Lingling Yang; Qingwei Jiang; Ting Ren; Lijiao Zhang; Zhenhua Shen; Qinghua Yang; Ruiyong Wang; Junbiao Chang (Journal of Fluorescence, 2015)

Evaluation of 90-day Repeated Dose Oral Toxicity, Glycometabolism, Learning and Memory Ability, and Related Enzyme of Chromium Malate Supplementation in Sprague-Dawley Rats - Weiwei Feng; Huiyu Wu; Qian Li; Zhaoxiang Zhou; Yao Chen; Ting Zhao; Yun Feng; Guanghua Mao; Fang Li; Liuqing Yang; Xiangyang Wu (Biological Trace Element Research, 2015)

Chemical composition, antioxidant and cytoprotective activities of lotus receptacle - Weicheng Hu; Gongcheng Wang; Ting Shen; Yuning Wang; Boran Hu; Xinfeng Wang; Lei Wu; Pengxia Li; Lilian Ji (Horticulture, Environment, and Biotechnology, 2015)

HAP1 helps to regulate actin-based transport of insulin-containing granules in pancreatic β cells - Zhiyong Wang; Ting Peng; Hongnian Wu; Jun He; He Li (Histochemistry and Cell Biology, 2015)

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

Proteome analysis of pear reveals key genes associated with fruit development and quality - Jia Ming Li; Xiao San Huang; Lie Ting Li; Dan Man Zheng; Cheng Xue; Shao Ling Zhang; Jun Wu (Planta, 2015)

Construction of a High-Density Simple Sequence Repeat Consensus Genetic Map for Pear (Pyrus spp.) - Hui Chen; Yue Song; Lei-Ting Li; M. Awais Khan; Xiu-Gen Li; Schuyler S. Korban; Jun Wu; Shao-Ling Zhang (Plant Molecular Biology Reporter, 2015)

Genome-Wide Identification, Expression, and Activity Analysis of Alkaline/Neutral Invertase Gene Family from Cassava (Manihot esculenta Crantz) - Yuan Yao; Meng-Ting Geng; Xiao-Hui Wu; Jiao Liu; Rui-Mei Li; Xin-Wen Hu; Jian-Chun Guo (Plant Molecular Biology Reporter, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Effects of Triterpenoid From Schisandra chinensis on Oxidative Stress in Alcohol-Induced Liver Injury in Rats - Bin Li; Lijie Zhu; Ting Wu; Jiachen Zhang; Xinyao Jiao; Xiuying Liu; Yanqun Wang; Xianjun Meng (Cell Biochemistry and Biophysics, 2015)

Preparation and Characterization of Protein Hydrolysates From Little Loligo Squid ( Uroteuthis chinensis ) - Yu-xue Wu; Wang Li; Ting Jin (Journal of Aquatic Food Product Technology, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Secretomes are a potential source of molecular targets for cancer therapies and indicate that APOE is a candidate biomarker for lung adenocarcinoma metastasis - Zan Liu; Yuan Gao; Fengxia Hao; Xiaomin Lou; Xiuwei Zhang; Yang Li; Di Wu; Ting Xiao; Longhai Yang; Qingchang Li; Xueshan Qiu; Enhua Wang (Molecular Biology Reports, 2014)

An updated view on the differentiation of stem cells into endothelial cells - YiJiang Zhou; Feng Yang; Ting Chen; YuTao Wu; Mei Yang; JianHua Zhu; Li Zhang (Science China Life Sciences, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

Oxidative Stress and Autophagic Alteration in Brainstem of SOD1-G93A Mouse Model of ALS - Ting An; Pengxiao Shi; Weisong Duan; Shipan Zhang; Pin Yuan; Zhongyao Li; Dongxia Wu; Zuoshang Xu; Chunyan Li; Yansu Guo (Molecular Neurobiology, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

An α-glucan isolated from root of Isatis Indigotica, its structure and adjuvant activity - Junjie Shan; Guohui Sun; Jinwei Ren; Ting Zhu; Peiyuan Jia; Wensheng Qu; Qian Li; Junhua Wu; Hao Ma; Song Wen; Yuxia Wang (Glycoconjugate Journal, 2014)

Identification of microRNA-18a as a novel regulator of the insulin-like growth factor-1 in the proliferation and regeneration of deer antler - Wei Hu; Ting Li; Lei Wu; Mu Li; Xingyu Meng (Biotechnology Letters, 2014)

The relationship between typhoons' peripheral circulation and ground-level ozone concentrations in central Taiwan - Wan-Li Cheng; Li-Wei Lai; Walter Den; Meng-Ting Wu; Chao-An Hsueh; Pay-Liam Lin; Chueh-Ling Pai; Yeou-Lih Yan (Environmental Monitoring and Assessment, 2014)

Left hemiparalexia of Chinese characters: neglect dyslexia or disruption of pathway of visual word form processing? - Wenchao Yi; Ting Wu; Wei Chen; Ti-fei Yuan; Benyan Luo; Chunlei Shan; Jianan Li; Sheng He; Xuchu Weng (Brain Structure and Function, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Up-regulation of Slc39A2(Zip2) mRNA in peripheral blood mononuclear cells from patients with pulmonary tuberculosis - Yan-ting Tao; Qing Huang; Ya-li Jiang; Xiao-lei Wang; Ping Sun; Yuanyuan Tian; Hai-liang Wu; Min Zhang; Si-bo Meng; Yu-shu Wang; Qing Sun; Lian-ying Zhang (Molecular Biology Reports, 2013)

Altered methylation of IGF2 DMR0 is associated with neural tube defects - Lihua Wu; Li Wang; Shaofang Shangguan; Shaoyan Chang; Zhen Wang; Xiaolin Lu; Qin Zhang; Jianhua Wang; Huizhi Zhao; Fang Wang; Jin Guo; Bo Niu; et al. (Molecular and Cellular Biochemistry, 2013)

Cloning, expression and characterization of a phosphoglucomutase/phosphomannomutase from sphingan-producing Sphingomonas sanxanigenens - Haidong Huang; Xiaoyan Li; Mengmeng Wu; Shengxiu Wang; Guoqiang Li; Ting Ma (Biotechnology Letters, 2013)

Edaravone Ameliorates Oxidative Damage Associated with Aβ25-35 Treatment in PC12 Cells - Gui-lian Zhang; Wang-gang Zhang; Yun Du; Li Yao; Hong Sun; Ru Zhang; Enqi Liu; Ning Bu; Hai-qin Wu; Lei Zhang; Ting-ting Li; Ying-ying Guo (Journal of Molecular Neuroscience, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Differential responses of Abies fabri and Rhododendron calophytum at two sites with contrasting pollution deposition and available calcium in southwestern China - Fei-Hua Wu; Juan Chen; Ting-Wu Liu; Zhen-Ji Li; Juan Chen; Lei Chen; Shao-Hua Guan; Tong-Yang Li; Xue-Jun Dong; Janet Patton; Hai-Lei Zheng (Plant Ecology, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

Functional expression of ERG1 potassium channels in rat alveolar macrophages - Haiying Dong; Zhenyu Ji; Manling Liu; Yanxia Wang; Xiao Bai; Ting Wang; Zidong Liu; Yousheng Wu; Bo Zhang; Ying Luo; Zhichao Li; Mingqing Dong (Journal of Molecular Histology, 2013)

Drug–drug interaction of rabeprazole and clopidogrel in healthy Chinese volunteers - Jia Wu; Li-Tao Jia; Li-Ming Shao; Jia-Min Chen; Dan-Dan Zhong; Song Xu; Jian-Ting Cai (European Journal of Clinical Pharmacology, 2013)

Ectopic overexpression of porcine DGAT1 increases intramuscular fat content in mouse skeletal muscle - Ting Li; Dequan Xu; Bo Zuo; Minggang Lei; Yuanzhu Xiong; Hongxing Chen; Yanhong Zhou; Xiaojie Wu (Transgenic Research, 2013)

Geographic and Tissue Influences on Endophytic Fungal Communities of Taxus chinensis var. mairei in China - Lingshang Wu; Ting Han; Wenchao Li; Min Jia; Liming Xue; Khalid Rahman; Luping Qin (Current Microbiology, 2013)

RETRACTED ARTICLE: A 2-D DIGE analysis of simulated acid rain-responsive proteins in Pinus massoniana needles - Ting-Wu Liu; Wen-Jun Hu; Xiao-Qin Wang; Li Niu; Bin Fu; Fei-Hua Wu; Zhen-Ming Pei; Hai-Lei Zheng (Trees, 2012)

Cloning and Characterization of MxVHA-c, a Vacuolar H+-ATPase Subunit C Gene Related to Fe Efficiency from Malus xiaojinensis - Qian Zhang; Yi Wang; Xin Zhong Zhang; Li Li Yin; Ting Wu; Xue Feng Xu; Wen Suo Jia; Zhen Hai Han (Plant Molecular Biology Reporter, 2012)

Primary culture of hemocytes from Eriocheir sinensis and their immune effects to the novel crustacean pathogen Spiroplasma eriocheiris - Tingming Liang; Hong Ji; Jie Du; Jiangtao Ou; Wenjie Li; Ting Wu; Qingguo Meng; Wei Gu; Wen Wang (Molecular Biology Reports, 2012)

Sequence and phylogenetic analysis of H7N3 avian influenza viruses isolated from poultry in China in 2011 - Wu Hai-bo; Lu Ru-feng; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Xu Li-hua; Wu Nan-ping; Guo Chao-tan (Archives of Virology, 2012)

Enhanced Anti-Diabetic Activity of a Combination of Chromium(III) Malate Complex and Propolis and its Acute Oral Toxicity Evaluation - Xiang-Yang Wu; Fang Li; Ting Zhao; Guang-Hua Mao; Jing Li; Hong-Yuan Qu; Yue-Na Ren; Liu-Qing Yang (Biological Trace Element Research, 2012)

Genetic characterization of subtype H1 avian influenza viruses isolated from live poultry markets in Zhejiang Province, China, in 2011 - Hai-bo Wu; Chao-tan Guo; Ru-feng Lu; Li-hua Xu; En-kang Wo; Jin-biao You; Yi-ting Wang; Qiao-gang Wang; Nan-ping Wu (Virus Genes, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Characterization of a highly pathogenic H5N1 avian influenza virus isolated from ducks in Eastern China in 2011 - Wu Hai-bo; Guo Chao-tan; Lu Ru-feng; Xu Li-hua; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Wu Nan-ping (Archives of Virology, 2012)

Altered Methylation of the DNA Repair Gene MGMT Is Associated with Neural Tube Defects - Susanna Tran; Li Wang; Jing Le; Jing Guan; Lihua Wu; Jizhen Zou; Zhen Wang; Jianhua Wang; Fang Wang; Xiaoli Chen; Lingling Cai; Xiaolin Lu; et al. (Journal of Molecular Neuroscience, 2012)

Glutamate carboxypeptidase II gene polymorphisms and neural tube defects in a high-risk Chinese population - Hua Xie; Jin Guo; Jianhua Wang; Fang Wang; Huizhi Zhao; Chi Liu; Li Wang; Xiaolin Lu; Lihua Wu; Yihua Bao; Jizhen Zou; Ting Zhang; et al. (Metabolic Brain Disease, 2012)

Effects of average velocity on the growth and surface topography of biofilms attached to the reclaimed wastewater drip irrigation system laterals - Gui Bing Li; Yun Kai Li; Ting Wu Xu; Yao Ze Liu; Hai Jin; Pei Ling Yang; Da Zhuang Yan; Shu Mei Ren; Zhi Fang Tian (Irrigation Science, 2012)

Surface topographic characteristics of suspended particulates in reclaimed wastewater and effects on clogging in labyrinth drip irrigation emitters - Yun Kai Li; Yao Ze Liu; Gui Bing Li; Ting Wu Xu; Hai Sheng Liu; Shu Mei Ren; Da Zhuang Yan; Pei Ling Yang (Irrigation Science, 2012)

Response of Soybean Seed Germination to Cadmium and Acid Rain - Ting Ting Liu; Peng Wu; Li Hong Wang; Qing Zhou (Biological Trace Element Research, 2011)

Anti-hyperglycemic Activity of Chromium(III) Malate Complex in Alloxan-Induced Diabetic Rats - Xiang-Yang Wu; Fang Li; Wei-Dong Xu; Jiang-Li Zhao; Ting Zhao; Ling-Hong Liang; Liu-Qing Yang (Biological Trace Element Research, 2011)

Prevalence, intensity and associated factor analysis of Tropilaelaps mercedesae infesting Apis mellifera in China - Qi Hua Luo; Ting Zhou; Ping Li Dai; Huai Lei Song; Yan Yan Wu; Qiang Wang (Experimental and Applied Acarology, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

A regional ocean reanalysis system for coastal waters of China and adjacent seas - Guijun Han; Wei Li; Xuefeng Zhang; Dong Li; Zhongjie He; Xidong Wang; Xinrong Wu; Ting Yu; Jirui Ma (Advances in Atmospheric Sciences, 2011)

Establishment of a cerebral schistosomiasis experimental model in rabbits - Peng Wang; Dan Wang; Shi-Jie Chen; Ming-Can Wu; Xiang-Lin Cheng; Jun-Chuan Li; Ting-Xuan Chen; Zhan-Sheng Zhu (Neuroscience Bulletin, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Development, characterization, and cross-species/genera transferability of SSR markers for rubber tree (Hevea brasiliensis) - Fei Yu; Bao-Hua Wang; Su-Ping Feng; Jing-Yi Wang; Wei-Guo Li; Yao-Ting Wu (Plant Cell Reports, 2011)

Microarray analysis of the gene expression profile in the midgut of silkworm infected with cytoplasmic polyhedrosis virus - Ping Wu; Xiu Wang; Guang-xing Qin; Ting Liu; Yun-Feng Jiang; Mu-Wang Li; Xi-Jie Guo (Molecular Biology Reports, 2011)

Groundwater environmental capacity and its evaluation index - Li Ting Xing; Qiang Wu; Chun He Ye; Nan Ye (Environmental Monitoring and Assessment, 2010)

Isolation and characterization of polymorphic microsatellite loci in Aquilaria sinensis (Lour.) Gilg - Yan-Ting Zhang; Zheng-Feng Wang; Hong-Lin Cao; Xiao-Yi Li; Lin-Fang Wu; Shu-Bin Zhuo; Xiao-Feng Huang (Conservation Genetics Resources, 2010)

The CAG repeat in SCA12 functions as a cis element to up-regulate PPP2R2B expression - Chih-Hsin Lin; Chiung-Mei Chen; Yi-Ting Hou; Yih-Ru Wu; Hsiu-Mei Hsieh-Li; Ming-Tsan Su; Guey-Jen Lee-Chen (Human Genetics, 2010)

Rapid generation of dendritic cell specific transgenic mice by lentiviral vectors - Jinyu Zhang; Liyun Zou; Qin Liu; Jingyi Li; Jingran Zhou; Yong Wang; Na Li; Ting Liu; Hong Wei; Min Wu; Ying Wan; Yuzhang Wu (Transgenic Research, 2009)

Activation of Group III Metabotropic Glutamate Receptor Reduces Intracellular Calcium in β-Amyloid Peptide [31–35]-Treated Cortical Neurons - Li Zhao; Shen Ting Zhao; Zhong Ming Qian; Ce Zhang; Xiao Mei Wu; Fang Du; Ya Ke (Neurotoxicity Research, 2009)

Shear-wave splitting in the southeast of Cathaysia block, South China - Yuan Gao; Jing Wu; Jin-An Cai; Yu-Tao Shi; Shu Lin; Ting Bao; Zu-Ning Li (Journal of Seismology, 2009)

The block of intracellular calcium release affects the pollen tube development of Picea wilsonii by changing the deposition of cell wall components - Kun-Ming Chen; Guo-Li Wu; Yu-Hua Wang; Cui-Ting Tian; Jozef Šamaj; František Baluška; Jin-Xing Lin (Protoplasma, 2008)

Opposite effects of α-lipoic acid on antioxidation and long-term potentiation in control and chronically lead-exposed rats - Hui-Li Wang; Xiang-Tao Chen; Shu-Ting Yin; Jin Liu; Ming-Liang Tang; Chuan-Yun Wu; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Quercetin relieves chronic lead exposure-induced impairment of synaptic plasticity in rat dentate gyrus in vivo - Pu Hu; Ming Wang; Wei-Heng Chen; Ji Liu; Liang Chen; Shu-Ting Yin; Wu Yong; Ju-Tao Chen; Hui-Li Wang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Transplantation of NGF-Gene-Modified Bone Marrow Stromal Cells into a Rat Model of Alzheimer’ Disease - Li-Yan Li; Jin-Tao Li; Qing-Ying Wu; Jin Li; Zhong-Tang Feng; Su Liu; Ting-Hua Wang (Journal of Molecular Neuroscience, 2008)

Simultaneous analysis of microbial identity and function using NanoSIMS - Tianlun Li; Ting‐Di Wu; Laurent Mazéas; Laurent Toffin; Jean‐Luc Guerquin‐Kern; Gérard Leblon; Théodore Bouchez (Environmental Microbiology, 2008)
Summary Identifying the function of uncultured microbes in their environments today remains one of the main challenges for microbial ecologists. In this article, we describe a new method allowing simultaneous analysis of microbial identity and function. This method is based on the visualization of oligonucleotide probe‐conferred hybridization signal in single microbial cells and isotopic measurement using high‐resolution ion microprobe (NanoSIMS). In order to characterize the potential of the method, an oligonucleotide containing iodized cytidine was hybridized on fixed cells of Escherichia coli cultured on media containing different levels of 13 C or 15 N. Iodine signals could clearly be localized on targeted cells and the isotopic enrichment could be monitored at the single‐cell level. The applicability of this new technique to the study of in situ ecophysiology of uncultured microorganisms within complex microbial communities is illustrated.

Transplantation of NGF-Gene-Modified Bone Marrow Stromal Cells into a Rat Model of Alzheimer’ Disease - Li-Yan Li; Jin-Tao Li; Qing-Ying Wu; Jin Li; Zhong-Tang Feng; Su Liu; Ting-Hua Wang (Journal of Molecular Neuroscience, 2008)

Ontogeny of protease, amylase and lipase in the alimentary tract of hybrid Juvenile tilapia (Oreochromis niloticus × Oreochromis aureus) - Li Jun-sheng; Li Jian-lin; Wu Ting-ting (Fish Physiology and Biochemistry, 2006)

Characterization of action potential waveform-evoked L-type calcium currents in pituitary GH 3 cells - Yuk-Keung Lo; Sheng-Nan Wu; Chuan-Ter Lee; Hui-Fang Li; Hung-Ting Chiang (Pflügers Archiv - European Journal of Physiology, 2001)